Design and characterization of a wide-temperature-range smog chamber for atmospheric oxidation studies - Yanyong Xu; Hailiang Zhang; Shengrui Tong; Tongming Guo; Ling Zhu; Meifang Chen; Xiaofan Lv; Maofa Ge (Journal of Environmental Sciences, 2026)

Degradation of mycotoxins in cow milk by dielectric barrier discharge cold plasma and its effect on milk quality - Yike Han; Shangchen Fu; Meng Li; Siqi Wang; Yijie Lu; Wupeng Ge; Chunfeng Guo; Yuan Zhou; Zhenpeng Gao (International Dairy Journal, 2026)

Flip-Flow bioreactors enhance bioproductions with better oxygen transfer and energy saving - Ge Zhang; Manuel Tianchen Tang; Chao Li; Yongqiang Liu; Wanze Wang; Weike Guo; Xueqing Yi; Yiling Chen; Xuanming Xu; Fuqing Wu; Guo-Qiang Chen (Bioresource Technology, 2026)

A new BCI paradigm based on biological brain – digital twin brain dialogue - Ting Zhang; Rongxin Zhang; Xin Zeng; Min Zeng; Yuanhang Xu; Yue Xiong; Ge Zhang; Daqing Guo; Dezhong Yao (Cognitive Neurodynamics, 2026)

Transcription factor TaPIL1-mediated iron accumulation in wheat - Yanjun Meng; Zijia Tian; Jiayi Fan; Zhouxiang He; Bo Yu; Changqing Du; Tiancai Guo; Qiang Ge; Guozhang Kang (Plant Science, 2026)

Long-term particulate matter exposure and coronary inflammation: A large-scale cohort study assessed by pericoronary fat attenuation index - Yuan Xu; Yi Zhang; Ge Guo; Xin Meng; Jing Wei; Yuanyuan Fan; Jiageng Cai; Cencen Wu; Zhulan Cai; Penghui Zhao; Yuwen Ruan; Zhaowei Yin; et al. (Environmental Pollution, 2026)

Aerodynamic shape optimization of bridge towers based on a hybrid Softplus-Kriging surrogate model: Reducing aerodynamic interference on adjacent hangers - Dian-yi Guo; Wen-ming Zhang; Li-ming Zhao; Yao-jun Ge (Engineering Structures, 2026)

Enhancing capacitive deionization efficiency through liquid nitrogen quenching-mediated orbital symmetry breaking in cobalt-iron electronic structures - Baochang Cheng; Junchao Chen; Dongxuan Guo; Tongle Ge; Dong-Feng Chai; Jinlong Li (Desalination, 2026)

Heat-recirculation assisted syngas production from ethanol partial oxidation: Synergistic effects of composite porous media and typical additives - Huaming Dai; Mengsu Wang; Xin Ge; Zhaoxing Guo (Chemical Engineering Journal, 2026)

Directional electron/ion flux at crystalline-amorphous CoS2-MnOx heterointerface boosts water and seawater oxidation electrocatalysis - Qing Wang; Lei Yuan; Jianyu Xu; Ning Zhao; Xingmei Guo; Fangyan Zhu; Ali Tian; Zhenming Zhang; Ge Yin; Junhao Zhang (Chemical Engineering Journal, 2026)

Valorization of blue honeysuckle residue for nitrogen retention in composting: Microbial synergy mediated by differentiated electron transfer regulation - Xuan Tang; Yuhao Guo; Yueyi Liu; Zhenchao Wu; Hao Zhang; Xiujun Tu; Liangyang Mao; Weige Yao; Ying Yang; Shuo Li; Tong Yang; Tingting Xu; et al. (Biomass and Bioenergy, 2026)

A novel mycotoxin-degrading enzyme complex alleviates the combined toxicity of AFB1, DON, and ZEN in laying hens - Yan-Qi Ning; Yu Zhang; Yu-Hao Ge; Li-Jia Guo; Wen-Jie Yang; Lv-Hui Sun; Yu-Xuan Huang (Toxicon, 2026)

PbbHLH41 negatively regulates iron deficiency tolerance in pear - Zhou Xu; Yijing Ge; Shuqin Zhang; Xueqing Hui; Guoling Guo; Bing Jia; Lun Liu (Plant Science, 2026)

Hydrodynamic analysis for underwater vehicle recovery through dock integrated supporting vessel based on experimental investigation, part I: Wave sensitivity analysis - Guo Wang; Zerun Wang; Junbo Ge; Yunxiang You; Aichun Feng (Ocean Engineering, 2026)

Scaling-risk early warning in industrial cooling-water systems: A chemically regularized machine-learning framework using routine water-quality data - Jixuan Guo; Weiyi Yang; Shihan Wu; Xinyue Wei; Ruochun Wang; Ruoxin Ma; Xinyu Wu; Min-ge Tian; Hao Xu (Journal of Water Process Engineering, 2026)

Hydraulic connectivity regulates the evaporation paradox and salinization in a semi-arid lake–groundwater system - Xu Cao; Jin Hur; Xiangzhen Kong; Xiao Zhang; Chen Du; Bin Xue; Bing Yi; Yutao Guo; Xian-ge Wang; Wei He (Journal of Hydrology, 2026)

Construction of a cobalt oxide-modified anode and its enhanced chloride -to-active chlorine conversion behavior in cooling water - Yi Li; Chunxiao Liang; Junhan Yang; Yihang Guo; Honghua Ge (Journal of Environmental Chemical Engineering, 2026)

Lattice carbon-induced electronic regulation of AlCo2O4 spinels for boosting toluene oxidation - Dadao Wang; Xueqin Yang; Mimi Wu; Menglan Xiao; Yanhu Zhang; Mianmian Zhang; Xiuhong Zhu; Guangxin Ru; Yucong Guo; Bo Shi; Xiaolin Yu; Maofa Ge (Journal of Environmental Chemical Engineering, 2026)

SARMelt: MGLANet-driven high-resolution surface melt mapping of circum-Antarctic ice shelves from Sentinel-1 imagery during 2015–2023 - Lu Zhang; Qi Zhu; Dong Liang; Yiming Liu; Zherong Wu; Ji Ge; Yuqian Zhang; Huadong Guo (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Unraveling the core microbial succession during the moromi fermentation of cantonese soy sauce: An amplicon sequencing approach - Hongbiao Tang; Mouyong Zou; Xingui Zhu; Ge Tan; Liqiong Guo; Junfang Lin (Food Research International, 2026)

Cold plasma treatment enhanced defense responses against gray mold and enhances postharvest quality in cherry tomatoes - Miaomiao Ge; Ruirui Qiu; Xinzhi Fang; Ling Li; Jian Guo (Food Research International, 2026)

Adaptive seasonal management after eradicating invasive Spartina: A nature-based approach - Dong-Fan Xu; Qi Yuan; Hai-Qiang Guo; Bing Tan; Fei Quan; Zhe-Xiu Yu; Dong-Yang Han; Yu-Jiao Lu; Ying-Ying Hao; Si-Qi Zhou; Guang Ge; Bin Zhao; et al. (Ecological Engineering, 2026)

A konjac glucomannan-based hydrogel delivery system induces trained immunity via enhanced oxidative phosphorylation for improved vaccine protection - Zheng Jia; Yadong Gao; Husile Han; Chaonan Wang; Jiaqing Wang; Junjie Guo; Shuhe Zhang; Yifan Li; Junwei Ge; Fang Wang; Mingchun Gao (Carbohydrate Polymers, 2026)

Transient Trim25 Knockdown Enhances Transfection Efficiency in Two Teleost Fish Cell Lines - Yajun Wang; Xiaohuan Ge; Tiange Guo; Mengda Du; Yan He (Marine Biotechnology, 2026)

A robust HPLC-HILIC enrichment system for O-glycoproteomics profiling of plasma and cerebrospinal fluid across Alzheimer's disease progression - Zhenpeng Deng; Yan Wang; Lei Liu; Xin Guo; Haiyang Zhu; Mingming Dong; Yusong Ge; Yongliang Yu; Mingliang Ye (Analytica Chimica Acta, 2026)

Substantial mitigation of nitrous oxide realized in a light-mediated and aeration-free microalgal-bacterial consortium system - Lingfeng Wang; Weican Shi; Yanlin Liu; Zhaoming He; Jianhua Guo; Shijian Ge; Shuang Qiu (Algal Research, 2026)

Correction: Obesity Worsens Arsenic Trioxide-Induced Myocardial Toxicity and Its Protection by Metallothionein - Tingwen Ge; Lei Qian; Aiwen Li; Qiang Guo; Qiuju Liu; Jiuwei Cui (Cardiovascular Toxicology, 2026)

Numerical investigation of straight-line navigation motion response of the under-water vehicle under irregular waves - Guo Wang; Junbo Ge; JingJing Zhang; Yunxiang You; Panpan Han (Ocean Engineering, 2026)

Urinary biomarkers of emerging contaminants in relation to prevalent Parkinson's disease: An exploratory mixture and network toxicology study - Chiqun Shan; Yiming Ge; Junye Bian; Yuli Lin; Bo Fu; Qinru Xiao; Aihua Guo; Mengyan Li; Pan Xu; Yi Chen; Haobo Chen; Shaoyou Lu (Journal of Hazardous Materials, 2026)

Tandem mass tag-based quantitative proteomics reveals the relationship between protein changes and off-flavor in chilled fresh pork treated with electron beam irradiation - Lei Sun; Fengqin Ge; Leting Sun; Qizhen Guo; Feng Li; Dongxiao Sun-Waterhouse; Yongli Wang (Food Research International, 2026)

Investigating Microbial Communities and Metabolic Dynamics in Jiupei from Cellars of Different Ages: An Integrated Amplicon and Metabolomic Analysis of Mianrou-Style Baijiu - Longyun Zhang; Chun Pu; Congzhi Zhang; Fengxue Guo; Jiaojiao Song; Xiangyang Ge; Yan Xu (Food Bioscience, 2026)

Long-term outdoor artificial light at night and psychological symptoms among Chinese adolescents: Findings from a national school-based survey - Wenxin Ge; Jun Hong; Liqing Yao; Qiqi Lai; Jingyang Fang; Lixin Hu; Zhengge Jin; Wanxin Wu; Sichun Lin; Yinhuan Guo; Chang Qi; Xiaojian Yin; et al. (Environmental Research, 2026)

Retraction notice to ‘Association between prenatal exposure to ambient particulate matter and risk of hypospadias in offspring: A systematic review and meta-analysis’ [Environ. Res. 192 (2021) 110190] - Hua-Chuan Lin; Jing-Min Guo; Pin Ge; Ping Ou (Environmental Research, 2026)

Synergistic charge-size trimetallic design PVDF@Mn-co/Al-LDH for efficient lithium selectivity from high-Mg/Li ratio brine - Sehria Zia; Muhammad Kashif; Haojie Ge; Yafei Guo; Tianlong Deng (Desalination, 2026)

Curdlan-mangiferin composite hydrogel encapsulating coenzyme Q10 alleviates dry eye disease by improving mitochondrial function - Wenshuo Han; Yaning Liu; Huanhuan Ge; Hanwen Guo; Xinqi Zhao; Zijian Gao; Guohu Di; Xianggen Wu; Lei Tian; Peng Chen; Xiaoping Zhang (Chemical Engineering Journal, 2026)

The development of a constitutive promoter library for Cupriavidus necator to produce polyketides - Ziqi Jin; Xu Yan; Fang Yang; Ge Zhang; Guo-Qiang Chen (Chemical Engineering Journal, 2026)

Effects of starch degradation and starch-lipid complexes recombination on starch digestion under cold plasma regulation - Yuan Jiang; Xingrong Pan; Yuanfang Sun; Jingru He; Sihan Cheng; Zonnglin Guo; Kun Hu; Xiangzhen Ge (Carbohydrate Polymers, 2026)

Investigation of changes in microbial communities and metabolites for the nutrient re-utilization of fermented agricultural wastes in watermelon - Tong-Lu Wei; Yan-Ge Li; Mao-Song Pei; Hai-Nan Liu; Xue-Jie Zhu; Zhong-Hou Zhu; Da-Long Guo (Biomass and Bioenergy, 2026)

Influence of Interbedded Soft and Hard Rock on Rock Burst and Microseismic Activities in Deeps: Case Studies - Yue-Mao Zhao; Zheng-Chen Ge; Peng-Xiang Li; Kai Liu; Ben-Guo He; Xing-Dong Zhao; Guo-Qiang Zhu (Rock Mechanics and Rock Engineering, 2026)

WeedsDetectNet: A green attention and adaptive joint feature fusion network for weed detection in agricultural fields - Baoquan Ge; Zhenhong Jia; Ao Guo; Wei Chen; Jiajia Wang; Sensen Song; Gang Zhou (Crop Protection, 2026)

Making waves: Towards sustainability in wastewater management through the biological-ecological coupling system - Changjie Zhao; Zhen Hu; Baolei Guo; Liang Zhang; Jian Zhang; Shijian Ge (Water Research, 2026)

ST-SRNet: A deep learning framework for seismic response prediction of subsea tunnels - Yimu Chen; Kang Ge; Yutao Guo; Chao Hou; Zhenzhong Hu (Tunnelling and Underground Space Technology, 2026)

Molecular Evidence for Distinct Coastal Dissolved Organic Matter Responses to Nitrogen and Phosphorus Enrichment - Xin Guo; Junfeng Chen; Xiao Chen; Lianbao Zhang; Gang Li; Hongwei Ren; Bokun Chen; Yubin Hu; Ge Xu; Dingxi Zhang; Chen He; Quan Shi; et al. (Journal of Environmental Sciences, 2026)

The effects of biochar on ryegrass growth and microbial diversity in ionic rare earth tailings soil - Huijuan Wang; An Guo; Xinjin Xiao; Jin Huang; Fangfang Xie; Liusheng Ge; Yangwu Deng; Xiaoping Liu (Journal of Environmental Sciences, 2026)

Co-evolution of the pangenome, mobile genetic elements, and antimicrobial resistance genes reveals the public health risks of the dominant Salmonella 4,[5],12:i:- ST34 clone - Jiawen Chen; Shuaicheng Wu; Laiyu Fu; Yan Li; Xiaoxiao Duan; Yanling Liu; Yichi Zhang; Xindong Ge; Yongda Zhao; Lili Guo (Food Research International, 2026)

Exploring the endogenous and exogenous key aroma-active components in three aroma types of black teas from different cultivars - Weixuan Li; Zhouling Zhong; Han Yan; Longyu Guo; Ge Chen; Zhi Lin; Haipeng Lv; Yue Zhang; Yin Zhu (Food Research International, 2026)

Association study on the regulation of muscle development-related genes, proteins, and metabolites in different tissues by gastrointestinal flora during various developmental stages of Liaoning cashmere goats - Yinggang Sun; Xingtang Dou; Qingyu Yuan; Ran Duan; Qiying Zhan; Taiyu Hui; Yanjun Qiao; Jiaqi Li; Wangshu Li; Yunlong Guo; Dakun Lyu; Jiaqi Ge; et al. (Food Chemistry, 2026)

Inactivation effects of plasma-activated water against rice blast disease - Miaomiao Ge; Jian Guo; Xinzhi Fang; Jiaoyu Wang; Ling Li (Food Control, 2026)

Two-step pyrolysis enabled by bentonite catalysis for the co-production of bioactive humic acid and functional carbon-clay composites - Huanhuan Li; Jiarun Duan; Lijuan Zhang; Yong Wen; Yun Xiang; Chen Qiu; Junmei An; Zhiguo Guo; Yidong Cai; Changchun Ge; Xiaona Ren; Xinjiang Zhou; et al. (Environmental Research, 2026)

Characteristics analysis and experimental verification of supercritical water gasification continuous reactor based on thermal-fluid-structure interaction model - Jiasunle Li; Xinyu Li; Taizhen Liu; Zhiwei Ge; Liejin Guo (Chemical Engineering Journal, 2026)

A flexible antigen-presenting cell targeting lentinan immunomodulator promotes stimulator of interferon gene-driven cancer therapy - Jiaqian Miao; Junjie Wang; Qianli Zhu; Xiangshu Cheng; Jingxuan Ju; Minxia Zhang; Jiaxuan Guo; Li Xu; Guangbo Ge; Mingming Jin; Hongping Deng (Carbohydrate Polymers, 2026)

CRISPR/Cas9 mediated knockout of MeSSI enhances resistant starch content without compromising yield in cassava - Xiaohua Lu; Yajie Wang; Yannian Che; Yuheng Li; Baochang Nong; Yujian Ge; Xiangwen Wang; Yuxuan Guo; Ruimei Li; Jiao Liu; Jianchun Guo; Yuan Yao; et al. (Carbohydrate Polymers, 2026)

Quantifying ozone vertical transport over the Beijing–Tianjin–Hebei region: Insights from WRF-CAMx flux simulations - Hanyu Zhang; Jungang Wang; Yucong Guo; Maofa Ge; Hailiang Zhang; Zhiliang Yao (Atmospheric Pollution Research, 2026)

Advances in Alzheimer’s disease: mechanistic insights and therapeutic targets - Yu-Juan Jia; Yi-Jun Ge; Bowei Li; Ying Yang; Huaqiu Chen; Jie Liu; Jun-Hong Guo; Jin-Tai Yu; Ke-Qiang Ye; Jian-Zhi Wang; Weihong Song; Yan-Jiang Wang (Science China Life Sciences, 2026)

Chloride attenuates lime-induced cadmium immobilization in the soil-rice system - Jingxia Guo; Madinai Abulimiti; Yuqing Wu; Chenghao Ge; Dongmei Zhou; Yanhui Chen (Plant and Soil, 2026)

Characterization of an Endophytic Fusarium odoratissimum Strain 25# from Dysosma versipellis with Putative Podophyllotoxin Production - Xiao-Ming Tan; Zheng-Hu Guo; Xiang-Hua Xia; Xin-Yi Xie; Wen-Tao Tan; Chang-Ge Yuan; Yun-Sheng Wang; Ya-Qin Zhou (Current Microbiology, 2026)

Differential responses of soil microbial biomass and diversity to long-term phosphorus fertilization: A global meta-analysis - Jiahao Ge; Xiaoyi Han; Xinyue Lei; Qixuan Wang; Pengyue Wu; Nanhai Zhang; Yuying Guo; Pu Yang; Baili Feng; Jinfeng Gao (Agriculture, Ecosystems & Environment, 2026)

Short-Term Passive Acoustic Monitoring Indicates Associations Between Fish Vocal Activity and Offshore Wind Farm Noise - Qitong Ge; Shouguo Yang; Hongyi Guo; Xuguang Zhang; Xianming Tang (Fishes, 2026)
The rapid expansion of offshore wind farms (OWFs) is reshaping coastal soundscapes through operational turbine noise, while the acoustic responses of soniferous fishes within operational wind-farm areas remain difficult to assess using conventional fishery surveys. In this study, passive acoustic monitoring (PAM) was deployed within the Yangjiang Offshore Wind Farm to examine short-term associations among underwater sound fields, turbine spatial layout, a turbine startup event, and putative fish-call activity. Fish-call detections were lower along the transect with 550 m turbine spacing than along the 1300 m transect, coinciding with higher measured sound pressure levels in the 550 m spacing layout. Acoustic activity in the central zone of the 1300 m array was 6.46 times higher than that of the 550 m layout, suggesting that lower-noise areas within wind farms may provide favorable acoustic conditions for detectable fish-calling activity. During a turbine startup event, fish-call detection rates temporarily decreased during the transient increase in sound pressure level and subsequently recovered as the underwater noise returned toward baseline conditions. These patterns indicate that PAM can capture short-term soundscape-associated variation in fish-calling activity or call detectability. We further propose a conceptual trade-off framework in which foundation-associated habitat benefits and operational noise may jointly shape the acoustic space use of soniferous fishes in OWFs.

Functional differences between healthy and stressed soils: Rare and abundant root exudates as a regulatory switch for quorum sensing in rhizosphere microbiota - Yueyi Liu; Zhenchao Wu; Zeming Ye; Liangyang Mao; Xiujun Tu; Yuhao Guo; Weige Yao; Ying Yang; Shuo Li; Jie Kang; Baiyan Cai; Jingping Ge (Plant and Soil, 2026)

Quercetin exerts radioprotective effects against radiation-induced intestinal injury with involvement of the PI3K-AKT/Caspase-3 axis - Qing Guo; Zhibing Tang; Zhenyu Hou; Ge Yan; Jiaxuan Wang; Man Zhang; Ruige Ma; Juan Wang; Qiong Feng; Zhen Wang; Chunlei Wang; Lin Zhao (Molecular and Cellular Biochemistry, 2026)

Effect of plasma-activated water and calcium treatment on the softening of apricot fruit based on WSP changes - Mengpei Liu; Wanrui Li; Ge Li; Xiaopeng Wei; Chunyan Jia; Xin Guo; Haifei Lu (Journal of Plant Growth Regulation, 2026)

Antibacterial, insecticidal, and α -glucosidase inhibitory constituents of Cyclea racemosa Oliv. - Jing Li; Guiqin Li; Fanrong Yang; Yucheng Huang; Yafeng Wang; Bingyuan Yang; Zhangbin Liu; Lunfa Guo; Biqun Zou; Kedi Yang; Li Ge; Yonglin Huang; et al. (Natural Product Research, 2026)

Brain-wide mapping and region-specific cellular characterization of Trhr1 reporter-labeled cells in mice using VISoR imaging - Mingrui Zhang; Su Ma; Hanbo Guo; Yuehan Ji; Hong Ni; Rongjing Ge; Yuanyuan Wang; Yong Jiang; Lianjun Li; Yuyang Zhu; Qian Wang; Lingxiao Guo; et al. (Brain Structure and Function, 2026)

From supply–demand imbalance to functional synergy: ecosystem service bundles and network structures in a mountainous megacity, China - Dawen Qian; Hongyi Guo; Limin Tan; Zechang Chen; Yunlong Zhang; Chen Ge (Environment, Development and Sustainability, 2026)

Genomic and genetic insights into the divergence between indica and japonica rice - Xiangxi Zhuansun; Wenlong Guo; Siqi Xia; Jun Shu; Kai Wang; Qiyu Zhang; Hao Wen; Lina Du; Siyu Wen; Ge Gao; Junran Wang; Dan Wang; et al. (Science Bulletin, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Investigation on the temperature dependence of decomposition reaction mechanism of C4F9OC2H5 - Biao Zhou; Xikang Zhang; Xingjian Kang; Muying Ge; Yang Guo; Kai Wang; Hideki Yoshioka (Journal of Fluorine Chemistry, 2026)

Bridging semantics and geometry: A decoupled LVLM–SAM framework for reasoning segmentation in optical remote sensing - Xu Zhang; Junyao Ge; Yang Zheng; Kaitai Guo; Jimin Liang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Corrigendum to “Preparation of multifunctional hydrogel composed of polyvinyl alcohol/ chitosan/cellulose nanofiber/anthocyanin and its application in intelligent food packaging systems” [Food Res. Int. 235 (2026) 119173] - Zhen-Zhen Lu; Jie Chen; Jing Jin; Xiao-Rui Ge; Xiao-Hui Yao; Wei-Guo Zhao; Dong-Yang Zhang (Food Research International, 2026)

Preparation of multifunctional hydrogel composed of polyvinyl alcohol/ chitosan/cellulose nanofiber/anthocyanin and its application in intelligent food packaging systems - Zhen-Zhen Lu; Jie Chen; Jing Jin; Xiao-Rui Ge; Xiao-Hui Yao; Wei-Guo Zhao; Dong-Yang Zhang (Food Research International, 2026)

Lignin degradation enhancement in poultry manure and maize residue composting via flax retting waste liquid and biochar: Dominant microbial generalist species mediated - Tong Yang; Xiujun Tu; Xuan Tang; Yuhao Guo; Yueyi Liu; Zhenchao Wu; Hao Zhang; Ying Yang; Shuo Li; Weige Yao; Jinyu Du; Tingting Xu; et al. (Food and Bioproducts Processing, 2026)

Urban heat exposure patterns and domain-specific executive function in adolescents - Lixin Hu; Wenwen Bao; Zhengge Jin; Jun Hong; Wenxin Ge; Yawen Tan; Liqing Yao; Wanxin Wu; Jiaqi Chen; Xiuzhi Yang; Zhuowen Wu; Sichun Lin; et al. (Environmental Research, 2026)

Numerical manifold method for compression molding of granular materials - Xuezhen Zhai; Yuchen Guo; Yongjia Zhang; Rui Yue; Liuchen Shu; Youjun Ning; Pengwan Chen; Ge Kang (Computers and Geotechnics, 2026)

From gas-liquid to liquid-liquid: A programmable compartmented droplet microreactor under ambient conditions - Gaojian Chen; Duo Wei; Junhao Zhu; Rong Guo; Lingling Ge (Chemical Engineering Journal, 2026)

SIRT6 alleviates ischemic injury via orchestrating the RREB1/Snail and STC1/Smad7 signaling pathways to regulate endothelial-mesenchymal transition - Zhentao Zhang; Zheyan Fang; Shuang Zhao; Mukaddas Abdurahman; Gang Zhao; Runyang Feng; Zhenyang Guo; Xueting Yu; Hangnan Hong; Jilong Geng; Xiansu Nie; Supuya Abuduwahapi; et al. (Science China Life Sciences, 2026)

Phytolith-occluded carbon sequestration by Suaeda salsa in the Yellow River Delta estuarine channel shifts: opportunities for improved salt marsh management - Li Zhang; Bowen Rong; Changzi Ge; Xiangxing Gao; Cuilian Guo; Shaobin Han (Journal of Soils and Sediments, 2026)

Prediction of the joint toxicity of microplastics and organic pollutants on algae based on machine learning - Jing Lu; Yang Song; Bin Hou; Ge Guo; Yating Jia (Marine Pollution Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Population responses to climate change in the marginal areas of the dryland in East Asia since the LGM - Yanyan Yu; Junyi Ge; Junyan Geng; Haibin Wu; Amber Johnson; Feng He; Zhengtang Guo (Quaternary Science Reviews, 2026)

Integrative palynology and UPb zircon geochronology of the Jiufengshan Formation (upper Aptian, Dayangshu Basin, NE China): Evidence for early angiosperm expansion at mid-latitudes - Yan Zhang; Iván R. Barreiro; Chuan-biao Wan; Wen-chun Ge; Guo-chen Wang; Yun-fei Xue; Ti Li; Xin Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Early-life and lifelong exposure to environmentally relevant enrofloxacin reorganizes a proteobacteria-centered gut-lipid-resistome steady state in marine medaka - Ziyi Guo; Zheyu Wang; Yaxin Liu; Meiru Wang; Hongyue Ma; Ziwei Wang; Siyuan Zhang; Yidan Chang; Hezi Ge; Chenglu Li; Hui Yang; Hui Miao; et al. (Journal of Hazardous Materials, 2026)

Low-carbon electro-assisted biological treatment of fluoronitrobenzene with DFT-guided cathodes and RSM optimization - Le Huang; Zhipeng Ge; Xili Wang; Jiaze Liu; Huajun Feng; Hai Xiang; Qiaoqi Guo (Journal of Environmental Sciences, 2026)

Polygonatum kingianum polysaccharides delay aging through UPRmt-mediated regulation of mitochondrial function and intestinal homeostasis - Jing-Juan Yang; Sheng-Lan Zhao; Ya-Ge Ma; Jian-Guo Jiang; Xi Zhang (Food Bioscience, 2026)

Carbon-doping-induced adsorption energy gradient for highly selective alkynol semi‑hydrogenation over PdCu catalysts - Yuan Ren; Jiapeng Huang; Yaohui Zhao; Ruiyun Guo; Yanan Li; Zixin Ge; Qian Wang; Junhao Lu; Anyu Feng; Chenyao Xiao; Mingshang Jin (Chemical Engineering Journal, 2026)

Co NPs@N-Doped Peanut Shell-derived Biochar As an Efficient Catalyst for Peroxymonosulfate Activation in Acetaminophen Degradation - Xiaoxin Chen; Xingzi Zhu; Caiyan Ge; Jinxin Wang; Manli Guo; Yujuan Cao; Bixia Lin (Water, Air, & Soil Pollution, 2026)

Reducing wheat grain Cd via harnessing indigenous microbiota in weakly alkaline soil - Chenghao Ge; Yixuan Wang; Wenyan Ma; Hong-Bo Li; Jingxia Guo; Hafiz Adeel Ahmad; Yan Gao; Dongmei Zhou (Plant and Soil, 2026)

Sea Spray Aerosol Generation Techniques and Their Influence on Heterogeneous Chemistry - Xingchen Yang; Yiming Huang; Ting Lei; Yucong Guo; Xiang He; Maofa Ge; Weigang Wang (Aerosol Science and Engineering, 2026)

A Novel Wave-Absorbing Support System for Mitigating Rock Burst in Deep-Buried Hard Rock Tunnels - Yue-Mao Zhao; Zheng-Chen Ge; Ben-Guo He; Cheng-Xiang Yang; Xing-Long Li; Xiao-Jun Yu; De-Xian Li; Yong-Ping Liu (Rock Mechanics and Rock Engineering, 2026)

Local administration of polymyxin B-conjugated Akkermansia muciniphila outer membrane vesicles attenuate asthma by suppressing M2 macrophage polarization - Chenchen Hou; Wenhui Sun; Lina Wang; Xiahui Ge; Qiyun Tu; Huaqi Guo; Tianyu Zhou; Lifeng Yan; Weining Xiong (Science China Life Sciences, 2026)

A physics-informed hybrid framework for dynamic wellhead pressure prediction and equipment safety assessment in high-temperature high-pressure condensate gas wells - Lu Zou; Ming Tang; Shiming He; Taiheng Zhang; Ge Wang; Xinyu Guo; Xuliang Zhang; Huajun Li (Process Safety and Environmental Protection, 2026)

Chemically modified bacterial cellulose–mediated fiber salting-out method for preparing tough hydrogels - Bei Zhang; Xin-Xin Chen; Xiao-Rui Ge; Xin-Ping Wang; Xiao-Hui Yao; Wei-Guo Zhao; Tao Chen; Dong-Yang Zhang (Carbohydrate Polymers, 2026)

Electric field as a priming trigger reshaping redox network for synergistic perfluorooctanoic acid degradation and humus synthesis during aerobic composting - Yueyi Liu; Zhenchao Wu; Hao Zhang; Xuan Tang; Weige Yao; Ying Yang; Shuo Li; Tong Yang; Jinyu Du; Tingting Xu; Yu Su; Yaqi Huang; et al. (Bioresource Technology, 2026)

Seasonal characteristics of atmospheric oxidizing capacity at environmental background area in North China from long-term field observations of O3, HONO and HCHO - Shuangshuang Ge; Zhiqiang Ma; Hailiang Zhang; Hanyu Zhang; Weiwei Pu; Yulu Qiu; Jinlong Hou; Chao Liu; Yucong Guo; Fan Dong; Di He; Liyan Zhou; et al. (Atmospheric Environment, 2026)

Genetic deletion of miR-200a/200b increases growth and feed conversion efficiency in yellow catfish - Xu Wang; Yan Xie; Qiaohong Lin; Yang Xiong; Ying Liu; Si Ge; Qiuen Tan; Zhipeng He; Youbo Jiang; Qingqing Han; Shuang Jin; Peipei Huang; et al. (Science China Life Sciences, 2026)

Endoplasmic Reticulum Stress in the Keratinocytes Contributes to Chronic Itch by Activation of Lipocalin 2/MC4R/TRPV1 Pathway - Wei Ge; Yu Feng; Li Zhang; Qian-Liang Wang; Cheng-Wei Zhang; Zhi-Hong Wang; Guo-Kun Zhou; Shi-Yu Sun; Xiu-Hua Miao; Tong Liu; Bin Wu; Jun Yan (Neuroscience Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Enhanced dust removal with charged active water mist: Insights from macro-experiments and molecular simulations - Liying Sun; Shaocheng Ge; Jiace Guo; He Liu; Weizhi Zhao; Yongliang He; Jiacheng Nie (Journal of Environmental Chemical Engineering, 2026)

Development of high-efficient CuFeZnAl-based hydrotalcite catalyst for glycerol hydrogenolysis to 1,2-propanediol - Yuanyuan Ge; Yifan Ma; Zhikuan Lin; Zhihang Lai; Haijun Guo; Bo Chen; Hairong Zhang; Lian Xiong; Xinde Chen; Zhili Li (Journal of Environmental Chemical Engineering, 2026)

Co-gasification coupled with steam reforming of inseparable livestock biowastes for green hydrogen-rich syngas production - Jiarui Zhu; Qiuhan Pu; Liang Wang; Ge Kong; Zengjian Guo; Ru Sun; Guanyu Zhang; Xin Zhang; Xuesong Zhang; Lujia Han (Journal of Environmental Chemical Engineering, 2026)

The effect of metakaolin on the properties of MSWI fly ash-slag binder: Compressive strength and chloride ions immobilization - Junjie Zhang; Zhaocheng Guo; Ge Zhang; Ting Zhang; Xuefeng Song (Journal of Environmental Management, 2026)

Deep learning-based realtime multiload response prediction and inverse analysis of offshore bridges - Zhu-Yu Sun; Yu-Tao Guo; Kang Ge; Chao Hou; Zhen-Zhong Hu (Engineering Structures, 2026)

Three-terminal quantum dot LEDs with integrate-and-fire neuron for on-device encryption - Ge Zhou; Youjiang Pan; Hailong Hu; Tailiang Guo; Fushan Li (Chemical Engineering Journal, 2026)

Molecular identification and genetic diversity of Echinococcus granulosus sensu stricto in livestock from Qinghai lake on the Qinghai-Tibetan plateau - Jun He; Guoyan Zhou; Fan Zhang; Hongrun Ge; Ao Chen; Ru Meng; Zhihong Guo; Yijuan Ma; Yong Fu (Veterinary Research Communications, 2026)

Gut commensal Lactobacillus strain induces a balanced trained immunity phenotype to enhance vaccine efficacy through JAK-STAT-SOCS pathway - Lingdi Niu; Hai Li; Junjie Guo; Zheng Jia; Qingru Chang; Ning Liu; Shuhe Zhang; Junwei Ge (Probiotics and Antimicrobial Proteins, 2026)

Integrated multi-omics analyses elucidate the key regulatory networks in response to Tomato brown rugose fruit virus infection in Solanum lycopersicum L. - Huiyan Guo; Xue Dong; Yue Wang; Qingtao Ge; Yimin Tan; Jiaxing Zhang; Xueqing Zhuang; Zhiping Wang; Mengnan An; Zihao Xia; Xueqing Yang; Yuanhua Wu (Plant Cell Reports, 2026)

Multi-omics characterization of benzo[a]pyrene toxicity networks identifies SERPINE1 and STK3 as prognostic biomarkers and therapeutic targets in head and neck squamous cell carcinoma - Yan Guo; Jiarui Zhang; Jingchun Ge; Liang Li; Ming Liu; Linli Tian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A network pharmacology-based study on the mechanism of hirudin attenuates renal interstitial fibrosis through Nrf2 and NF-κB signalling pathways - Kang Yang; Yijiao Wang; Xiaoxia Xun; Hao Zhao; Guanting Chen; Tao Li; Jinhua Ge; Siyu Guo; Shengtao Ye; Zhenzhen Wang; Yaoxian Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

3D GCN–CNN Hybrid Model for 3D Mineral Prospectivity Modeling of Porphyry- and Skarn-Type Mineralization - Xiaohui Li; Chengrui Zhao; Feng Yuan; Yue Li; Chaojie Zheng; Mingming Zhang; Can Ge; Dong Guo; Xueyi Lan; Sanming Lu (Natural Resources Research, 2026)

Environmental drivers and ecological processes underlying microbial community zonation in deep-sea polymetallic nodule sediments - Ning Guo; Wenquan Zhang; Tingting Li; Huameng Ge; Zepeng Zhang; Weizhe Li; Dewi Seswita Zilda; Ocky Karna Radjasa; Bailin Cong; Chengcheng Li; Shenghao Liu (Marine Environmental Research, 2026)

Study on the migration mechanism of heavy metals in the supercritical water gasification of coal - Hao Sun; Jiayi Yu; Zhiwei Ge; Liejin Guo (Journal of Hazardous Materials, 2026)

Mechanism of polystyrene microplastics facilitating the intestinal absorption of dietary Zn in daphnia under trophic transfer - Jingyi Guo; Ruohua Qu; Na Liu; Fei Ge (Journal of Environmental Sciences, 2026)

Numerical simulation of refracturing fracture propagation behaviors under non-uniform pore pressure field for the waterflooded reservoir - Xian Shi; Xiaoxin Ge; Wanqiang Gu; Wei Liu; Qi Gao; Anhai Zhong; Liaoyuan Zhang; Tiankui Guo (Geomechanics for Energy and the Environment, 2026)

Effects of carbonization temperature on the synthesis and antibacterial properties of honeysuckle carbon dots: Application in extending pork shelf life - Leyi Li; Gege Su; Yiheng Deng; Xue Pan; Jiayin Hou; Wenhao Luo; Hua Zheng; Hongtao Lei; Xiangzhen Ge; Zonglin Guo (Food Packaging and Shelf Life, 2026)

Ecological effects and strategies of Spartina alterniflora Loisel. removal in China - Zhanbin Luo; Fu Chen; Xi-En Long; Jing Ma; Jiyou Wei; Yudi Guo; Yanfeng Zhu; Yongjun Yang; Xiaoping Ge; Yanyan Kang; Ming Zou; Lei Liu; et al. (Environmental Impact Assessment Review, 2026)

Dipole-engineered pyridinium iodide passivation for efficient Sn-Pb and all-perovskite tandem solar cells - Ciyu Ge; Chenwei Ni; Qi Xu; Bokai Hao; Wei Ai; Chengjie Deng; Peiyan Zhang; Xinzhi Zu; Hongyan Lu; Zeyu Zhang; Weijun Ke; Haisheng Song; et al. (Chemical Engineering Journal, 2026)

Additive manufacturing of silicon nitride ceramics via DLP: A synergistic engineering strategy for achieving ultra-high solid loading slurries - Qing Qin; Zihan Guo; Runze Liu; Siran Yin; Gang Xiong; Zhen Shen; Xiaojun Zeng; Changchun Ge (Chemical Engineering Journal, 2026)

Chemical looping oxidation mechanism of methanol in supercritical water - Chenxi Gu; Jindi Du; Kangsen Chen; Changwei Guo; Taizhen Liu; Zhiwei Ge; Liejin Guo (Chemical Engineering Journal, 2026)

Predicting Remaining Oil Saturation in Complex Carbonate Reservoirs via Constrained BSEM Inversion and an IP-Inclusive Saturation Model - Yao Lu; Zu-Zhi Hu; Wei Wan; Ya-Neng Luo; Guo Zhao; Ke Yang; Shuai-Yin Ge; Zhan-Xiang He; Yun-Sheng Zhao (Applied Geophysics, 2026)

Influences of Structural and Species Diversity on Forest Resistance to Drought - Erin T. H. Crockett; Qinfeng Guo; Jeff W. Atkins; Ge Sun; Kevin M. Potter; Jennifer K. Costanza; Scott V. Ollinger; Christopher W. Woodall; Steven McNulty; Carl Trettin; Justin Holgerson; Jingfeng Xiao (Ecology Letters, 2026)
Biodiversity can enhance forest resistance to drought, but the forms of diversity involved and conditions under which diversity confers resistance remain unclear. We used Forest Inventory and Analysis (FIA) plot data to examine whether four variables—structural richness (variation in tree heights, stand density, canopy cover and/or spatial heterogeneity), species richness (number of tree species), structural evenness and species evenness—are associated with the resistance of net primary productivity to drought and whether these relationships change with drought severity and by ecoregion. Structural richness was positively associated and species evenness was negatively associated with resistance, but the strength of these relationships varied by ecoregion. Relationships between structural richness and resistance and between species evenness and resistance became stronger under more severe droughts, supporting the stress gradient hypothesis. Forest managers cannot readily change abiotic conditions but could increase structural richness and select certain species to enhance forest resistance to drought.

Sustainable alternative to biological nitrogen removal: Is ammonia recovery from municipal wastewater a fantasy? - Wenjie Hao; Yuanyuan Yu; Yi Gong; Ge’er Wang; Maoqin Ao; Minyuan Han; Haoquan Zhang; Qingxiang Guo; Jingmei Yao; Yi Yang; Zhongbo Zhou; Le Han (Water Research, 2026)

New Pachyportax fossils from the Late Miocene Shuitangba locality, Yunnan, revealing the early Bovini evolution and radiation - Ding-Ge Guo; Sayyed Ghyour Abbas; Qi-Gao Jiangzuo; Chun-Xiao Li; Yan-Wu Yang; Jia-Yong Cao; Bin Zou; Shi-Qi Wang; Xue-Ping Ji (Palaeoworld, 2026)

Exogenous melatonin alleviates heat stress-induced metabolic slowdown affecting broiler growth by improving lipid metabolism - Fei Song; Binglin Wang; Xin Kang; Aige Han; Huiyuan Rui; Xiangyang Xu; Yi Guo; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2026)

Retention time prediction of emerging contaminants via transfer learning with graph neural networks - Jiewen Deng; Junbin Chen; Jingyi Wang; Xingying Li; Sisi Liu; Linke Ge; Guang-Guo Ying; Chang-Er Chen (Journal of Hazardous Materials, 2026)

Beyond zinc porphyrins: Immobilized algal chlorophyllin carboxylates as hydrophilic carbonic anhydrase mimics for recyclable CO2 capture - Yong Xiang; Daoyong Yu; Yi Zhao; Rujing Guo; Jialin Chen; Baosheng Ge; Zijun Xiao (Journal of Environmental Chemical Engineering, 2026)

Dual-enzyme co-immobilized aluminum-based metal-organic frameworks with hierarchical structure: Efficient and stable dual-enzyme cascade catalyst - Xia Gao; Huibin Pan; Weitong Dang; Jinhang Guo; Chengfang Qiao; Qian Liu; Chunsheng Zhou; Hongguang Ge; Yaqiang Zhang (Journal of Environmental Chemical Engineering, 2026)

Enhancement of selective lithium extraction from α-spodumene by autoclaving with NaOH and NaAlO2 at 200–300 °C - Shuhao Dong; Yakai Yang; Hao Zhang; Meiyan Yu; Hui Guo; Ge Kuang; Haidong Wang; Xiaohui Fan (Hydrometallurgy, 2026)

The integration of hydrogen-rich gases activation with coal tar cracking over encapsulated Ni-based catalysts for in-situ upgrading coal pyrolysis volatiles - Mingyi Wang; Jiaofei Wang; Xiangyang Guo; Shiyu Tang; Ge Gao; Junwen Wang (Fuel, 2026)

Ultrasound-assisted extraction of peptidoglycan from Lactiplantibacillus plantarum: Structural characterization, anti-browning enhancement, and immunomodulatory effects - Yuwei Sun; Kemin Guo; Peiyun He; Dongning Li; Yunshu Ge; Guoqiang Zhang; Xuebo Liu (Food Chemistry, 2026)

CMSS1 promoted CXCL8-CXCR1/2 pathway to accelerate the invasion and immune escape of triple-negative breast cancer - Dequan Ding; Min Li; Xue Guo; Ge Wu; Yan Zhang (Journal of Molecular Histology, 2026)

Comparative Analysis of Physicochemical Properties, Sensory Characteristics, and Microbial Communities in Jiupei Fermented with the Peel and Core of Houhuo Daqu - Dongying Ge; Wenchao Cai; Chunhui Shan; Zhongjun Liu; Zhuang Guo (Current Microbiology, 2026)

Pseudonocardia mahuensis sp. nov., Isolated from Sediment of Mahu Lake in China - Chaolan Liu; Liwei Zhou; Zhuoxin Du; Jianghua Li; Lufeng Dan; Yan Ge; Guoqing Zhuang; Yidong Guo (Current Microbiology, 2026)

Obesity Worsens Arsenic Trioxide-Induced Myocardial Toxicity and Its Protection by Metallothionein - Tingwen Ge; Lei Qian; Aiwen Li; Qiang Guo; Qiuju Liu; Jiuwei Cui (Cardiovascular Toxicology, 2026)

Ethambutol induces optic neuropathy through SDHB-mediated ferroptosis in retinal ganglion cells via Smad4 pathway - Qiushi Li; Wei Ge; Yifan Zhang; Qibin Xu; Junli Xu; Yu Zhang; Xingneng Guo; Wenyan Sheng; Liwei Zhu (Human Cell, 2026)
Ethambutol (EMB)-induced optic neuropathy (EON) is a clinical concern. Ferroptosis, involving iron and toxic reactive oxygen species (ROS), causes unique cell death, but its mechanism in EON is unclear. This study aims to explore the EON mechanisms. Wistar rats were used to establish an EON model by administering EMB at 50 mg/kg daily for 8 weeks. Retinal ganglion cells (RGC-5 cells) were used for in vitro experiments. Histological staining, MTT assays, flow cytometry, western blot analysis, dual-luciferase reporter assay, chromatin immunoprecipitation, and high-throughput sequencing were conducted to investigate cell death modes and molecular changes. EMB treatment leads to significant cell loss and structural damage in RGCs of EON model, predominantly through ferroptosis. We confirm increased ROS levels, downregulation of SLC7A11 and GPX4, and decreased glutathione (GSH) levels, upregulation of malondialdehyde (MDA) and 4-hydroxynonenal (4-HNE) levels in EMB-treated RGC-5 cells. Furthermore, sequencing data reveal that in RGC-5 cells treated with EMB, the differentially expressed genes (DEGs) primarily exhibited alterations in biological functions associated with metabolism, stress response, and apoptotic regulation. Specifically, EMB inhibits the expression of succinate dehydrogenase enzyme B (SDHB), thereby disrupting antioxidant defenses and facilitating ferroptosis. Moreover, Smad4 has been pinpointed as a pivotal transcription factor in regulating SDHB expression. Notably, its interaction with the promoter region of SDHB is inhibited by EMB. This study provides compelling evidence for the involvement of ferroptosis in EON and highlights SDHB and Smad4 as potential therapeutic targets for mitigating this adverse effect.

Effects of ocean acidification on intestinal homeostasis and organismal performance in a marine bivalve: From microbial shifts to physiological suppression - Minggui Liu; Xiaoyu Guo; Lanfang Han; Yuanyuan Zhao; Chengjun Ge (Marine Pollution Bulletin, 2026)

Comprehensive assessment and policy implications of pesticide packaging waste management in China - Wenjie Shangguan; Can Wang; Qiliang Huang; Zongjie Ren; Hongyi Liu; Chunli Xu; Ge Chen; Dukang Ma; Yongwang Guo; Lidong Cao (Waste Management, 2026)

Copper exposure induces autophagy and angiogenesis in liver cell via ATF4 activation independent of TFEB - Meng Zhang; Yi-Ge Zhang; Yu-Tian Shi; Xiao-Chuan Qu; Yu-Heng Li; Ji-Xing Miao; Guo-Ming Sun; Peng Ge; Bao-Qin Liu (Toxicology, 2026)

Temporal dynamics and environmental controls of carbon and nitrogen stabilization in soil aggregates during afforestation on the Loess Plateau - Xin Qin; Weibo Kong; Zhao Peng; Liangchen Guo; Xinyi Feng; Nannan Ge; Liping Qiu; Mingan Shao; Guohua Rong; Xiaorong Wei (Soil Biology and Biochemistry, 2026)

Modulation of residual current and water flux by the construction of Yangshan deep-water harbour, Shanghai, China - Wei Mao; Wenyun Guo; Jianzhong Ge; Pingxing Ding (Regional Studies in Marine Science, 2026)

Retraction notice to “Application of Brachypodium genotypes to the analysis of type II resistance to Fusarium head blight (FHB)” [Plant Sci. 272 (2018) 255–266] - Peisen Su; Xiuxiu Guo; Yanhui Fan; Liang Wang; Guanghui Yu; Wenyang Ge; Lanfei Zhao; Xin Ma; Jiajie Wu; Anfei Li; Hongwei Wang; Lingrang Kong (Plant Science, 2026)

Highly oxidized germacrane-type sesquiterpenoid dimers from Elephantopus tomentosus L.: Structural characterization, DFT calculation and anti-hepatoma potential - Zi-Hao Ge; Si-Hui Mi; Wen-Long Kou; Guo-Dong Yao; Bin Lin; Jian Wang; Ming Bai; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2026)

Investigation on the FCNN-based propeller optimization constrained by cavitation performance - Junyu Ge; Haipeng Guo; Guangnian Li; Lin Du (Ocean Engineering, 2026)

Anti-attacks prescribed performance formation tracking control for USV system via adaptive switching mechanism - Zexi Li; Yakun Zhu; Chao Yuan; Yaosen Li; Ge Guo (Ocean Engineering, 2026)

Comparison investigation of hydrodynamic responses for SUBOFF travelling on and near free surface - Dahui Ge; Yucai Chen; Guo Wang; Junbo Ge; Yunxiang You; Aichun Feng (Ocean Engineering, 2026)

Dissection of the genetic basis of 1392 rice landraces and 770 hybrid combinations reveals great potential of rice landraces in hybrid rice improvement - Yinting Wang; Zixuan Li; Bi Wu; Xueqiang Wang; Wenyan Yang; Danjing Lou; Jinyue Ge; Ziran Liu; Wenlong Guo; Neng Zhao; Jun Yang; Weiya Fan; et al. (Molecular Plant, 2026)

Magnetic Fe-Mn spinel particle electrodes from red mud-shield slag wastes for 3D electrocatalytic dye degradation - Xinxin Li; Fumin Ren; Junshi Liu; Sibo Jia; Xiaoyu Ge; Houliang Guo (Journal of Environmental Management, 2026)

Compact-pol to quad-pol SAR reconstruction via a joint mathematical-physical-constrained multimodal correlation-preserving latent diffusion framework - Zihuan Guo; Hong Zhang; Ji Ge; Xiao-Ming Li; Peifeng Ma; Haoxuan Duan; Lu Xu; Chao Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Quantitative analysis of corn adulteration in sweet potato starch using a CNN-LSTM hybrid model - Hongyi Ge; Xuye Yuan; Heng Wang; Keke Jia; Yuying Jiang; Chunyan Guo; Wenhui Zhou; Yuan Zhang; Wenyue Cao; Yitong Zhou; Tianzhi Zhang; Xinxin Liu (Food Chemistry, 2026)

Engineered core-shell immunomodulators for dual immune activation and sustained anti-MRSA protection via macrophage metabolic reprogramming - Shuhe Zhang; Chaonan Wang; Qingru Chang; Junjie Guo; Jiaqing Wang; Zheng Jia; Ning Liu; Yaosheng Xiong; Qijun Hu; Junwei Ge; Fang Wang; Mingchun Gao (Chemical Engineering Journal, 2026)

Innovative NFC-based flexible sensing system for wireless and battery-free detection of H2S: A game-changer in real-time fresh food freshness evaluation - Ning Shi; Yan Tong; Boyang Xu; Xiaohu Ge; Yueqiang Cao; Yu Han; Yunda Chen; Anxin Luo; Xiaochan Wang; Gang Liu; Xiande Zhao; Guo Zhao (Chemical Engineering Journal, 2026)

Echinacoside Improves Memory Function and Bone Mineral Density in the Aged SAMP8 Mouse Model - Rong Zhou; Ge Tian; Jing Yu; Rui Wang; Ning Peng; Xingzhi Guo; Rui Li (Molecular Neurobiology, 2026)

An Integrated MEEMD-FELM Hybrid Model for Accurate Solar Irradiance Prediction for the techno-economic design of a renewable hydrogen generation - Min Li; Yinping Jiang; Ge Cao; Tao Xu; Ruiqiang Guo (Environment, Development and Sustainability, 2025)

A Boronic Acid-Based Ratiometric Fluorescent Probe for Selective Detection of Hydrogen Peroxide - Ruilin Ge; Ruijia Gan; Rongrong Guo; Xiaowei Xu; Chaobing Gao (Journal of Fluorescence, 2025)

ICFMNet: an automated segmentation and 3D phenotypic analysis pipeline for plant, spike, and flag leaf type of wheat - Pengliang Xiao; Sheng Wu; Shiqing Gao; Weiliang Wen; Chuanyu Wang; Xianju Lu; Xiaofen Ge; Wenrui Li; Linsheng Huang; Dong Liang; Xinyu Guo (Computers and Electronics in Agriculture, 2025)

Differential evolution with bi-strategy co-deployment framework and diversity improvement - Liangliang Sun; Zhenghao Song; Ge Guo; Yucheng Zhang; Natalja Matsveichuk; Yuri Sotskov (Swarm and Evolutionary Computation, 2025)

Corrigendum to “Ecosystem sustainability of rice and aquatic animal co-culture systems and a synthesis of its underlying mechanisms” [Science of the Total Environment, 880 (2023) 163314] - Lei Ge; Yu Sun; Yujie Li; Luyao Wang; Guanqing Guo; Lili Song; Cui Wang; Guogan Wu; Shuangxi Li; Peng Li (Science of The Total Environment, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Multiomic insights into the regulatory mechanism of anammox consortia: Interspecies cooperation, degradation and self-adaptation to plasticizer stress - Ge-Ge Wu; Jing-Ao Jin; Na-Na Han; Wen-Li Guo; Nian-Si Fan; Ren-Cun Jin (Journal of Hazardous Materials, 2025)

Thermodynamic, economic, and environmental analysis of a supercritical water partial oxidation autothermal cogeneration system of coal - Guowei Xing; Yifeng Li; Changyifan Ren; Zhiwei Ge; Liejin Guo (Journal of Cleaner Production, 2025)

Pelletization and steam reactivation of steel slag-derived calcium-based sorbent for CO2 capture - Nai Rong; Yuhan Wang; Zhihang Guo; Kaiwei Liu; Xiuliang Shi; Long Han; Lichao Ge; Geng Wang; Chao Hu; Xiaokang Wan (Journal of Environmental Chemical Engineering, 2025)

Porous amorphous manganese oxide micro-nanostructures boosted electron transfer between periodate and organic contaminants: The significance of surface reactive oxygen species - Shuyang Deng; Rongyi Ge; Fan Yang; Xiao Guo; Hongrui Xiao; Kangle Lv; Yaobin Ding (Journal of Environmental Chemical Engineering, 2025)

Green reagent-driven resource recovery: Separation of hematite and iron-bearing silicate minerals from complex low-grade iron ore - Wencheng Ge; Zixuan Guo; Jie Liu; Yimin Zhu; Shuai Yuan; Peng Gao; Xiaolong Zhang; Yuexin Han (Journal of Environmental Chemical Engineering, 2025)

UAVPairs: A benchmark for match pair retrieval of large-scale UAV images - Junhuan Liu; San Jiang; Wei Ge; Wei Huang; Bingxuan Guo; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Synchronized removal of non-rare earth ions (Al3+, Fe3+, Th4+, U6+, and F−) from rare earth leach solutions using lanthanum‑cerium oxides for pH adjustment - Di Wu; Xinjin Xiao; An Guo; Qiaofa Lan; Huijuan Wang; Liusheng Ge; Xiaoqiang Wen; Lingdong Sun; Chunsheng Liao (Hydrometallurgy, 2025)

Machine learning intelligently selects feature values to construct a sensor array based on tri-functional Mn-doped covalent organic polymer nanozymes for identifying flavonoid compounds - Guo-Qi Zhang; Wen-Cai Jiang; Xiao-Mei Li; Ren-Jie Li; Yi Feng; Ri-Ge Li Nai; Hui-Lin Cheng; Zhi-Bo Hou; Xiao-Jun Luo; Yan Zhao (Food Chemistry, 2025)

A comprehensive story of pea peptides and pea polyphenols: Research status, existing problems, and development trends - Xinyu Sun; Guocong Ma; Dan Hai; Ge Bai; Qi Guo; Tianlin Wang; Xianqing Huang; Lianjun Song (Food Chemistry, 2025)

Structure characterization and anti-infection activity of a homogeneous heteropolysaccharide COP-60a from Cornus officinalis leaf - Yi Xiong; Wenchen Yu; Ge Wang; Deyong Zeng; Xiaoyi Li; Jingxuan Jia; Jianlong Wang; Yue Zhang; Jianguo Guo; Yingyu Zhou; Weihong Lu (Carbohydrate Polymers, 2025)

Genome-wide survey and expression analysis of JAZ genes in watermelon (Citrullus lanatus) - Yan-Ge Li; Jing Zhang; Xiu-Xiu Cai; Le-Ping Fan; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Molecular Biology Reports, 2025)

Serum Copper and Heart Failure: A Cross-Sectional and In Silico Toxicological Study - Xiangyu Guo; Ran Wei; Ge Yang; Maoxun Huang (Cardiovascular Toxicology, 2025)

DOM from eco-friendly fertilizers increases soil potential pathogen risk and shapes specific microbial populations under sprinkler and drip irrigation - Jinluo Fan; Rui Song; Heng Luo; Haijun Wu; Dongming Wu; Jun Wang; Yanqun Guo; Shuailing Hou; Mingguang Luo; Guoliang Ren; Hui Deng; Jiwei Luo; et al. (Applied Soil Ecology, 2025)

Microalgae-based removal of pharmaceutically active compounds (PhACs) from wastewater: Mechanisms and applications - Ye Lin; Xue Pu; Jingyuan Xia; Xiyang Lu; Heyang Hu; Jiawei Bai; Fuyuan Guo; Shijian Ge; Shuang Qiu (Algal Research, 2025)

Research on Acoustic-Electrical Integrated Technology in Geothermal Resource Exploration, Development and Monitoring - Feng Chu; Rui Xu; Rong-hua Zhang; Yi-guo Xue; Deng-rui Wu; Lin-zhi Lang; Shu-ge Liu; Jing-kai Qu (Applied Geophysics, 2025)

Pollution profiles and human health risk assessment of BPA analogues in seafood from a Chinese coastal city - Yuehong Shen; Haonan Chen; Mengyuan Liang; Liguo Guo; Jie Gu; Lili Shi; Feng Ge; Guixiang Ji (Marine Pollution Bulletin, 2025)

A novel mycotoxin-degrading enzyme complex can biodegrade AFB1, DON, and ZEN co-contamination in both in vitro and in vivo experiments - Yan-Qi Ning; Zhe Peng; Yu Zhang; Alainaa Refaie; Jing-Hui Ge; Li-Jia Guo; Wen-Jie Yang; Lv-Hui Sun (Toxicon, 2025)

Bifidobacterium animalis subsp. Lactis A6 alleviates comorbid constipation and depression by rebalancing tryptophan metabolism - Jian Wang; Yimei Ren; Juan Chen; Shanbin Chen; Xiaoxia Li; Jianwen Chen; Xifan Wang; Lijun Li; Liang Zhao; Yixuan Li; Qi Zhang; Wei Xiong; et al. (Science Bulletin, 2025)

Extreme palaeofloods since the LGM in the Dadu River Grand Canyon, eastern Tibetan Plateau - Peini Mao; Yongqiang Guo; Yonggang Ge; Tao Liu (Quaternary Science Reviews, 2025)

A Rayleigh distribution-based fatigue damage prediction model for offshore structures under bimodal responses - Haiyang Ge; Xiaozhou Guo; Xin Li; Qiangqiang Wei; Bo Wu (Ocean Engineering, 2025)

Multi-target tracking and surrounding control for multi-USV system under unknown disturbances based on distributed NMPC - Yakun Zhu; Zhiming Li; Yaosen Li; Chao Yuan; Ge Guo (Ocean Engineering, 2025)

Flash roasting for phase transformation of α-spodumene coupled with sulfuric acid pressure leaching to enhance lithium extraction - Dongqi Song; Wei Chen; Qingkang Yan; Yu Liu; Ge Kuang; Hui Guo; Guosheng Li; Yijun Cao (Minerals Engineering, 2025)

An improved model based on lattice Boltzmann method for the simulation of water and salt migration in unsaturated soils - Chao Shen; Guo Tian; Shen Wei; Dongwei Zhang; Ge Song (Journal of Hydrology, 2025)

Schwertmannite maintains effective stabilization of arsenic in flooded paddy soil: Insights from a two-season rice experiment and underlying mechanisms - Ru Wang; Yang Song; Yinglin Guo; Nan Ge; Xiaomeng Wang; Lixiang Zhou; Guanyu Zheng (Journal of Hazardous Materials, 2025)

The role of aging biomarkers and reproductive hormones in the association between microcystin-LR exposure and semen quality - Kangfeng Ge; Jian Hou; Wenqian Huo; Xiao Liang; Jun Yang; Haibin Guo; Xingde Du; Ruiyang Meng; Feiyang Guo; Xin Wang; Yingfei Yang; Xiaodong Liu; et al. (Journal of Hazardous Materials, 2025)

Self-Supported ZIF-Based nanozymes with high catalytic activity and enhanced stability for CO2 capture - Yong Xiang; Daoyong Yu; Rujing Guo; Wentao Wu; Jiuzhou Zhao; Shuai Zhang; Baosheng Ge; Zijun Xiao (Fuel, 2025)

Spatiotemporal correlations of water network elements in Yilong Lake Basin and the drivers—an analysis based on the PLS-DSDM model - Yunan Huang; Xuesen Zhang; Yunchun Chen; Zuokai Xie; Xiaofei Guo; Jiansheng Zhang; Lijun Liao; Xingyan Ge; Xingpeng Liu; Weijun Zeng (Environmental Research, 2025)

Advanced PDMS@Li/ZnAl-LDH microspheres for lithium recovery from Qarhan Salt Lake brine with high Mg/Li disparity - Sehria Zia; Muhammad Kashif; Haojie Ge; Kaiyu Zhao; Yafei Guo; Tianlong Deng (Desalination, 2025)

Dual-stage reverse-dialysis-engineered cartilage-biomimetic hydrogels: Highly resilient anti-swelling double-layer architectures - Zheng-Feng Zhang; Mei-Yan Ling; Xiao-Rui Ge; Jia-Ying Chen; Bei Zhang; Xiao-Hui Yao; Peng Song; Wei-Guo Zhao; Dong-Yang Zhang; Jun Wang (Chemical Engineering Journal, 2025)

General strategy for efficient persistent RTP polymer over 3 s: luminophore with a moderate θn-π angle - Danman Guo; Tong Zou; Yiling Miao; Jinzheng Chen; Zhu Chen; Xiangyu Ge; Faxu Lin; Yi Zhang; Zhenguo Chi; Zhiyong Yang; Huahua Huang (Chemical Engineering Journal, 2025)

Gold nanoclusters as multifunctional nanoantibiotics: synthesis, mechanisms and applications in combating bacterial infections - Baiyang Liu; Zheming Yang; Jinwen Zhou; Bingbing Chen; Wenjia Li; Jing Hou; Xinmiao Wang; Shipeng Ning; Ge Xu; Xinhui Zeng; Qing Li; Zengchao Guo; et al. (Chemical Engineering Journal, 2025)

Influence of overlooked environmental factors on analytical accuracy in hygrothermal response of building envelopes based on the coupled heat and moisture transfer theory - Tao Gao; Ye Guo; Weilan Wu; Jian Ge; Yifan Fan; Jiang Lu; Yucong Xue (Building and Environment, 2025)

Exploring nonlinear and interaction effects of macro- and micro-environmental factors on age-friendliness of streets through explainable machine learning - Yafei Guo; Yipeng Ge; Yueshan Ma; Qizheng Gan; Shubo Chen; Yang Liu; Yalong Mao (Building and Environment, 2025)

Biochar-induced strong microbial carbon limitation prompts organic carbon sequestration and plant growth in antibiotic-contaminated soil - Linlin Qiu; Tim J. Daniell; Muhammad Nafees; Yihao Chen; Shuyu Zhou; Weihong Wu; Jia Du; Qingwei Zhou; Meiqing Jin; Weiying Ji; Jiaying Ge; Hongyan Guo (Plant and Soil, 2025)

Csde1 Mediates Neurogenesis via Post-transcriptional Regulation of the Cell Cycle - Xiangbin Jia; Wenqi Xie; Bing Du; Mei He; Jia Chen; Meilin Chen; Ge Zhang; Ke Wang; Wanjing Xu; Yuxin Liao; Senwei Tan; Yongqing Lyu; et al. (Neuroscience Bulletin, 2025)

Variations in water vapour and temperature in the upper atmosphere - Chaman Gul; Shichang Kang; Yuanjian Yang; Xinlei Ge; Dong Guo; Yueyue Yu (Advances in Space Research, 2025)

Unmanned Aerial Vehicle (UAV) Aeromagnetic System Based on Fluxgate Sensor and Its Applications - Nan Zhang; Li-zhong Xu; Tian-hao An; Jin-ge Zhang; Hua Guo (Applied Geophysics, 2025)

Depth matters: The impact of vegetation clipping on phosphorus fractions across peatland depth profiles - Yuchen Suo; Xin Guo; Leming Ge; Chenhao Cao; Meng Wang (Soil and Tillage Research, 2025)

Valorization of dredged sediment through Al³⁺-mediated C-A-S-H gel networks: Bridging mechanisms for enhanced structural bonding in non-autoclaved brick production - Shengya Zhou; Hongzhi Zhang; Jingjing Lv; Ke Sun; Kaixin Guo; Fangyu Chen; Yuanzhen Liu; Zhi Ge (Journal of Environmental Chemical Engineering, 2025)

Gaseous ozone assisted Maillard reaction of chickpea protein isolate- arabinose: Improving structural and functional properties and enhancing emulsion stability - Xiaopeng Wei; Ziyan Zhou; Xiaoyuan Wang; Megan Povey; Guo Liu; Shanshan Zhang; Ping Geng; Lihua Zhang; Zhenzhen Ge (Innovative Food Science & Emerging Technologies, 2025)

Nondestructive detection of wheat germination status based on terahertz imaging technology and the MobileNetV3-GS method - Hongyi Ge; Chunyan Guo; Yuying Jiang; Yuan Zhang; Wenhui Zhou; Heng Wang; Shun Wang (Food Bioscience, 2025)

PM2.5 promotes platelet activation and thrombosis via ROS/MAPKs pathway-mediated mitochondrial dysfunction - Yuquan Xie; Dongxia Fan; Biao Wu; Jianshu Guo; Ge Wang; Lu Yu; Chihang Zhang; Jinzhuo Zhao; Si Zhang (Environmental Research, 2025)

Localised evaporative emission inventory of gasoline vehicle volatile organic compounds (VOCs) in China: Insights into regional variations and driving behaviours - Chunxiao Hao; Dailin Yin; Junfang Wang; Hang Yin; Xiao Guo; Jia Ke; Qingyan Liu; Yunshan Ge; Guangyu Dou (Environmental Pollution, 2025)

Fracture evolution and anchoring mechanisms in discontinuous rock masses with irregular joints: Discrete element study using a novel damage constitutive model - Yin-Ge Zhu; Yue Wu; Cheng-Hao Han; Wei-Guo Qiao; Feng Jiang; Ji-Xian Dong; Shuai Zhang; Yan-Zhi Li (Computers and Geotechnics, 2025)

Red blood cell-mimetic hollow covalent organic framework with oxygen-replenishing and cavitation-amplified for enhanced sonodynamic therapy of periodontitis - Yang Zhou; Qiyuan Pan; Ruolin Wang; Yan Ge; Xiao Zhang; Yifan Guo; Rongyin Sun; Xianglong Liu; Sainan Liu; Min Liu; Jun Lin (Chemical Engineering Journal, 2025)

Stainless steel catalyzed pyrolysis of waste oil: Biofuel production, catalyst regeneration and environmental assessment - Guo-qiang Zhu; Huo-yun Xu; Jia-yu Zhang; Ge-liang Xie; Zhen Fang; Lujiang Xu (Chemical Engineering Journal, 2025)

Selective expansion of TCF7-expressing tumor-reactive T cell subpopulations during ovarian tumor-infiltrating T cell production ex vivo - Dingfeng Liu; Ting Zhang; Qinli Sun; Dongli Cai; Yanan Lou; Genyu Wang; Bowen Xie; Yicheng Zhu; Chong Wang; Zhouping Lu; Chenfei Liu; Yuan Li; et al. (Science China Life Sciences, 2025)

Health risk assessment of heavy metal(loid)s in a soil-rice system in the selenium-enriched area based on Monte Carlo simulation and bioaccessibility - Qingsong Ge; Ge Chen; Wei Guo; Jiyang Zhao; Yuxue Yao; Lei Yang; Tao Jiang; Jiawen Chen; Liugen Zheng (Environmental Geochemistry and Health, 2025)

Antibiotic Susceptibility Evaluation in Bacterial Infections from Orthopedic Inpatients with Leg Trauma - Juanjuan Zhang; Fangfang Jiao; Yonghan Ge; Bei Cheng; Jingjing Guo (Current Microbiology, 2025)

Sex-Associated Indels and Candidate Gene Identification in Fujian Oyster (Magallana angulata) - Yi Han; Yue Ning; Ling Li; Qijuan Wan; Shuqiong Li; Ying Yao; Chaonan Tang; Qisheng Wu; Xiang Guo; Jianfei Qi; Yizhou Ke; Hui Ge; et al. (Fishes, 2025)
Sex determination is a fundamental biological process governing animal reproduction. Although substantial progress has been made in elucidating its genetic basis, the genetic architecture underlying complex sex determination systems remains poorly understood. In this study, we identify sex-associated insertion–deletion (indel) variants, screen candidate genes, and compare sex-associated variation across populations with different genetic backgrounds in the Fujian oyster (Magallana angulata). Based on whole-genome resequencing data of a culture strain (designated FL), a total of 299,774 high-quality indels were identified. By integrating genome-wide association analysis (GWAS), fixation index (FST) analysis, and sex-biased genotype frequency comparisons, 77 overlapping sex-associated indels were identified, predominantly clustered within a 1.8 Mb (8.3–10.1 Mb) region on chromosome 9. Principal component analysis (PCA) based on the sex-associated markers and their subsets consistently separated male and female individuals in the FL strain. For two representative sex-associated indels, PCR-based genotyping methods were developed and validated. Functional annotation identified putative candidate genes for sex determination, including PKD1L1, 5-HTRL, SCP, and CCKRa. Comparative analysis of variants within PKD1L1 across wild, farmed, and selectively bred populations revealed a progressive enrichment of male-linked alleles in domesticated and selectively bred groups, particularly in male individuals. This study provides direct evidence that sex in the Fujian oyster is genetically determined and reveals that domestication and artificial selection may drive the emergence of major sex-determining loci, offering important insights into the genetic basis of sex determination in the Fujian oyster, and establishing a theoretical and practical foundation for molecular marker-assisted breeding of monosex lines for this species.

Low VTG1 levels trigger failed development of yellow follicles in ZZ female Chinese soft-shelled turtles - Jiequn Tang; An Huang; Jinni Wang; Yanyan Zhang; Wei Sun; Ling Xiao; Chutian Ge; Yin Guo (Aquaculture, 2025)

Dual-functional berberine-magnolol co-assembled nanoparticles inhibit Fusarium graminearum growth and mycotoxin production - Chenguo Li; Wei He; Yao Cui; Shimin Wu; Qing'ao Song; Ying Li; Jimin Guo; Xizhen Ge; Pingfang Tian (Pesticide Biochemistry and Physiology, 2025)

Scenario-dependent O3 driver identification and formation responses to VOCs/NO emission reduction pathways from integrated and sectoral sources in the Beijing-Tianjin-Hebei region, China - Hanyu Zhang; Wantong Guo; Jungang Wang; Hailiang Zhang; Maofa Ge; Shengrui Tong; Na Zhao; Zhiliang Yao (Journal of Hazardous Materials, 2025)

Study on supercritical water partial oxidation mechanism of sulfur-containing compounds by ReaxFF molecular dynamics - Ruochen Xiong; Guowei Xing; Yifeng Li; Zhiwei Ge; Liejin Guo (Journal of Hazardous Materials, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

Cascade regulatory mechanism of soil organic phosphorus mineralization mediated by quorum sensing signal molecules C4/C6/C8-HSL: Dynamic response based on phosphatase secretion of core species - Zhenchao Wu; Jie Kang; Liangyang Mao; Yueyi Liu; Shuo Li; Weige Yao; Ying Yang; Xiujun Tu; Yuhao Guo; Jinyu Du; Xuan Tang; Tong Yang; et al. (Chemical Engineering Journal, 2025)

Recent advances of fluorescent carbon dots for biological imaging and biosensing - Jing Bian; Zheng Wang; Jinnian Ge; Wanqing Gong; Kaisheng Nan; Zefang Liu; Jinlu Guo; Qinfu Zhao; Xiaofan Wang; Long Wan (Chemical Engineering Journal, 2025)

Degradation-induced changes in soil nutrient availability alter leaf and root traits and their coordination in a riparian wetland ecosystem - Junxiang Ding; Ming Dou; Wenjing Ge; Yingshu Cao; Xiaoying Guo; Yue Yin; Guangsheng Zhou; Deliang Kong; Mei Liu (Plant and Soil, 2025)

A practice guideline for therapeutic drug monitoring of mycophenolic acid for solid organ transplants - Shuang Liu; Hongsheng Chen; Zaiwei Song; Qi Guo; Xianglin Zhang; Bingyi Shi; Suodi Zhai; Lingli Zhang; Liyan Miao; Liyan Cui; Xiao Chen; Yalin Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2025)
Mycophenolic acid (MPA), the active moiety of both mycophenolate mofetil (MMF) and enteric-coated mycophenolate sodium (EC-MPS), serves as a primary immunosuppressant for maintaining solid organ transplants. Therapeutic drug monitoring (TDM) enhances treatment outcomes through tailored approaches. This study aimed to develop an evidence-based guideline for MPA TDM, facilitating its rational application in clinical settings. The guideline plan was drawn from the Institute of Medicine and World Health Organization (WHO) guidelines. Using the Delphi method, clinical questions and outcome indicators were generated. Systematic reviews, Grading of Recommendations Assessment, Development, and Evaluation (GRADE) evidence quality evaluations, expert opinions, and patient values guided evidence-based suggestions for the guideline. External reviews further refined the recommendations. The guideline for the TDM of MPA (IPGRP-2020CN099) consists of four sections and 16 recommendations encompassing target populations, monitoring strategies, dosage regimens, and influencing factors. High-risk populations, timing of TDM, area under the curve (AUC) versus trough concentration ( C 0 ), target concentration ranges, monitoring frequency, and analytical methods are addressed. Formulation-specific recommendations, initial dosage regimens, populations with unique considerations, pharmacokinetic-informed dosing, body weight factors, pharmacogenetics, and drug–drug interactions are covered. The evidence-based guideline offers a comprehensive recommendation for solid organ transplant recipients undergoing MPA therapy, promoting standardization of MPA TDM, and enhancing treatment efficacy and safety.

Production of phytoliths and phytoc in above- and belowground parts of common reed (Phragmites australis) in a riverine wetland of the Yellow River Delta, China - Li Zhang; Wenyi Sheng; Huijia Song; Lele Liu; Weihua Guo; Yuzhi Wang; Changzi Ge (Journal of Soils and Sediments, 2025)

Effects of the Coapplication of Silicon Fertilizer and Plant Ash on the Phytolith-occluded Carbon Sequestration Potential of Suaeda salsa - Zhang Li; Liu Lele; Zhang Jing; Guo Cuilian; Wang Fang; Ge Changzi (Estuaries and Coasts, 2025)

Urban parks as effective airborne cooling sources: planning suggestions based on an empirical study in Xi'an, China - Juejun Ge; Yupeng Wang; Dian Zhou; Ye Guo; Jicheng Wang; Zhaolin Gu (Urban Climate, 2025)

Predicting estrogen receptor agonists from plastic additives across various aquatic-related species using machine learning and AlphaFold2 - Wen-Jun Shi; Zhou Cao; Xiao-Bing Long; Chong-Rui Yao; Jin-Ge Zhang; Chang-Er Chen; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Modeling and optimization of destructive disassembly line balancing problem considering multiple failures - Bao Chao; Saixiyalatu Bao; Chuanfeng Qiu; Ge Qiu; Shujie Liang; Yingying Ke; Chaoyong Zhang; Hongfei Guo (Journal of Cleaner Production, 2025)

The impact of green and low-carbon technologies on carbon emission intensity: Evidence from patent data in China's counties - Zhaowen Wang; Ge Wu; Zhuang Miao; Anda Guo (Journal of Cleaner Production, 2025)

RSTeller: Scaling up visual language modeling in remote sensing with rich linguistic semantics from openly available data and large language models - Junyao Ge; Xu Zhang; Yang Zheng; Kaitai Guo; Jimin Liang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Prediction and controlling factors of high-fluoride groundwater in the Yellow River Basin based on machine learning model - Chunli Su; Weili Ge; Xianjun Xie; Zhihao Guo; Zhaohui Luo; Yiqun Gan; Ziyi Xiao; Yanhui Gao; Yanmei Yang (Groundwater for Sustainable Development, 2025)

Reversible regulation of room temperature phosphorescence and fluorescence in cucurbit[8]uril-mediated lanthanide MOFs - Qingyu Niu; Zerong Ge; Xiao Liu; Tian-meng Guo; Zongjie Hu; Weihan Li; Zhiqiang Li (Chemical Engineering Journal, 2025)

Facile construction of a pH-responsive vaterite based abamectin delivery platform and visual tracking of micro-particle transport in cucumber plants - Chunhua Niu; Ge Bai; Wanjun Gu; Linxiang Zhou; Shengxue Liu; Zhong Wei; Kai Chen; Xuhong Guo (Chemical Engineering Journal, 2025)

Deep plowing enhanced soil nematode communities and soil quality in dryland wheat fields on the Loess Plateau of China - Yuejing Qiao; Duo Gao; Yaqi Fan; Lijing Zhang; Qiuyan Yan; Laichun Guo; Junyong Ge; Tingmiao Huang (Agriculture, Ecosystems & Environment, 2025)

Two undescribed coumarins from Hansenia weberbaueriana - Yixiao Pan; Mengdan Liu; Yunjie Hu; Chenyi Yan; Dale Guo; Ge Kuang (Natural Product Research, 2025)

Development of dynamic topology optimization method for offshore jacket platforms - Yu-Tao Guo; Kang Ge; Chen Wang; Xiao-Long Zhao; Bin-Bin Li (Ocean Engineering, 2025)

Combined exposure of sleep deprivation and environmental particulate matter drives aging in multiple systems - Lu Yu; Chihang Zhang; Biao Wu; Jianshu Guo; Dongxia Fan; Ge Wang; Wenqing Zhang; Lin Lin; Xinlei Xu; Xihao Du; Xiao-yong Zhang; Yuquan Xie; et al. (Journal of Hazardous Materials, 2025)

Where does the wine go experiencing regulated deficit irrigation: the effect of RDI on volatile composition and the sensory properties of Cabernet Sauvignon wines - Guo Cheng; Jianing Li; Zhihao Deng; Ziyin Peng; Dong Li; Mengyuan Wei; Qian Ge; Caihong Li; Xiangyu Sun; Yulin Fang (Food Bioscience, 2025)

Cadmium exposure and health outcomes:An umbrella review of meta-analyses - Wenzhuo Xu; Sainan Wang; Wenhua Ruan; Mingyue Hao; Kele Jiang; Hao Guo; Anyi Geng; Mengting Man; Zheng Hu; Yun Liu; Guifang Jin; Haiyan Shi; et al. (Environmental Research, 2025)

Synergistic enhancement of ionic conductivity and mechanical strength of inorganic hydroxide exchange membranes via orientation engineering for water electrolysis - Qingjie Xi; Wei Wang; Ruixiang Guo; Chenyi Zhao; Xiaofen Liu; Xiaorui Jin; Yongan Yang; Kai-Ge Zhou; Meiling Wu (Chemical Engineering Journal, 2025)

Seismic performance of multiple hardening wall: macro-element modelling, parametric analysis, and design - Hongbo Jiang; Haotian Liu; Tong Guo; Guangzhong Fan; Jian Sun; Hongxing Qiu; Wenjie Ge; Yanqing Xu; Kongyang Chen; Chunchao Chen (Bulletin of Earthquake Engineering, 2025)

Correction: Identification of sex-linked markers and genes in Portuguese oyster (Magallana angulata) - Xiaoyan Zhou; Yue Ning; Jingyi Xie; Yi Han; Chaonan Tang; Caiyuan Su; Qijuan Wan; Qisheng Wu; Xiang Guo; Jianfei Qi; Yizhou Ke; Hui Ge; et al. (Frontiers in Marine Science, 2025)

Identification of sex-linked markers and genes in Portuguese oyster (Magallana angulata) - Xiaoyan Zhou; Yue Ning; Jingyi Xie; Yi Han; Chaonan Tang; Caiyuan Su; Qijuan Wan; Qisheng Wu; Xiang Guo; Jianfei Qi; Yizhou Ke; Hui Ge; et al. (Frontiers in Marine Science, 2025)
The Portuguese oyster ( Magallana angulata ) is a valuable aquaculture species with sexual dimorphism in growth and nutritional traits, making it a promising candidate for sex-controlled breeding. However, the genetic mechanisms underlying its sex determination remain poorly understood. This study represents the first population-level investigation to identify sex-linked genetic markers and candidate genes in M. angulata using genome-wide association studies (GWAS) and transcriptomic analysis. A total of 1,613 sex-associated SNPs were identified, primarily located on Chr. 9 (7.99 Mb–10.51Mb). SNP annotation revealed 57 genes around these sex-associated SNPs. Transcriptomic analysis identified 8,635 differentially expressed genes (DEGs) between male and female gonads, of which 12 overlapped with GWAS-identified genes. Among these, four genes ( 5-HTR , ADPKD1-a , SCP , and SLC28A3 ) exhibited strong sex-specific genetic differentiation, with 5-HTR showing the most pronounced association. Further population genetic analysis revealed higher genetic diversity and heterozygosity of 5-HTR in males. Six sex-associated haplotypes based on SNPs within 5-HTR were constructed and validated in an independent population, although with reduced significance, suggesting both continuity and variation in sex determination mechanisms across populations. These findings provide a critical foundation for understanding the genetic basis of sex determination and advancing sex-controlled breeding strategies in M. angulata.

Effects of Clitocybe squamulosa polysaccharides on the intestinal microenvironment and microbiome of cyclophosphamide-induced mice - Xueran Geng; Dongdong Guo; Guangliang Ge; Zehui Li; Shuting Hou; Tergun Bau; Sitong Yao; Lijing Xu; Yanfen Cheng; Ludan Hou; Junlong Meng; Mingchang Chang (Food Bioscience, 2025)

Multifunctional and structural magnetic nanobranches for high-efficiency biological detection - Wenxu Hu; Yongliang Dong; Tianxin Ge; Si-Yang Liu; Jianhe Guo; Liqiu Wang; Changqing Yi; Xing Han; Zong Dai (Chemical Engineering Journal, 2025)

pH/GSH-Driven inside-out nanoreactor initiating copper(I)-precursor chelation-promoted bioorthogonal therapy - Zhexiang Wang; Xinyi Li; Rui Lv; Ruochen Guo; Qinglei Shu; Tianjin Ge; Jun Yan; Zhihao Zhao; Guanghui Wang; Jian Liu (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Using quantitative evaluation model to assess the environmental benefits of metabolites in flax retting wastewater aerobic compost: The trade-offs of core species build the profiles of beneficial and harmful metabolites converted from lignocellulose - Ying Yang; Zhichao Yang; Jie Kang; Zhenchao Wu; Yangcun Sun; Xinbo Cao; Yuhao Guo; Xiujun Tu; Liangyang Mao; Shuo Li; Weige Yao; Jingping Ge; et al. (Chemical Engineering Journal, 2025)

Development of Brassica rapa-nigra monosomic alien addition lines: cytology, genetics, and morphology - Pengfei Li; Haiyan Wu; Shizhen Guo; Shunlin Wang; Mimi Zhang; Mengyang Liu; Wei Ma; Jianjun Zhao; Chen Tan; Cheng Cui; Xianhong Ge; Zaiyun Li (Theoretical and Applied Genetics, 2025)

Foxp3 inhibits PCV2 replication by reducing the ATPase activity of Rep - Ruijiao Jiang; Qiuyan Huang; Ruiting Shen; Yongning Zhang; Lei Zhou; Xinna Ge; Jun Han; Xin Guo; Hanchun Yang (Veterinary Microbiology, 2025)

Dual pathways of carbon neutrality in urban green spaces: assessment and regulatory strategies - Yuan Feng; Chenyu Fang; Xiaoli Jia; Peihao Song; Lin Zhou; Xin Xu; Kun Wang; Ruizhen He; Nan Guo; Shidong Ge (Sustainable Cities and Society, 2025)

Numerical investigation for shielding effects of two vessels in side-by-side configurations - Wei Wang; Dahui Ge; Guo Wang; Junbo Ge; Yihan Zhao; Aichun Feng (Ocean Engineering, 2025)

Height and terrain correction of UAV radioactive measurements based on DEM data - Zhipeng Deng; Liangquan Ge; Long Wen; Shengliang Guo; Chuanfeng Tang; Peng Yu; Zekuan Chen (Journal of Environmental Radioactivity, 2025)

Global patterns and determinants of year-to-year variations in surface urban heat islands - Xuanqing Guo; Huilin Du; Wenfeng Zhan; Yingying Ji; Chenguang Wang; Chunli Wang; Shuang Ge; Shasha Wang; Jiufeng Li; Sida Jiang; Dazhong Wang; Zihan Liu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Experimental and simulation study on the performance of corrugated plate enhanced solar chimney power plant combined with distillation system - Lu Zuo; Chenkai Xiao; Ziyang Yan; Zinan Guo; Long Huang; Yunting Ge (Desalination, 2025)

Enhanced production of lactic acid via glycerol selective oxidation over K-doped Pt/Sn-MFI catalysts - Haodong Xie; Haobin Wei; Zunlong Hu; Sida Ge; Yingshuo Guo; Pengfei Guo; Meng Wu; Xicheng Jia; Jiazhou Li; Tianliang Lu; Yuming Zhang; Wenhao Luo; et al. (Chemical Engineering Journal, 2025)

Effect of different iron species on disinfection byproducts formation in drinking water distribution systems - Jining Ge; Yuan Zhuang; Yili Wang; Jiaqi Guo; Baoyou Shi (Chemical Engineering Journal, 2025)

Stratified distribution of recycled components in the mantle of the South China Sea unveiled through magnesium isotopes - Zhen-Min Ge; Xiao-Long Huang; Fan Yang; Yang Yu; Guan-Hong Zhu; Le Zhang; Yu-Xin Cai; Guo-Hong Sun (Chemical Geology, 2025)

Late Miocene paleo-seismic events and tectonic responses of the western Qinling Mountains recorded in aeolian deposits - Long Chen; Zhengtang Guo; Xin Zhou; Junyi Ge; Chaoqin Chen; Zhilin He (Science China Earth Sciences, 2025)

Baicalin plays a protective role by regulating ferroptosis in multiple diseases - Shiyun Guo; Qi Zhang; Hangwei Ge; Honggang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

High C/N ratio induced by fertilizer application enhance paddy soil CO2 fixation capacity under anaerobic condition - Ne Wu; Qiong Liu; Xiaomeng Wei; Zhenke Zhu; Xiaobin Guo; Tida Ge; Jinshui Wu (Journal of Soils and Sediments, 2025)

Mesua ferrea L. extract inhibits cell invasion and tumor growth in breast cancer in vitro and in vivo - Zhi-Ying Liu; Ge Ge; Shuang-Shuang Ma; Xi-Ya Chen; Yue Cong; Shu-Yun Wang; Ya-Ping Guo (Tissue and Cell, 2025)

Emulation of Schrödinger dynamics with metamaterials - Zhao-Xian Chen; Wan-Ge Song; Guang-Chen He; Xiao-Meng Zhang; Ze-Guo Chen; Haitan Xu; Emil Prodan (Science Bulletin, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Corrigendum to “Application of Brachypodium genotypes to the analysis of type II resistance to Fusarium head blight (FHB)” [Plant Sci. 272 (2018) 255–266] - Peisen Su; Xiuxiu Guo; Yanhui Fan; Liang Wang; Guanghui Yu; Wenyang Ge; Lanfei Zhao; Xin Ma; Jiajie Wu; Anfei Li; Hongwei Wang; Lingrang Kong (Plant Science, 2025)

Hendersines J–M: Isoquinoline alkaloids from Corydalis hendersonii Hemsl. with cardiomyocyte protective and NO production inhibitory effects - Xiaochun Zhou; Zefeng Zhang; Changxin Liu; Shungang Jiao; Fuxing Ge; Qiuyuan Ding; Yiru Shen; Qiang Guo; Xingyun Chai (Phytochemistry, 2025)

Eco-hydrological recovery following large vegetation disturbances from a mega earthquake on the eastern Tibetan plateau - Jiehao Zhang; Yulong Zhang; Matthew P. Dannenberg; Qinfeng Guo; Jeff W. Atkins; Wenhong Li; Ge Sun (Journal of Hydrology, 2025)

Estimation and evaluation of usage, loss and ecological risk of neonicotinoid pesticides in a large catchment - Xian-Kun Ma; Qian-Qian Zhang; Feng-Jiao Peng; Liang-Li Dong; Jin-Ge Zhang; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Spatial-confined CuCo bimetallic nanoparticles in nitrogen-doped carbon flowers enable low-input/input-free electrocatalytic hydrogen production - Fenghua Ge; Mengjiao Guo; Xu Dong; Fengcai Lei; Junfeng Xie; Qikun Zhang; Zhihua Li; Qian Wang; Pin Hao (Journal of Environmental Chemical Engineering, 2025)

Sewage treatment effect of MPSRs under different influent NH4+-N concentrations and its mechanism of nitrogen removal - Ge Yu; Guo Shen; Liyuan Zhao; Wanying Liu; Wenbin Zhao; Fan Wang; Shengshu Ai; Dejun Bian; Donglei Zou (Journal of Environmental Chemical Engineering, 2025)

Study on potassium recovery of coal gasification process in supercritical water - Chenchen Zhou; Hui Jin; Zhiwei Ge; Liejin Guo (Journal of Environmental Chemical Engineering, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Aquatic photochemistry for different dissociation forms of cephalosporin antibiotics: Degradation kinetics, products and photo-modified toxicity - Linke Ge; Yadi Guo; Qing Xie; Yan Yang; Peng Zhang; Jiahong Wang; Yunqing Zhu (Environmental Pollution, 2025)

Realizing continuous recycling of wasted LCO based on extractants functioning as H+ diffusion pump - Liang Lou; Junkai Xiong; Xinghua Guan; Liankang Ye; Houqiang Shi; Qihui Guo; Lvye Yang; Xiang Ge (Chemical Engineering Journal, 2025)

Steam-assisted one-step fabrication of Ni-Ce biochar catalysts for enhanced biomass pyrolysis-steam reforming - Jiali Guo; Jit Loong Cyrus Foo; Liya Ge; Wei Ping Chan; Andrei Veksha; Guicai Liu; Zhifeng Hu; Shuai Guo; Grzegorz Lisak (Chemical Engineering Journal, 2025)

Temperature effects on SOA formation of n-dodecane reaction initiated by Cl atoms - Cici Fan; Weigang Wang; Ke Wang; Ting Lei; Wang Xiang; Chunyan Hou; Junling Li; Yucong Guo; Maofa Ge (Atmospheric Environment, 2025)

Development of potential intron polymorphic (PIP) markers in melon (Cucumis melo L.) - Rui Sun; Yan-Ge Li; Ding-Ding Zuo; Meng-Ling Zheng; Jing Zhang; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Rational design of a near-infrared fluorescent probe for rapid monitoring of carboxylesterase in live cells and drug-induced liver injury mice - Weitao Xing; Kaili Yang; Yonglong Zhu; Xinyi Li; Yan Zhang; Linxia Guo; Jing-Yuan Ge; Yang Bai; Zhongyan Chen (Analytica Chimica Acta, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

STC2 regulates the proliferation, migration and glycolysis of glioma cells through modulating ITGB2 - Zefeng Wei; Dengfeng Ge; Jie Bu; Xuenan Wang; Tao Zhong; Xiaoxiao Gongye; Bin Zhang; Feng Yan; Chunyan He; Runhan Guo; Jiayi Li; Zhenzhen Jin (Metabolic Brain Disease, 2025)

Tide-surge interaction and its impact on coastal inundation: a case study of super typhoon Meranti - Wenyun Guo; Fenglin Zhang; Jianzhong Ge; Hongsheng Zhang (Frontiers in Marine Science, 2025)
Typhoon-induced storm tides can cause severe coastal inundation hazards in low-lying lands. The extreme water levels can be significantly modified by the nonlinear tide-surge interactions. To explore the impact of these interactions on coastal inundation on Xiamen Bay and its adjacent low-lying coastal regions during Super Typhoon Meranti (1614), a series of numerical experiments utilizing a high-resolution FVCOM model were conducted. The results show that tide-surge interaction is extremely strong in Xiamen Bay, with relative intensity of 0.1 to astronomical tides and over 0.3 to the practical surges across most area of the bay. The nonlinear interaction tends to decrease the peak water levels across the bay but elevates peak surges in most parts of it. There are two peaks in the surges. The former peak occurs around mid-rising tide, and can mainly attribute to the nonlinear tide-surge interaction, while the latter mid-falling peak is resulted from the combined action of the strong wind and tide-surge interaction. The momentum balance analysis revealed that nonlinear transformations in local acceleration and advection terms are remarkable throughout the bay, and the nonlinear transformations in surface wind stress and bottom friction are significant in the shallow Jiulong River Estuary and the waters around Dadeng Island. During this storm, tide-surge interactions led to a significant reduction in inundation area, inundation depths, and inundation duration, by about 24%, 16%, and 10%, respectively. This study highlights the importance of considering tide-surge interactions in the assessment of coastal inundations risks.

LettuceP3D: A tool for analysing 3D phenotypes of individual lettuce plants - Xiaofen Ge; Sheng Wu; Weiliang Wen; Fei Shen; Pengliang Xiao; Xianju Lu; Haishen Liu; Minggang Zhang; Xinyu Guo (Biosystems Engineering, 2025)

Analysis of the effect of highway extra-long tunnel Accompanying vehicle lighting on driving behavior in horizontal curve − A driving simulation study - Hongcheng Ge; Cancan Song; Difei Jing; Wei Li; Ze Shi; Zhongyin Guo; Fangyan Zhang (Tunnelling and Underground Space Technology, 2025)

Effects of melatonin on the pharmacokinetics and amino acid metabolism profile of vigabatrin in rats - Qiang Zheng; Song-Lin Xu; Xin-Lin Guo; Chuan-Yu Wang; Meng-Die Ma; Jin-Fang Ge (Toxicology and Applied Pharmacology, 2025)

Antitussive drug dextromethorphan induces developmental impairment in zebrafish - Dong-Dong Ma; Wen-Jun Shi; Zhi-Jie Lu; Jin-Ge Zhang; Li-Xin Hu; Zheng Huang; Si-Ying Li; Xiao-Bing Long; Xin Liu; Chu-Shu Huang; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

The dynamics impact of phlorizin on gut microbiota and metabolites in an in vitro fermentation model - Dingzuo Ge; Luyao Zheng; Li Liu; Xin Chen; Jiawei Zhou; Han Ge; Liqiang Guo; Hua Hua; Ruirui Wang; Lei Zhang (Food Research International, 2025)

Mechanisms of phosphorus conversion in chicken manure and straw composting systems regulated by flax-retting wastewater and a combination of flax-retting wastewater and biochar - Shuo Li; Jie Kang; Zhenchao Wu; Yangcun Sun; Xiujun Tu; Yuhao Guo; Liangyang Mao; Ying Yang; Weige Yao; Jingping Ge (Chemical Engineering Journal, 2025)

circTP63-N suppresses the proliferation and metastasis of nasopharyngeal carcinoma via engaging with HSP90AB1 to modulate the YAP1/Hippo signaling pathway - Dan Wang; Sicheng Zuo; Junshang Ge; Hongke Qu; Jie Wu; Na Yi; Lei Shi; Yumin Wang; Yongzhen Mo; Chunmei Fan; Yi He; Pan Chen; et al. (Science China Life Sciences, 2025)

Delta Opioid Peptide [d-Ala2, d-Leu5]-Enkephalin Improves Physical and Cognitive Function and Increases Lifespan in Aged Female Mice - Lixia Huo; Hongquan Zhang; Chengwu Tang; Ge Cui; Tao Xue; Huihui Guo; Fandi Yao; Wei Zhang; Wenming Feng (Molecular Neurobiology, 2025)

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

Succession of bacterial community during microbially driven cyanobacterial organic matter degradation and its relationship to water quality in Taihu Lake, China - Jing Chen; Yongqiang Zhou; Yunlin Zhang; Quanzhong Guo; Shulan Zhang; Guanghuan Ge (Aquatic Ecology, 2025)

First report of alfalfa mosaic virus infecting Potentilla anserina L. in China - Miaomiao He; Zhengnan Li; Mengze Guo; Ge Yan; Fenghua Cheng; Jian Wang; Junqiao Li (Journal of Plant Pathology, 2025)

Pseudorabies virus inhibits the unfolded protein response for viral replication during the late stages of infection - Peng Gao; Jianle Ren; Qiongqiong Zhou; Peng Chen; Ailin Zhang; Yongning Zhang; Lei Zhou; Xinna Ge; Xin Guo; Jun Han; Hanchun Yang (Veterinary Microbiology, 2025)

C-C motif chemokine ligand 5 contributes to radon exposure-induced lung injury by recruiting dendritic cells to activate effector T helper cells - Liping Ma; Yilong Wang; Junwang Guo; Xuewen Zhang; Shuang Xing; Benbo Liu; Guo Chen; Xu Wang; Jiyao Hu; Ge Li; Gencheng Han; Maoxiang Zhu (Toxicology, 2025)

Q-learning assisted multi-objective evolutionary optimization for low-carbon scheduling of open-pit mine trucks - Yao Huang; Yinan Guo; Guoyu Chen; Hong Wei; Xiaoxiao Zhao; Shengxiang Yang; Shirong Ge (Swarm and Evolutionary Computation, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Mitigating nitrobenzene toxicity in anaerobic digestion using hollow carbon spheres: Enhanced methane production via direct interspecies electron transfer - Shunan Zhao; Keyang Li; Shaoqing Zhu; Qianli Guo; Ge Song; Kai Zhao; Qianming Gong; Ruiping Liu (Journal of Water Process Engineering, 2025)

Mechanistic insight into the decomposition of sulfone compounds in supercritical water - Libo Lu; Wenwen Wei; Zijian Fang; Shi Liu; Zhiwei Ge; Hui Jin; Yunan Chen; Liejin Guo (Journal of Environmental Management, 2025)

Dual-signal ratiometric electrochemical aptasensor for Zearalenone detection based on magnetic-assisted enrichment and hybridization chain reaction - Wentao Guo; Xuxin Zhang; Bin Deng; Hao Chen; Shun Wu; Yaohui Wu; Yonghong Wang; Ge Ning (Food Chemistry, 2025)

Synergistic effect of 2′-Fucosyllactose or galactooligosaccharide with Bifidobacterium bifidum DNG6 improves the intestinal barrier by modulating the SCFAs-TLR4/NF-κB cascade response in DSS-induced colitis in mice - Cui-Cui Sun; Yu-Qi Wang; Xin-Yu Wang; Guo-Fang Zhang; Hong-Fang Cao; Ge Song; Li-Bo Liu; Chun Li; Irina Valeryevna Boyarineva; Peng Du (Food Bioscience, 2025)

Corrigendum to ‘Mechanisms of imbalanced testicular homeostasis in infancy due to aberrant histone acetylation in undifferentiated spermatogonia under different concentrations of Di(2-ethylhexyl) phthalate (DEHP) exposure’ [Environ. Pollut. 347 (2024) 123742] - Yu Tian; Jiachen Guo; Lei Hua; Yinuo Jiang; Wei Ge; Xiaoyuan Zhang; Diya Cai; Dongliang Lu; Bin Wang; Wei Shen; Zhongyi Sun; Baoquan Han (Environmental Pollution, 2025)

Multiple-scale urban form renewal strategies for improving diffusion of building heat emission—A case in Xi’an, China - Juejun Ge; Yupeng Wang; Ye Guo; Jicheng Wang; Dian Zhou; Zhaolin Gu (Energy and Buildings, 2025)

A time-dependent interactive effect of nitrite and ammonia on inflammatory and immune response in the head kidney of silver carp (Hypophthalmichthys molitrix) - Yiwen Li; Honghui Guo; Hen Ge; Hang Sha; Yidi Wu; Guiwei Zou; Hongwei Liang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Photoelectrochemical water splitting improved by a cucurbit[7]uril-induced ternary heterojunction - Hong-Si Guo; Wenfeng Zhao; Qingmei Ge; Nan Jiang; Mao Liu; Hang Cong (Chemical Engineering Journal, 2025)

Anisotropic hydrogel sensors with muscle-like structures based on high-absorbent alginate fibers - Chen Hang; Zihan Guo; Kai Li; Jiuyong Yao; Hailing Shi; Ruihao Ge; Junxuan Liang; Fengyu Quan; Kewei Zhang; Xing Tian; Yanzhi Xia (Carbohydrate Polymers, 2025)

Deciphering bioprocess responses in organic phosphorus mineralization to different antibiotic stresses: Interaction mechanisms mediated by microbial succession and extracellular polymeric substances and regulatory patterns - Zhenchao Wu; Jie Kang; Liangyang Mao; Rui Sun; Xiujun Tu; Yuhao Guo; Jingping Ge (Bioresource Technology, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Mechanism of acclimation to chronic intermittent hypoxia in the gills of largemouth bass (Micropterus salmoides) - Qiao Liu; Hong Wang; Jiayu Ge; Lipeng Guo; Rabia Tahir; Jie Luo; Kuo He; Haoxiao Yan; Xin Zhang; Quanquan Cao; Zhang Cheng; Liulan Zhao; et al. (Fish Physiology and Biochemistry, 2025)

Response of nitrifiers to gradually increasing pH conditions in a membrane nitrification bioreactor: Microbial dynamics and alkali-resistant mechanism - Weican Shi; Zhaoming He; Jiahui Lu; Lingfeng Wang; Jianhua Guo; Shuang Qiu; Shijian Ge (Water Research, 2025)

Increased health risk from co-exposure to polycyclic aromatic hydrocarbons, phthalates, and per- and polyfluoroalkyl substances: Epidemiological insight from e-waste workers in Hong Kong - Junye Bian; Zhihui Guo; Gengze Liao; Feng Wang; Yanny Hoi Kuen Yu; Victoria H. Arrandale; Alan Hoi-shou Chan; Jiayin Huang; Yiming Ge; Xinjie Li; Xulong Chen; Bingjun Lu; et al. (Science of The Total Environment, 2025)

Earth's record-high greenness and its attributions in 2020 - Yulong Zhang; Jiafu Mao; Ge Sun; Qinfeng Guo; Jeffrey Atkins; Wenhong Li; Mingzhou Jin; Conghe Song; Jingfeng Xiao; Taehee Hwang; Tong Qiu; Lin Meng; et al. (Remote Sensing of Environment, 2025)

Tectono-sequence evolution of an extensional strike-slip composite basin, a case study of the Miaoxi'nan sub-sag in the eastern Bohai Bay Basin - Sheng Fu; Haifeng Yang; Lijun Song; Wei Zhou; Jiawang Ge; Yanqin Guo (Marine and Petroleum Geology, 2025)

Selective removal of ligand in bi-linker MIL-125 by pyrolysis method to improve the oxidative desulfurization - Zhi Huang; Junzhen Guo; Liang Chu; Haibin Yang; Liyan Wang; Zhaokun Wang; Zhaohui Liu; Mu Yang; Ge Wang (Fuel, 2025)

Determination of deoxynivalenol (DON) by a label-free electrochemical immunosensor based on Ni Fe PBA nanozymes - Suhui Xu; Tianhao Zhou; Jiamin Wang; Ge Guo; Zhiyan Chen; Huaxiang Li; Zhenquan Yang; Yajun Gao (Food Chemistry, 2025)

Alleviating self-discharge of printed interdigital supercapacitor based on conjugatedly configured pairs of pre-sodiated manganese oxide - Liankang Ye; Liang Lou; Qihui Guo; Junkai Xiong; Houqiang Shi; Lvye Yang; Yuanyu Wang; Xucheng Liu; Ge Xiang (Chemical Engineering Journal, 2025)

Editing of the soluble starch synthase gene MeSSIII-1 enhanced the amylose and resistant starch contents in cassava - Xiaohua Lu; Yajie Wang; Xinghou Zhen; Yannian Che; Hui Yu; Yujian Ge; Xiangwen Wang; Ruimei Li; Mengting Geng; Bin Zhou; Jiao Liu; Jianchun Guo; et al. (Carbohydrate Polymers, 2025)

Deferoxamine-induced neurotoxicity: Role of chaperone-mediated autophagy dysfunction in neuronal apoptosis in the hippocampus - Hong Zhang; Jian Guo; Jiayi Chu; Huanhuan Yu; Jialin Zhang; Siman Ma; Ge Jin; Yingshan Jiang; Jiao Xiao; Yutong Hou; Minyan Li; Shiliang Yin (Chemico-Biological Interactions, 2025)

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

Cadmium absorption and translocation in rice plants are influenced by lower air temperatures during grain filling stage - Xinzhen Zhang; Hang Xu; Jiangying Tang; Juan Yang; Zhiqiang Guo; Yang Xiao; Yulu Ge; Tian Liu; Qian Hu; Hejun Ao; Wanju Shi (Science of The Total Environment, 2024)

Improving global gross primary productivity estimation using two-leaf light use efficiency model by considering various environmental factors via machine learning - Zhilong Li; Ziti Jiao; Ge Gao; Jing Guo; Chenxia Wang; Sizhe Chen; Zheyou Tan; Wenyu Zhao (Science of The Total Environment, 2024)

Microbial degradation of DOC released by the mixed culture of Crassostrea gigas and Undaria pinnatifida - Tian Hu; Jie Su; Kuishuang Shao; Shanshan Dong; Yuyang Xie; Yawen Wei; Hongxia Ming; Tingting Shi; Ge Guo; Jingfeng Fan (Regional Studies in Marine Science, 2024)

Abscisic acid treatment positively regulates suberin polyaliphatics biosynthesis at wound sites in postharvest yam tubers - Xiaopeng Wei; Jing Xue; Ping Geng; Guo Liu; Ziyan Zhou; Chuanxue Yin; Yiwen Ji; Jiajun Dai; Guanhua Tang; Guangyuan Zhao; Wei Zong; Zhenzhen Ge; et al. (Postharvest Biology and Technology, 2024)

Associations between magnesium depletion score and depression among individuals aged 20 to 60 years - Zongao Cai; Jiachen She; Xiaozhu Liu; Ruihui Li; Shuang Guo; Zeyang Han; Jiyang Zhou; Hairong Zhang; Yudi Xu; Ge Zhang; Zhaokai Zhou; Xueli Guo; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Association between pyrrolizidine alkaloids exposure and risk of abnormal serum indices—Insights from a descriptive cross-sectional study in Yunnan Province - Xiaoxiang Sun; Zhengyuan Xie; Zheng He; Yisheng He; Zigao Zhao; Xuerong Yan; Xiangjing Song; Zijie Chen; Tao Wang; Quanrui Yue; Yiming Chen; Hanfeng Ye; et al. (Journal of Hazardous Materials, 2024)

High-affinity potassium transporter TaHAK1 implicates in cesium tolerance and phytoremediation - Jin Liu; Shuai-Bo Chen; Ze-Hua Fan; Haitao Liu; Yinglong Chen; Chandra Shekhar Seth; Evgenios Agathokleous; Tian-Cai Guo; Guo-Zhang Kang; Ge-Zi Li (Journal of Hazardous Materials, 2024)

A 2D/3D hierarchical hybrid enables energy-saving hydrogen production coupled with glycerol and urea electro-oxidation - Ziyu Zhou; Fenghua Ge; Ruirui Xu; Xu Dong; Mengjiao Guo; Guanwei Cui; Qian Wang; Pin Hao (Journal of Environmental Chemical Engineering, 2024)

Impact of pyrolysis temperature on heavy metals environmental risk in biochar derived from co-pyrolysis of Alternanthera philoxeroides and sludge - Tong Xiao; Pikun Zhou; Yun Liu; Kaike Zhang; Fangyu Liu; Ge Guo; Fuquan Ni; Yu Deng (Journal of Environmental Chemical Engineering, 2024)

Understanding the factors influencing high-temperature Daqu from different geographical regions - Zhendong Zhang; Yaolan Meng; Yurong Wang; Qiangchuan Hou; Haibo Zhang; Ming Zhang; Ge Hu; Yingying Zhou; Qifu Pan; Zhuang Guo (Food Bioscience, 2024)

Co-exposure to parabens, bisphenol A, and triclosan and the associations with dyslipidemia in Chinese older adults: The mediation effect of oxidative stress - Zhihui Guo; Xiaohu Ren; Peiyi Liu; Yilan Deng; Junye Bian; Yiming Ge; Benhong Xu; Xinxin Tang; Xinjie Li; Haiyan Huang; Jianjun Liu; Shaoyou Lu (Environmental Research, 2024)

Multiomics analysis reveal the impact of 17α-Ethinylestradiol on mortality in juvenile zebrafish - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying; Wen-Jun Shi (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Highly efficient solar seawater evaporation by aerogel with vertical channels and hierarchical pores structure based on high-absorbent alginate fibers - Zihan Guo; Chen Hang; Kai Li; Jiuyong Yao; Hailing Shi; Ruihao Ge; Xiaole Gong; Fengyu Quan; Lijie Zhang; Kewei Zhang; Liwen Tan; Xing Tian; et al. (Chemical Engineering Journal, 2024)

Engineered Halomonas for production of gamma-aminobutyric acid and 2-pyrrolidone - Ge Zhang; Weike Guo; Xueqing Yi; Zhongnan Zhang; Lizhan Zhang; Xu Liu; Fuqing Wu; Qiong Wu; Guo-Qiang Chen (Bioresource Technology, 2024)

Corynoline alleviates hepatic ischemia–reperfusion injury by inhibiting NLRP3 inflammasome activation through enhancing Nrf2/HO-1 signaling - Xin Ge; Yue Gu; Wendong Wang; Wenzhi Guo; Panliang Wang; Peng Du (Inflammation Research, 2024)

Individual traits modify environmental effects on interaction, connectivity, and productivity of macrophyte community - Hui Fu; Jingjing Guo; Xianjun He; Yaoqi Chen; Zhouhang Wu; Yili Ge; Guojun Cai (Hydrobiologia, 2024)

Assessment of genetic diversity of Camellia yuhsienensis based on leaf structure and inter simple sequence repeat (ISSR) markers - Yuling Zou; Xiaoning Ge; Chao Yan; Qiuping Zhong; Danyang Chen; Zexin Chen; Yaqi Yuan; Hongyan Guo; Youcheng Zhou; Jinfeng Wang; Linqing Cao (Genetic Resources and Crop Evolution, 2024)

High-precision Q modeling and Q migration technology and its applications in loess plateau regions - Wei Xu; Hong-Xing Liu; Hong-Gang Mi; Bing Zhang; Jun-Chao Guo; Yong Ge; Jun You (Applied Geophysics, 2024)

Identification of SNPs and Candidate Genes Associated with Growth Using GWAS and Transcriptome Analysis in Portuguese Oyster (Magallana angulata) - Jingyi Xie; Yue Ning; Yi Han; Caiyuan Su; Xiaoyan Zhou; Qisheng Wu; Xiang Guo; Jianfei Qi; Hui Ge; Yizou Ke; Mingyi Cai (Fishes, 2024)
Portuguese oyster (Magallana angulata) is one of the most important shellfish species worldwide. Although significant improvements in growth have been achieved through artificial selection breeding, the genetic basis underlying these traits remains unclear. Thus, this study aimed to (i) estimate variation and heritability for growth-related traits and (ii) identify SNPs and candidate genes associated with growth traits in Portuguese oyster. Five growth-related traits, including shell height (SH), shell length (SL), shell width (SW), whole weight (WW), and soft tissue weight (STW), were measured and analyzed in 114 one-year-old individuals from a cultivated population in Fujian Province, China. Through whole-genome sequencing and genotyping, we obtained 8,183,713 high-quality SNPs. Based on the genomic relationship matrix, heritability for the five traits was estimated, ranging from 0.071 to 0.695. Through genome-wide association analysis (GWAS), a total of nine SNPs were identified as significantly or suggestively associated with one of the growth-related traits, each explaining phenotypic variation ranging from 14.13% to 18.56%. Differentially expressed genes (DEGs) between individuals with extreme phenotypes were identified using comparative transcriptome analysis, ranging from 868 to 2274 for each trait. By combining GWAS and comparative transcriptome analysis, a total of seven candidate genes were identified, with biological functions related to growth inhibition, stress response, cell cycle regulation, and immune defense. The associations between the candidate genes and the growth-related traits were validated by using single-marker association analysis in other populations. Based on SNPs in these candidate genes, 16 haplotypes associated with growth-related traits were obtained. This study contributes to a deeper understanding of the genetic mechanisms of growth traits, and provides a theoretical basis and genetic markers for the breeding of fast-growing strains of the Portuguese oyster.

PRRSV infection inhibits CSFV C-strain replication via GSDMD-mediated pyroptosis - Ruijiao Jiang; Dengjin Chen; Yongning Zhang; Lei Zhou; Xinna Ge; Jun Han; Xin Guo; Hanchun Yang (Veterinary Microbiology, 2024)

Trace elements in PM2.5 from 2016 to 2021 in Shenzhen, China: Concentrations, temporal and spatial distribution, and related human inhalation exposure risk - Jialei Yang; Xin Chen; Xiaoheng Li; Jinfeng Fu; Yiming Ge; Zhihui Guo; Jiajia Ji; Shaoyou Lu (Science of The Total Environment, 2024)

Potassium persulfate enhances humification of chicken manure and straw composting: The perspective of rare and abundant microbial community structure and ecological interactions - Xiujun Tu; Bo Yin; Jie Kang; Zhenchao Wu; Yuhao Guo; Guoxu Ao; Yangcun Sun; Jingping Ge; Wenxiang Ping (Science of The Total Environment, 2024)

Long-term agricultural cultivation decreases microbial nutrient limitation in coastal saline soils - Guanjun Li; Zhi Ma; Liang Wei; Cuiyan Wu; Hao Chen; Bin Guo; Tida Ge; Jianming Wang; Jingwen Li (Science of The Total Environment, 2024)

E-commerce and air pollution: Evidence from China - Anda Guo; Ge Wu; Zhuang Miao; Xiaodong Chen (Journal of Cleaner Production, 2024)

Occurrence and migration patterns of microplastics in different tidal zones of tourist beaches: A case study in the Bohai Bay, North China - Yutao Zuo; Yawen Ge; Ruolin Wang; Wanqiang Xu; Changhong Liu; Zixiao Guo; Shuo Wang; Huiyuan Jia; Yuecong Li (Journal of Environmental Management, 2024)

Satellite remote sensing of vegetation phenology: Progress, challenges, and opportunities - Zheng Gong; Wenyan Ge; Jiaqi Guo; Jincheng Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Outburst flood events since the Last Glacial Maximum in the Hutiao Gorge of Jinsha River: Geomorphological evidence from eddy gravel bars - Xiaoling Huang; Yuzhu Zhang; Yongqiang Guo; Yonggang Ge; Peini Mao; Tao Liu; Sikai Wang (Geomorphology, 2024)

Transcriptome and metabolome analyses reveal the effects of formula and breast milk on the growth and development of human small intestinal organoids - Xianli Wang; Yiming Zhong; Chengdong Zheng; Chenxuan Huang; Haiyang Yao; Zimo Guo; Yilun Wu; Zening Wang; Zhengyang Wu; Ruihong Ge; Wei Cheng; Yuanyuan Yan; et al. (Food Research International, 2024)

Characterization of a short-term processing technology of black garlic with low 5-HMF content - Jun Liu; Jing Li; Shihao Ge; Xiaoyu Fu; Jiamin Zhu; Mengnan Wang; Yanrong Wang; Xiaoxiao Huang; Xinzheng Qin; Yixian Tu; Jun Xing; Chao Ma; et al. (Food Control, 2024)

Hypoxia induces reversible gill remodeling in largemouth bass (Micropterus salmoides) through integrins-mediated cell adhesion - Qiao Liu; Lipeng Guo; Hanwen Zhang; Jiayu Ge; Jie Luo; Kaige Song; Liulan Zhao; Song Yang (Fish & Shellfish Immunology, 2024)

Parabens, bisphenols, and triclosan in coral polyps, algae, and sediments from sanya, China: Occurrence, profiles, and environmental implications - Yiming Ge; Han Zhang; Jinfeng Fu; Zhihui Guo; Qiulu Dong; Jiaxin Yu; Zhiling Mo; Yuxi Lai; Jialei Yang; Shaoyou Lu (Environmental Pollution, 2024)

Aquatic plants combined with microbial fuel cells promote sulfamethoxazole and sul genes removal from aquaculture pond sediments via bioelectrochemistry - Qiao Liu; Nisha Zhang; Jiayu Ge; Leji Zhang; Lipeng Guo; Hanwen Zhang; Kaige Song; Jie Luo; Liulan Zhao; Song Yang (Environmental Pollution, 2024)

Quaternized poly(aryl imidazolium) containing bulky binaphthyl group as proton exchange membrane for high-temperature fuel cells - Tiegen Guo; Yixin Wang; Ge Chao; Xiaowei Zhou; Erqiang Yang; Zixin Lv; Jiajun Zheng; Kang Geng; Nanwen Li (Chemical Engineering Journal, 2024)

Spontaneous built-in electric field in W-W2C@C heterostructure: Accelerating Sn2- directed migration in Li-S batteries - Henan Jia; Pei Su; Taotao Guo; Mingwei Liu; Tianyu Huo; Shoucong Gao; Ge Jing; Dianbo Ruan; Mao-Cheng Liu (Chemical Engineering Journal, 2024)

Cascading effects of human activities and ENSO on the water quality of Poyang Lake in China - Yili Ge; Zhouhang Wu; Yaoqi Chen; Peiqin Guo; Aiping Wu; Huanyao Liu; Guixiang Yuan; Youzhi Li; Hui Fu; Erik Jeppesen (CATENA, 2024)

Impact of invasive apple snails on shallow water ecosystems under different nutrient conditions: results from a mesocosm study - Liang He; Shiyuan Guo; Guanghao Wang; Zixuan Ning; Huan Zhang; Gang Ge (Hydrobiologia, 2024)

Enhanced Cooling Efficiency of Urban Trees on Hotter Summer Days in 70 Cities of China - Limei Yang; Jun Ge; Yipeng Cao; Yu Liu; Xing Luo; Shiyao Wang; Weidong Guo (Advances in Atmospheric Sciences, 2024)
Increasing the urban tree cover percentage (TCP) is widely recognized as an efficient way to mitigate the urban heat island effect. The cooling efficiency of urban trees can be either enhanced or attenuated on hotter days, depending on the physiological response of urban trees to rising ambient temperature. However, the response of urban trees’ cooling efficiency to rising urban temperature remains poorly quantified for China’s cities. In this study, we quantify the response of urban trees’ cooling efficiency to rising urban temperature at noontime [∼1330 LT (local time), LT=UTC+8] in 17 summers (June, July, and August) from 2003–19 in 70 economically developed cities of China based on satellite observations. The results show that urban trees have stronger cooling efficiency with increasing temperature, suggesting additional cooling benefits provided by urban trees on hotter days. The enhanced cooling efficiency values of urban trees range from 0.002 to 0.055°C % −1 per 1°C increase in temperature across the selected cities, with larger values for the low-TCP-level cities. The response is also regulated by background temperature and precipitation, as the additional cooling benefit tends to be larger in warmer and wetter cities at the same TCP level. The positive response of urban trees’ cooling efficiency to rising urban temperature is explained mainly by the stronger evapotranspiration of urban trees on hotter days. These results have important implications for alleviating urban heat risk by utilizing urban trees, particularly considering that extreme hot days are becoming more frequent in cities under global warming.

Spatial and temporal distribution patterns of atmospheric PM2.5 and water-soluble inorganic ions in Shenzhen, China from 2016 to 2021 - Yuli Lin; Liuyi Yin; Xiaoheng Li; Yiming Ge; Zhihui Guo; Hongmei Qiu; Jiajia Ji; Shaoyou Lu (Chemosphere, 2024)

Microbial carbon and phosphorus metabolism regulated by C:N:P stoichiometry stimulates organic carbon accumulation in agricultural soils - Xiangxiang Wang; Hongrui Zhang; Dan Cao; Cuiyan Wu; Xianting Wang; Liang Wei; Bin Guo; Shuang Wang; Jina Ding; Hao Chen; Jianping Chen; Tida Ge; et al. (Soil and Tillage Research, 2024)

Nanoplastics composite norfloxacin induced changes in conformation and function of lysozyme and differential effects of co-exposure contamination - Hengyu Song; Pin Jiang; Houquan Tang; Zaifeng Wang; Xuan Ge; Xiangxiang Li; Falin He; Shuqi Guo; Guang Tian; Yuntao Qi; Shaoyang Hu; Rutao Liu (Science of The Total Environment, 2024)

Exploring the effects of environmentally relevant concentrations of tris(2-chloroethyl) phosphate on tadpole health: A comprehensive analysis of intestinal microbiota and hepatic transcriptome - Zi-Ying Wang; Wen-Qi Xie; Zi-Yong Xiang; Chi-Ying Zhang; Yi-Ge Xie; Roy You Chen Quah; Guo-Hua Ding (Science of The Total Environment, 2024)

Coarse particulate air pollution and mortality in a multidrug-resistant tuberculosis cohort - Huiying Feng; Erjia Ge; Nicholas Grubic; Xin Liu; Hui Zhang; Qiang Sun; Xiaolin Wei; Fangjing Zhou; Shanshan Huang; Yuhui Chen; Huixin Guo; Jianwei Li; et al. (Science of The Total Environment, 2024)

Research on operation characteristics of wind supercharged solar chimney dust haze removal street light - Lu Zuo; Zinan Guo; Tian Zhou; Chenkai Xiao; Long Huang; Yunting Ge (Process Safety and Environmental Protection, 2024)

Fast finite-time fault-tolerant trajectory tracking control of unmanned surface vehicles with multiple actuator constraints - Zhenyu Gao; Hengchao Ma; Ge Guo (Ocean Engineering, 2024)

Enhancing energy yield and reducing environmental impact through co-hydrothermal carbonization of undehydrated sewage sludge and fungus bran - Shuai Guo; Jiyou Mu; Long Gao; Liya Ge; Grzegorz Lisak (Journal of Environmental Chemical Engineering, 2024)

Integrated biomarker-based ecological risks assessment of tadpole responses to tris(2-chloroethyl) phosphate, tris(1-chloro-2-propyl) phosphate, and their combined environmental exposure - Wen-Qi Xie; Zi-Ying Wang; Yi-Ge Xie; Jia-Jun Hao; Xin-Dan Cao; Zi-Yong Xiang; Lu-Ping Lou; Guo-Hua Ding (Environmental Pollution, 2024)

Construction of MS-Ti3C2TX MXene continuous conductive structure for highly efficient fluoride removal in flow-electrode capacitive deionization - Zhenzong Lu; Dan Zhang; Hu Kang; Shichong Guo; Hongwei Ge; Yiheng Li; Zhining Wang; Yiming Li (Chemical Engineering Journal, 2024)

High-efficiency blue hybridized local and charge-transfer fluorescent material affording OLEDs with external quantum efficiency exceeding 14 % - Guiming Wu; Xiangyu Ge; Zhan Yang; Yanyan Liu; Zhu Chen; Yuyuan Wang; Gaoyu Li; Danman Guo; Huangjun Deng; Juan Zhao; Zhenguo Chi (Chemical Engineering Journal, 2024)

Comparison of kinetic energy conversion characteristics of two extreme precipitation episodes during persistent unusually heavy rainfall on 17–23 July 2021 in Henan, China - Ziyang Lai; Yushu Zhou; Xuyang Ge; Guo Deng; Lixia Zhang (Atmospheric Research, 2024)

Characterization and function of promoters of silicon transporter genes PeLsi1-1 and PeLsi1-2 from moso bamboo (Phyllostachys edulis) - Bohao Ge; Qianru Liu; Bowen Li; Xiaorui Bi; Kuo Dong; Jiaojiao Guo; Xin Geng; Yuzhen Chen; Cunfu Lu (Plant Cell Reports, 2024)

Pollution Characteristics and Risk Assessment of Heavy Metals in Dujiangyan Irrigation District, China - Yang Qiao; Hongling Yin; Shuyu Lin; Xiaoke Guo; Hui Zhang; Geng Ge; Yuxiang Lu (International Journal of Environmental Research, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Photo-induced protonation assisted nano primary battery for highly efficient immobilization of diverse heavy metal ions - Hongjian Ge; Chaowen Chen; Sijia Li; Xinyue Guo; Jing Zhang; Pengqi Yang; Huan Xu; Jia Zhang; Zhengyan Wu (Journal of Hazardous Materials, 2024)

In situ U–Pb dating of garnet, vesuvianite, and scheelite from the Nanyangtian tungsten deposit reveals an Early Cretaceous W mineralization event in Southeast Yunnan, China - Xiao-Yu Zhao; Ming-Guo Deng; Wen-Chang Li; Yan-Wen Tang; Ding-Cai Zhang; Sheng-Kang Han; Wen-Bo Song; Qing-Ge Zhang; Jing-Wei Xu (Gondwana Research, 2024)

Constructing Ni/ZnMOx composite metal oxide adsorbents with excellent desulfurization capacity and thermal stability for reactive adsorption desulfurization - Pu Dai; Mengya Guo; Hui Ge; Caimei Fan; Xuekuan Li; Xiuquan Liu; Junpeng Feng; Rui Li; Mingxing Tang (Fuel, 2024)

Experimental study on the damage and fracture mechanism of deep coal beds impacted by water jets at different temperatures - Shirong Cao; Xiaojun Wang; Zhaolong Ge; Zhiguo Guo; Liang Zhang (Fuel, 2024)

Per- and polyfluoroalkyl substances in Chinese commercially available red swamp crayfish (Procambarus clarkii): Implications for human exposure and health risk assessment - Junye Bian; Jiayi Xu; Zhihui Guo; Xinjie Li; Yiming Ge; Xinxin Tang; Bingjun Lu; Xulong Chen; Shaoyou Lu (Environmental Pollution, 2024)

Gasification characteristics and sulfur migration mechanism during supercritical water partial oxidation of 2-methylthiophene - Ruochen Xiong; Shi Liu; Jiayi Yu; Zhiwei Ge; Liejin Guo (Chemical Engineering Journal, 2024)

Iodine/soluble starch cryogel: An iodine-based antiseptic with instant water-solubility, improved stability, and potent bactericidal activity - Wei Sun; Zi-Xi Wang; Yuxin Guo; Chengcheng Li; Ge Gao; Fu-Gen Wu (Carbohydrate Polymers, 2024)

Genome-wide association study and selective sweep analysis uncover candidate genes controlling curd branch length in cauliflower - Yingxia Yang; Yutong Guo; Jing Wang; Wenjuan Cheng; Mingjie Lyu; Qian Wang; Jianjin Wu; Mingyan Hua; Weihua Zhang; Deling Sun; Xianhong Ge; Xingwei Yao; et al. (Theoretical and Applied Genetics, 2024)

Occurrences of nitrate-contaminated groundwater in the piedmont aquifers: hydrogeochemical characteristics and health risks - Haiyan Liu; Guanglu Zhang; Huaming Guo; Zhen Wang; Qin Ge (Environmental Geochemistry and Health, 2024)

The underestimated role of manganese in modulating the nutrient structure in a eutrophic seasonally-stratified reservoir - Zifu Xu; Lianghao Ge; Wenbin Zou; Bingchen Lv; Jun Yang; Zijian Chai; Xiaoyu Guo; Xunchi Zhu; Shuh-Ji Kao (Water Research, 2024)

Influence of community complexity and regulation by two-component system on community stability in aerobic composting in the presence of penicillin residues - Yuhao Guo; Ziliang Yin; Jie Kang; Xiujun Tu; Guoxu Ao; Jingping Ge; Wenxiang Ping (Journal of Cleaner Production, 2024)

Deep learning prediction of yields of fluid catalytic cracking via differential evolutionary dual-stage attention-based LSTM - Ge He; Lei Luo; Li Zhou; Yiyang Dai; Xu Ji; Chao Guo; Zhaopeng Lu (Fuel, 2024)

Tree species mixing effects on the radial growth of Pinus massoniana and Castanopsis hystrix: A comparison between even-aged and uneven-aged stands - Renjie Chen; Xiali Guo; Yuxian Ge; Qidong Li; Angang Ming; Huilin Min; Weijun Shen (Forest Ecology and Management, 2024)

The size-dependent effects of nanoplastics in mouse primary hepatocytes from cells to molecules - Yaoyue Wang; Xingchen Zhao; Houquan Tang; Zaifeng Wang; Xuan Ge; Shaoyang Hu; Xiangxiang Li; Shuqi Guo; Rutao Liu (Environmental Pollution, 2024)

A robust and low-cost blended-fiber-based evaporator with high efficiency for solar desalination - Qianqian Liu; Xiangjun Liu; Ge Chen; Pei Feng; Yucheng Xiong; Meng An; Cheng Shao; Xiongfei Zhu; Renzong Wang; Jianshi Sun; Jisheng Sun; Chunfang Guo; et al. (Desalination, 2024)

Response characteristics of plants and pollutant removal in subsurface flow constructed wetlands under resting operation - Jingying Zhang; Hongli Xie; Ge Bai; Dun Guo; Lei Yang; Jun Lan; Yongxiang Ren (Chemical Engineering Journal, 2024)

Mining for QTL controlling maize low-phosphorus response genes combined with deep resequencing of RIL parental genomes and in silico GWAS analysis - Bowen Luo; Peng Ma; Chong Zhang; Xiao Zhang; Jing Li; Junchi Ma; Zheng Han; Shuhao Zhang; Ting Yu; Guidi Zhang; Hongkai Zhang; Haiying Zhang; et al. (Theoretical and Applied Genetics, 2024)

Aβ-Aggregation-Generated Blue Autofluorescence Illuminates Senile Plaques as well as Complex Blood and Vascular Pathologies in Alzheimer’s Disease - Hualin Fu; Jilong Li; Chunlei Zhang; Peng Du; Guo Gao; Qiqi Ge; Xinping Guan; Daxiang Cui (Neuroscience Bulletin, 2024)

Ile-Pro-Pro attenuates sympathetic activity and hypertension - Jun-Liu Chen; Rui Ge; Xiu-Zhen Li; Yue Zhang; Wen-Yuan Hao; Na Li; Zhi-Qin Xu; Qi Chen; Yue-Hua Li; Guo-Qing Zhu; Xiao Tan (Journal of Physiology and Biochemistry, 2024)

Sedimentary biogeochemical gradients across the Sunda Shelf in the South China Sea and correlations with satellite observations - Yuanfang Zhang; Lin Deng; Zaiming Ge; Lin Guo; Qian P. Li (Frontiers in Marine Science, 2024)
The sediment biogeochemistry of phosphorus (P) and biogenic silica (BSi) in the southern South China Sea shelf (SSCS) is inadequate understood. Here, we examine the spatial distributions of P species and BSi in surface sediments across the Sunda Shelf and explore their relationships with satellite data of sea surface chlorophyll-a (Chla), suspended particulate matter (SPM), particulate organic carbon, particulate inorganic carbon, primary production (PP), and phytoplankton functional types. The total sediment P (TSP), in the range from 283.94 to 579.94 μg/g dry sediment, was dominated by inorganic P with higher levels in stations outside the Lupar and Saribas estuaries. The TSP was composed of seven different P species including Ca-IP and Ca-OP (58%), Detr-P (15%), Exch-P (11%), Fe-IP (10%), Ref-P (4%) and Ads-IP (2%) based on a sequential extraction method. The concentrations of various sediment P species were found significantly correlated with satellite climatological SPM, diatom biomass, and monthly climatological pico-PP revealing the importance of biological production for the sediment P storage, whereas the sediment BSi concentration showed no correlations with any of the above satellite products. An elevated R 2 value in the regression of BSi with the in-situ depth-integrated Chla points to the need of developing satellite algorithms with vertical profiles from space. Finally, we argue that future studies of the SSCS sediment biogeochemistry may be benefited from data of hyperspectral and geostationary satellites.

Pyrrolizidine alkaloids from Jacobaea vulgaris Gaertn and theoretical studies on intramolecular interactions - Aikebaier Jumai; Guo-An Zou; Ge-yu Liu; Haji Akber Aisa (Natural Product Research, 2024)

An engineered DNA aptamer-based PROTAC for precise therapy of p53-R175H hotspot mutant-driven cancer - Lingping Kong; Fanlu Meng; Ping Zhou; Ruixin Ge; Xiaoshan Geng; Zhihao Yang; Guo Li; Linlin Zhang; Jing Wang; Jinfeng Ma; Cheng Dong; Jun Zhou; et al. (Science Bulletin, 2024)

An experimental investigation on the foam proportion for coal dust suppression in underground coal mines - Hongsheng Li; Panpan Xu; Songyong Liu; Juan Wang; Lei Zhang; Huifu Ji; Feng Guo; Ge Li (Process Safety and Environmental Protection, 2024)

Nanoplastics induced health risk: Insights into intestinal barrier homeostasis and potential remediation strategy by dietary intervention - Xuemei Meng; Lei Ge; Jiawei Zhang; Jinkai Xue; Graciela Gonzalez-Gil; Johannes S. Vrouwenvelder; Shaomin Guo; Zhenyu Li (Journal of Hazardous Materials, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

The effect and mechanism of combined exposure of MC-LR and NaNO2 on liver lipid metabolism - Jun Yang; Zongxin Zhang; Xingde Du; Yongshui Wang; Ruiyang Meng; Kangfeng Ge; Chunrui Wu; Xiao Liang; Huizhen Zhang; Hongxiang Guo (Environmental Research, 2024)

Long-term exposure to ambient ozone and adult-onset asthma: A prospective cohort study - Jiayue Zhang; Baozhuo Ai; Yuming Guo; Lan Chen; Ge Chen; Haitao Li; Hualiang Lin; Zilong Zhang (Environmental Research, 2024)

Experiment evaluation and thermodynamic analysis of pulping modification on ordered conversion of bark in supercritical water - Hui Ge; Yong Huang; Zhaozheng Liu; Fan Liu; Yu-Nan Chen; Liejin Guo (Chemical Engineering Journal, 2024)

Thermodynamic modeling of freeze pretreatment in the destruction of rice straw structure combined with alkaline-hydrothermal method for enzymatic hydrolysis - Qian Dong; Chun-xiao Gong; Ge-liang Xie; Guo-qiang Zhu; Zhen Fang (Bioresource Technology, 2024)

Toxicity comparison and risk assessment of two chlorinated organophosphate flame retardants (TCEP and TCPP) on Polypedates megacephalus tadpoles - Yi-Ge Xie; Zi-Ying Wang; Wen-Qi Xie; Zi-Yong Xiang; Xin-Dan Cao; Jia-Jun Hao; Guo-Hua Ding (Aquatic Toxicology, 2024)

Ablated Sonic Hedgehog Signaling in the Dentate Gyrus of the Dorsal and Ventral Hippocampus Impairs Hippocampal-Dependent Memory Tasks and Emotion in a Rat Model of Depression - Yan Luo; Yan Wang; Feng Qiu; Guanghan Hou; Jian Liu; Hui Yang; Mei Wu; Xuanqi Dong; Dongwei Guo; Ziyan Zhong; Xi Zhang; Jinwen Ge; et al. (Molecular Neurobiology, 2024)

Revealing the heterogeneity of periodic visiting patterns across different ages and spaces using a flexible detection method: A case study of Beijing - Zidong Fang; Tao Pei; Ci Song; Xiaorui Yan; Le Liu; Sihui Guo; Yaxi Liu; Yong Peng; Dasheng Ge; Jie Chen (Applied Geography, 2024)

Water addition but not reduction alters plant biomass–diversity relationship - Yan Yu; Josep Peñuelas; Jordi Sardans; Jiu‐ying Pei; Ge Li; Guo‐lin Liu; Jian‐Sheng Ye (Global Change Biology, 2024)
The relationship between plant aboveground biomass and diversity typically follows a unimodal pattern, showing a positive correlation in resource‐poor habitats and a negative correlation in resource‐rich environments. Precipitation is a crucial resource for both plant biomass and diversity in terrestrial ecosystems. However, the impact of precipitation changes on the relationship between plant biomass and diversity remains unclear. We conduct a water addition field experiment in a semiarid grassland and identify a unimodal relationship between plant biomass and species richness under ambient conditions. Water addition delays the declining phase of this unimodal curve and shift it upward compared to ambient conditions. Our meta‐analysis of water addition experiments conducted across major biomes worldwide (grassland, shrubland, desert, and forest) supports this finding, while water reduction does not alter the biomass–diversity relationship. Water addition increases biomass in all climate but only increases species richness in arid and semiarid climate. Similarly, water reduction decreases biomass in all climate but only reduces species richness in arid and semiarid climate. Species richness in dry subhumid and humid climate does not change significantly. Furthermore, our field experiment shows that water addition increases plant diversity while decreasing soil inorganic nitrogen levels. The increase in one resource, such as water, leads to the scarcity of another, such as nutrient, thus postponing the declining phase of the plant biomass–diversity relationship typically observed in resource‐rich habitats. Our research contributes to predicting the plant biomass–diversity relationship under changing precipitation conditions and highlights the complex interplay between water availability, nutrient level, and plant diversity.

Ratiometric fluorescence platform for the ultrasensitive detection of kanamycin based on split aptamer co-recognition triggers Mg2+-DNAzyme-driven DNA walker systems - Xia Lu; Long Wang; Guowei Li; Yuxin Wang; Guo Hao; Yi Ding; Mengjia Liu; Shangchen Fu; Liqing Xu; Na Ge; Wupeng Ge (Science of The Total Environment, 2024)

Carbohydrate and fatty acid metabolisms are involved in delaying senescence of ‘Zaosu’ pear fruit following caffeic acid treatment - Canying Li; Yan Guo; Hengping Xu; Miao Wang; Yonghong Ge (Postharvest Biology and Technology, 2024)

A four-dimensional digital twin framework for fatigue damage assessment of semi-submersible platforms and practical application - Bo Wu; Qiangqiang Wei; Xin Li; Yufeng Kou; Wenyue Lu; Haiyang Ge; Xiaozhou Guo (Ocean Engineering, 2024)

Sulfur migration mechanism of pig manure in supercritical water: A combined experimental and DFT study - Shuyuan Zhang; Mingming Du; Hui Ge; Siqi Rong; Yunan Chen; Liejin Guo (Journal of Hazardous Materials, 2024)

MIL-88A(Fe)/g-C3N4 composite and its catalytic membrane for tetracycline removal via peroxydisulfate activation: Performance, mechanism and toxicity evaluation - Huayu Wang; Yanhua Cao; Changsheng Guo; Ming Ge (Journal of Environmental Chemical Engineering, 2024)

Review of chemical looping technology for energy conservation and utilization: CO2 capture and energy cascade utilization - Jinbiao Yan; Sha Wang; Bin Hu; Huarong Zhang; Lipei Qiu; Weijun Liu; Yun Guo; Jun Shen; Bin Chen; Xiang Ge; Cong Shi (Journal of Environmental Chemical Engineering, 2024)

High efficiency triethylamine gas sensor based on SmVO4 nano octahedron granules - Cheng Yu Xu; Shu Yi Ma; Tian Yuan Dong; Ji Ming Liu; Jin Sha Wei; Hong Tao Jiang; Ping Ni; Ge Ge Fan; Jia Yun Guo (Journal of Environmental Chemical Engineering, 2024)

Correlation analysis of microbial groups and sensory quality in the fourth round of the stacked fermentation of sauce-flavor liquor - Dongying Ge; Yurong Wang; Wenchao Cai; Qiangchuan Hou; Longxin Tian; Juzhen Liu; Jiaping Zhou; Chunhui Shan; Zhuang Guo (Food Bioscience, 2024)

Comprehensive analysis of the complete mitochondrial genome of Lilium tsingtauense reveals a novel multichromosome structure - Kai Qu; Ying Chen; Dan Liu; Haili Guo; Ting Xu; Qi Jing; Lei Ge; Xiuge Shu; Xiaowei Xin; Xiaoman Xie; Boqiang Tong (Plant Cell Reports, 2024)

Effect of Oxygen–Glucose Deprivation of Microglia-Derived Exosomes on Hippocampal Neurons: A Study on miR-124 and Inflammatory Cytokines - Yizhen Zhu; Xue Zhao; Ruojing Liu; Dan Yang; Guo Ge (Journal of Molecular Histology, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

Genetic differences among populations of Gynura procumbens (Lour.) Merr - Jiangfan Yu; Xinjian Tan; Dunyuan Huang; Qiuping Zhong; Ping Gu; Youcheng Zhou; Linqing Cao; Liyun Wang; Xirui Wan; Chuansong Chen; Yaqi Yuan; Hongyan Guo; et al. (Genetic Resources and Crop Evolution, 2024)

Expression characteristics and interference analysis of glucose-6-phosphate dehydrogenase reveal its importance in Pyropia yezoensis under salt stress - Li Huan; Mengmeng Shi; Guohong Lin; Baoyu Zhang; Xiujun Xie; Menglin Guo; Xi Qiang; Zhaojia Ge; Jianfeng Niu; Zhenbing Zheng; Xulei Wang; Guangce Wang (Algal Research, 2024)

Mechanisms of chloride to promote the uptake and accumulation of cadmium in rice (Oryza sativa L.) - Jingxia Guo; Chenghao Ge; Guo Wang; Dongmei Zhou (Science of The Total Environment, 2024)

The effect of artificial light at night (ALAN) on the characteristics of diapause of Aedes albopictus - Qing Liu; Heng-Duan Zhang; Dan Xing; Jing-Wen Xie; Yu-Tong Du; Ming Wang; Zi-Ge Yin; Nan Jia; Chun-Xiao Li; Teng Zhao; Yu-Ting Jiang; Yan-De Dong; et al. (Science of The Total Environment, 2024)

The azole biocide climbazole induces oxidative stress, inflammation, and apoptosis in fish gut - Zhi-Jie Lu; Wen-Jun Shi; Dong-Dong Ma; Jin-Ge Zhang; Xiao-Bing Long; Si-Ying Li; Fang-Zhou Gao; Qian-Qian Zhang; Guang-Guo Ying (Science of The Total Environment, 2024)

Investigation of dry environment construction Equipment's medium displacement system for submarine pipelines - Kaichuang Wang; Jiawang Chen; Jian Huang; Peiwen Lin; Jin Guo; Hai Zhu; Yuping Fang; Xuehua Chen; Guomin Cao; Wenbao Jia; Xu Gao; Han Ge (Ocean Engineering, 2024)

Adaptive output-feedback event-triggered formation control for underactuated ships with obstacle avoidance mechanism - Shang Liu; Guoqing Zhang; Ge Guo; Jiqiang Li (Ocean Engineering, 2024)

A hybrid data-driven and learning-based method for denoising low-cost IMU to enhance ship navigation reliability - Zhaoyi Zhang; Ying Li; Jiyou Wang; Zhichen Liu; Ge Jiang; Hua Guo; Weihang Zhu (Ocean Engineering, 2024)

Causal association between long-term exposure to air pollution and incident Parkinson’s disease - Baozhuo Ai; Jiayue Zhang; Shiyu Zhang; Ge Chen; Fei Tian; Lan Chen; Haitao Li; Yuming Guo; Angela Jerath; Hualiang Lin; Zilong Zhang (Journal of Hazardous Materials, 2024)

Modulator-assisted solvent-free synthesis of amorphous zirconium terephthalate catalyst for efficient oxidative desulfurization - Liang Chu; Junzhen Guo; Zhaokun Wang; Haibin Yang; Zhaohui Liu; Zhi Huang; Liyan Wang; Mu Yang; Ge Wang (Journal of Hazardous Materials, 2024)

Comprehensive analysis of combustion behavior, kinetics, and gas emissions of fungus bran biofuel through torrefaction pretreatment and polypropylene addition - Shuai Guo; Xiaoyan Deng; Lidong Liu; Liya Ge; Grzegorz Lisak (Fuel, 2024)

Study on spray characteristics of micro-nano bubble premixed fuel - Rong Xuan; Liang Guo; Ningning Cai; Wanchen Sun; Yuying Yan; Hao Zhang; Yanling Chen; Han Wang; Junfeng Zhang; Youxin Ge (Fuel, 2024)

Molecular mechanism of dissolvable metal nanoparticles-enhanced CO2 fixation by algae: Metal-chlorophyll synthesis - Ruohua Qu; Na Liu; Qiong Wen; Jingyi Guo; Fei Ge (Environmental Pollution, 2024)

Macroencapsulated Al-Si phase change materials for high temperature latent thermal energy storage - Yunqi Guo; Bo Zhao; Haonan Guo; Yunfei Ge; Nan Sheng; Elisabetta Gariboldi; Chunyu Zhu (Chemical Engineering Journal, 2024)

Growth, nutrient removal, and lipid productivity promotion of Chlorella sorokiniana by phosphate solubilizing bacteria Bacillus megatherium in swine wastewater: Performances and mechanisms - Ya-Ming Ge; Wan-Chuan Xing; Xiu Lu; Shao-Rou Hu; Jun-Zhi Liu; Wei-Feng Xu; Hai-Xiang Cheng; Feng Gao; Qing-Guo Chen (Bioresource Technology, 2024)

A hybrid approach of anaerobic digestion model no. 1 and machine learning to model and optimize continuous anaerobic digestion processes - Yadong Ge; Junyu Tao; Zhi Wang; Lan Mu; Wei Guo; Zhanjun Cheng; Beibei Yan; Yan Shi; Hong Su; Guanyi Chen (Biomass and Bioenergy, 2024)

Interdecadal change of Tibetan Plateau vortices during the past 4 decades and its possible mechanism - Zhiqiang Lin; Weidong Guo; Jun Ge; Xiuping Yao; Dongsheng Su (Climate Dynamics, 2024)
The Tibetan Plateau vortices (TPVs) are mesoscale weather systems active at the near-surface of the Tibetan Plateau (TP), which are one of the major precipitation-producing systems over the TP and its surrounding areas. TPVs mainly occur in the warm season from May to September. In this paper, we investigated the interdecadal change of TPVs in the warm seasons of 1979–2020 with the six widely used reanalysis datasets. A significant change of the TPVs frequency appears around the mid-1990s, associated with less TPVs during 1979–1995 and more TPVs during 1996–2020, which is constant among the multiple reanalysis datasets. The abrupt change of TPVs is caused by a transition of the Atlantic Multi-decadal Oscillation (AMO) from a cold phase to a warm phase in the mid-1990s. The shift of AMO leads to a silk-road pattern-like wave train and a spatially asymmetric change of tropospheric temperature. It modifies the intensity of the subtropical westerly jet and the TP heating, leading to the interdecadal change of TPV activities.

Projected changes of compound droughts and heatwaves in China under 1.5 °C, 2 °C, and 3 °C of global warming - Taizheng Liu; Yuqing Zhang; Bin Guo; Yu Yin; Jing Ge (Climate Dynamics, 2024)

Activation of the calcium signaling, mitogen-activated protein kinase cascade and phenylpropane metabolism contributes to the induction of disease resistance in pear fruit upon phenylalanine treatment - Canying Li; Miao Wang; Yan Guo; Shuran Zhang; Hengping Xu; Yonghong Ge (Postharvest Biology and Technology, 2024)

Enhancement of disease resistance against Alternaria alternata in winter jujube fruit by phenyllactic acid through regulating Ca2+ signaling transduction and mitogen-activated protein kinase cascades - Hengping Xu; Canying Li; Miao Wang; Yan Guo; Shuran Zhang; Yonghong Ge (Postharvest Biology and Technology, 2024)

Methyl jasmonate promotes suberin biosynthesis by stimulating transcriptional activation of AchMYC2 on AchFHT in wound healing of kiwifruit - Xiaopeng Wei; Linyao Liu; Guo Liu; Ping Geng; Xiaobo Wei; Xing Yao; Jiaying Chen; Wenjie Gong; Zhenzhen Ge; Mengpei Liu; Linchun Mao (Postharvest Biology and Technology, 2024)

Synthesis and antifungal activity of 2,4-diacetylphloroglucinol analogues - Xi-Long Guo; Chun-Yan Zhao; Cui-Ping Zhang; Yi Zhu; Qing-Rong Wu; Yuan-Qing Zhou; Ya-Hong Fei; Fang Ge; Wei Shi (Phytochemistry Letters, 2024)

Screening androgen receptor agonists of fish species using machine learning and molecular model in NORMAN water-relevant list - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Chang-Er Chen; Guang-Guo Ying; Wen-Jun Shi (Journal of Hazardous Materials, 2024)

Corrigendum to “Cross-species analysis of transcriptome emphasizes a critical role of TNF-α in mediating MAP2K7/AKT2 signaling in zearalenone-induced apoptosis” [J Hazard Mater 459 (2023) 132226] - Fa-Li Zhang; Ke-Xin Zhu; Jing-Ya Wang; Min Zhang; Jia-Mao Yan; Qing-Chun Liu; Xiao-Yuan Zhang; Jia-Chen Guo; Xuan Liu; Qi-cheng Sun; Wei Ge; Lan Li; et al. (Journal of Hazardous Materials, 2024)

Characterization and prediction modeling of membrane distillation enhanced disc solar still - Lu Zuo; Chenkai Xiao; Ziyang Yan; Long Huang; Zinan Guo; Yunting Ge (Journal of Cleaner Production, 2024)

Forest fire susceptibility mapping based on precipitation-constrained cumulative dryness status information in Southeast China: A novel machine learning modeling approach - Longlong Zhao; Yuankai Ge; Shanxin Guo; Hongzhong Li; Xiaoli Li; Luyi Sun; Jinsong Chen (Forest Ecology and Management, 2024)

Comparative analysis of microbial community structure in the peel and core of Houhuo low-temperature Daqu - Dongying Ge; Wenchao Cai; Zhuang Guo; Zhongjun Liu; Yuanyuan Xu; Chunhui Shan (Food Bioscience, 2024)

Mechanisms of imbalanced testicular homeostasis in infancy due to aberrant histone acetylation in undifferentiated spermatogonia under different concentrations of Di(2-ethylhexyl) phthalate (DEHP) exposure - Yu Tian; Jiachen Guo; Lei Hua; Yinuo Jiang; Wei Ge; Xiaoyuan Zhang; Diya Cai; Dongliang Lu; Bin Wang; Wei Shen; Zhongyi Sun; Baoquan Han (Environmental Pollution, 2024)

Facial synthesis of FeOOH array-anchored carbon fiber as flow-through chloride-capturing electrode for ultrafast and super-stable capacitive deionization - Ziping Wang; Zizhen Liu; Lu Zhang; Zixin Guo; Genzhe Shen; Chenyi Xiao; Qiang Li; Ge Yang; Yong Liu; Xun Yuan (Desalination, 2024)

Measurement of Energy Expenditure by Indirect Calorimetry with a Whole-Room Calorimeter - Guo Zhou; Kaixuan Bao; Hui Xiao; Yamin Ge; Xingxing Kong; Tiemin Liu (Phenomics, 2024)

Effects of New Psychoactive Substance Esketamine on Behaviors and Transcription of Genes in Dopamine and GABA Pathways in Zebrafish Larvae - Si-Ying Li; Wen-Jun Shi; Dong-Dong Ma; Jin-Ge Zhang; Zhi-Jie Lu; Xiao-Bing Long; Xin Liu; Chu-Shu Huang; Guang-Guo Ying (Bulletin of Environmental Contamination and Toxicology, 2024)

Uphill cropland and stability assessment of gained cropland in China over the preceding 30 years - Tingting He; Jianhua Li; Maoxin Zhang; Ge Zhai; Youpeng Lu; Yanlin Wang; Andong Guo; Cifang Wu (Journal of Geographical Sciences, 2024)

Intensive N2 fixation accelerates microbial turnover in cropland soils - Wei Gao; Jun Zhao; Xiaobin Guo; Fang Wang; Xiangbi Chen; Zhenke Zhu; Tida Ge; Lianfeng Wang; Yakov Kuzyakov; Jinshui Wu; Zhongjun Jia (Science of The Total Environment, 2024)

Review of waste plastics treatment and utilization: Efficient conversion and high value utilization - Bin Hu; Sha Wang; Jinbiao Yan; Huarong Zhang; Lipei Qiu; Weijun Liu; Yun Guo; Jun Shen; Bin Chen; Cong Shi; Xiang Ge (Process Safety and Environmental Protection, 2024)

Postharvest caffeic acid dipping enhances disease resistance and storage capacity of ‘Zaosu’ pear fruit via regulating phenylpropane metabolism - Yan Guo; Canying Li; Miao Wang; Hengping Xu; Shuran Zhang; Jiaqi Liu; Yueruxin Jin; Yonghong Ge (Postharvest Biology and Technology, 2024)

An azole fungicide climbazole damages the gut-brain axis in the grass carp - Zhi-Jie Lu; Wen-Jun Shi; Fang-Zhou Gao; Dong-Dong Ma; Jin-Ge Zhang; Si-Ying Li; Xiao-Bing Long; Qian-Qian Zhang; Guang-Guo Ying (Journal of Hazardous Materials, 2024)

Alkaline pulping catalyzed ordered conversion of bark in supercritical water - Hui Ge; Yong Huang; Zhaozheng Liu; Fan Liu; Yu-nan Chen; Liejin Guo (Journal of Cleaner Production, 2024)

Ionic liquid microwave-assisted hydrodistillation extraction of Angelica sinensis essential oil and its own anti-inflammatory and antioxidant activities - Taotao Li; Huanxian Shi; Wenfei Wang; Jia Li; Tiantian Tang; Yujiao Wang; Ding Liu; Kai Yang; Xuan Wang; Jie Wang; Ning Xia; Jinhui Wang; et al. (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Automatic detection tree crown and height using Mask R-CNN based on unmanned aerial vehicles images for biomass mapping - Hancong Fu; Hengqian Zhao; Jinbao Jiang; Yujiao Zhang; Ge Liu; Wanshan Xiao; Shouhang Du; Wei Guo; Xuanqi Liu (Forest Ecology and Management, 2024)

Characterization of key flavor substances and their microbial sources in traditional sour bamboo shoots - Hui Tang; Jin-Kui Ma; Lin Chen; Li-Wen Jiang; Lin-Zhi Kang; Ying-Yu Guo; Ge-Yang Men; Dan-Xia Nie; Rui-Min Zhong (Food Chemistry, 2024)

Investigating the influence of CaCl2 induced surface gelatinization of red adzuki bean starch on its citric acid esterification modification: Structure–property related mechanism - Wei Liang; Qian Zhang; Shuangfeng Guo; Xiangzhen Ge; Huishan Shen; Jie Zeng; Haiyan Gao; Wenhao Li (Food Chemistry, 2024)

pH-responsive PVA/konjac glucomannan/functional liposome terpolymer composites: Spotlight on its structure-performance, functionality, barrier properties, controlled-release behavior, biodegradability, and its intelligent preservation role for food - Wei Liang; Xiangzhen Ge; Qian Lin; Li Niu; Wenqing Zhao; Xinyue Liu; Shuangfeng Guo; Marat Muratkhan; Wenhao Li (Food Packaging and Shelf Life, 2024)

Integration of galvanic reactions and engineered nanoconfinement in iron-copper nanocomposites for highly-efficient remediation of Cr(VI)-contaminated acidic/alkaline water - Sijia Li; Chaowen Chen; Hongjian Ge; Xinyue Guo; Huan Xu; Jia Zhang; Zhengyan Wu (Chemical Engineering Journal, 2024)

Molecular mechanism of phenolic acid biosynthesis in callus of a Tibetan medicinal plant (Mirabilis himalaica) under UV-B treatment - Jiaojiao Guo; Mengyi Liu; Rongchen Li; Bohao Ge; Xueqi Zhao; Yanjing Liu; Xiaozhong Lan; Yuzhen Chen; Cunfu Lu (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Application of temperature-sensitive liquid embolic agent loaded with oxaliplatin in the TACE procedure for rabbit VX2 gastric cancer - Yahua Li; Xiaoyong Ge; Zongming Li; Zihe Zhou; Kunpeng Wu; Yifan Li; Tengfei Ji; Changran Wang; Kefeng Guo; Jianzhuang Ren; Xinwei Han; Kewei Ren (Drug Delivery and Translational Research, 2024)

In-Line Inspection (ILI) Techniques for Subsea Pipelines: State-of-the-Art - Hai Zhu; Jiawang Chen; Yuan Lin; Jin Guo; Xu Gao; Yuanjie Chen; Yongqiang Ge; Wei Wang (Journal of Marine Science and Engineering, 2024)
Offshore oil and gas resources play a crucial role in supplementing the energy needs of human society. The crisscrossing subsea pipeline network, which serves as vital infrastructure for the storage and transportation of offshore oil and gas, requires regular inspection and maintenance to ensure safe operation and prevent ecological pollution. In-line inspection (ILI) techniques have been widely used in the detection and inspection of potential hazards within the pipeline network. This paper offers an overview of ILI techniques used in subsea pipelines, examining their advantages, limitations, applicable scenarios, and performance. It aims to provide valuable insights for the selection of ILI technologies in engineering and may be beneficial for those involved in pipeline integrity management and planning.

Potential Role of Bmal1 in Lipopolysaccharide-Induced Depression-Like Behavior and its Associated "Inflammatory Storm" - Dan-Dan Xu; Zhi-Qi Hou; Ya-Yun Xu; Jun Liang; Ye-Jun Gao; Chen Zhang; Fan Guo; Dan-Dan Huang; Jin-Fang Ge; Qing-Rong Xia (Journal of Neuroimmune Pharmacology, 2024)

Infection of PRRSV inhibits CSFV C-strain replication by inducing macrophages polarization to M1 - Tianbei Tuo; Dengjin Chen; Lihong Wang; Yongning Zhang; Lei Zhou; Xinna Ge; Jun Han; Xin Guo; Hanchun Yang (Veterinary Microbiology, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Formation control of UAV–USV based on distributed event-triggered adaptive MPC with virtual trajectory restriction - Yakun Zhu; Shilong Li; Ge Guo; Pengfei Yuan; Jianguo Bai (Ocean Engineering, 2024)

Catalytic gasification of anthracene in supercritical water with Ni/TiO2 catalyst: Products distribution and kinetics - Fanrui Meng; Shenghui Guo; Shi Liu; Changyifan Ren; Xingang Qi; Hui Jin; Zhiwei Ge; Liejin Guo (Fuel, 2024)

Micro- and nanoplastics interact with conventional pollutants on microalgae: Synthesis through meta-analysis - Jingke Ge; Peng Jin; Shuyu Xie; John Beardall; Yuan Feng; Can Guo; Zengling Ma; Guang Gao (Environmental Pollution, 2024)

Interactions between soil bacterial communities, assembly processes and microbial functions along the elevational gradient - Donghui Zhao; Congcong Shen; Zhi-Ming Zhang; Jichen Wang; Li-Mei Zhang; Baodong Chen; Guo-Xin Sun; Yuan Ge (CATENA, 2024)

New dating indicates intermittent human occupation of the Nwya Devu Paleolithic site on the high-altitude central Tibetan Plateau during the past 45,000 years - Junyi Ge; Xiaoling Zhang; Shejiang Wang; Linhui Li; Wei He; Yingshuai Jin; Peiqi Zhang; Bing Xu; Chenglong Deng; John W. Olsen; Zhengtang Guo; Xing Gao (Science China Earth Sciences, 2024)

Circ_0091579 Knockdown Inhibited HCC Proliferation and Glutamine Metabolism Through miR-1270/YAP1 Axis - Ming Liu; Bing Guo; Ge Zhang; Huanpeng Qi (Biochemical Genetics, 2024)

Impact of heat on emergency hospital admissions related to kidney diseases in Texas: Uncovering racial disparities - Chunyu Guo; Erjia Ge; Manzhu Yu; Changwei Li; Xiangqian Lao; Shuang Li; Jason Glaser; Yongqun He; Marina Almeida-Silva; Sisi Meng; Wei-Chung Su; Junfeng Zhang; et al. (Science of The Total Environment, 2024)

Phenyllactic acid maintains the storage quality of ‘Zaosu’ pears by regulating respiration and energy metabolism - Shuran Zhang; Canying Li; Miao Wang; Hengping Xu; Yan Guo; Yonghong Ge (Postharvest Biology and Technology, 2024)

Trajectory tracking control of two-joint underwater manipulator in ocean-wave environment - Dahui Ge; Guo Wang; Junbo Ge; Bing Xiang; Yunxiang You; Aichun Feng (Ocean Engineering, 2024)

A new method for point pollution source identification based on remote sensing inversion and water streamlines - Lan Luo; Yanjun Zhang; Wenxun Dong; Guo Zhang; Yi Xiao; Zhaohua Ge; Jinglin Zhang (Journal of Hydrology, 2024)

Detached eddy simulation of the heat release characteristics of H2-O2 reacting flow in supercritical water - Lijing Bei; Di Su; Jiawei Zhang; Hui Jin; Zhiwei Ge; Yunan Chen; Liejin Guo (Fuel, 2024)

Efficient degradation of ciprofloxacin in wastewater by CuFe2O4/CuS photocatalyst activated peroxynomosulfate - Xinyu Jia; Jinhui Zhang; Qinglin Huang; Chunyu Xiong; Haixia Ji; Qifang Ren; Zhen Jin; Shaohua Chen; Wanmi Guo; Jing Chen; Yao Ge; Yi Ding (Environmental Research, 2024)

Pore water pressure maintaining sampler for deployment on deep-sea ROV-Jellyfish - Ying Wang; Jin Guo; Xinghui Tan; Jiawang Chen; Yuping Fang; Wei Wang; Yongqiang Ge (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Self-limiting growth of thin dense LTA membranes boosts H2 gas separation performance - Pengyao Yu; Ge Yang; Yongming Chai; Lubomira Tosheva; Chunzheng Wang; Heqing Jiang; Chenguang Liu; Hailing Guo (Chemical Engineering Journal, 2024)

Fructooligosaccharides and fructans from Platycodon grandiflorum: Structural characterization, lung-oriented guidance and targetability - Jun Liang; Wen-Fei Wang; Yi Zhang; Yan-Qun Chai; Ya-Ge Li; Si-Liang Jiang; Xin-Hua Zhu; Yu-Li Guo; Zhen Wei; Xi-Zhe Sun; Hai-Xue Kuang; Yong-Gang Xia (Carbohydrate Polymers, 2024)

Organic fertilizers incorporation increased microbial necromass accumulation more than mineral fertilization in paddy soil via altering microbial traits - Zhe Li; Xiaomeng Wei; Zhenke Zhu; Yunying Fang; Hongzhao Yuan; Yuhong Li; Qihong Zhu; Xiaobin Guo; Jinshui Wu; Yakov Kuzyakov; Tida Ge (Applied Soil Ecology, 2024)

Tracking photosynthetic phenology using spectral indices at the leaf and canopy scales in temperate evergreen and deciduous trees - Jiaqi Guo; Xiaohong Liu; Wensen Ge; Liangju Zhao; Wenjie Fan; Xinyu Zhang; Qiangqiang Lu; Xiaoyu Xing; Zihan Zhou (Agricultural and Forest Meteorology, 2024)

A comprehensive observation on the pollution characteristics of peroxyacetyl nitrate (PAN) in Beijing, China - Hailiang Zhang; Shengrui Tong; Wenqian Zhang; Yanyong Xu; Mingzhu Zhai; Yucong Guo; Xin Li; Lili Wang; Guiqian Tang; Zirui Liu; Bo Hu; Chengtang Liu; et al. (Science of The Total Environment, 2023)

A semi-analytical model to estimate Chlorophyll-a spatial-temporal patterns from Orbita Hyperspectral image in inland eutrophic waters - Zhubin Zheng; Chao Huang; Yunmei Li; Heng Lyu; Changchun Huang; Na Chen; Ge Liu; Yulong Guo; Shaohua Lei; Runfei Zhang; Jianzhong Li (Science of The Total Environment, 2023)

Preparation and characterization of polyvinyl alcohol/glutaraldehyde cross-linked chitosan/ε-Polylysine degradable composite film and its antibacterial effect - Shuangfeng Guo; Xiuyun Zhang; Rong Ma; Xiangzhen Ge; Huishan Shen; Wei Liang; Guoquan Zhang; Wenhao Li (Journal of Food Engineering, 2023)

pH-Responsive graphene oxide/poly (methacrylic acid) hybrid nanofiltration membrane performance for water treatment - Li-yue Sun; De-hao Yu; Zhao-ge Juan; Yao Wang; Yan-xin Wang; Matt J. Kipper; Lin-jun Huang; Jian-guo Tang (Journal of Environmental Chemical Engineering, 2023)

Conversion of CO2 through solid oxide co-electrolysis cell with cobalt-free fuel electrode - Ben Ge; Panpan Zhang; Zeyang Wang; Junjie Zhou; Zhaowen Wang; Yi Guo; Zhibin Yang (Fuel, 2023)

Edible electrospun zein nanofibrous scaffolds close the gaps in biofilm formation ability between microorganisms - Meng-Xin Hu; Fei He; Cheng-Kai Tu; Zhe-Xin Chen; Hui Teng; Xin Shao; Ge-Rui Ren; Ya-Xin Guo (Food Bioscience, 2023)

JAZ1 gene regulates starch biosynthesis and changes physicochemical properties in wheat grains - Sha-Sha Yuan; Peng Fan; Dan-Dan Zhang; Hai-Tao Liu; Peng-Fei Wang; Tian-Cai Guo; Ge-Zi Li; Yong-Hua Wang; Guo-Zhang Kang (Food Bioscience, 2023)

Inducing root redundant development to release oxygen: An efficient natural oxygenation approach for subsurface flow constructed wetland - Jingying Zhang; Qiuhui Yan; Ge Bai; Dun Guo; Yanbin Chi; Bin Li; Lei Yang; Yongxiang Ren (Environmental Research, 2023)

Ephedrine and cocaine cause developmental neurotoxicity and abnormal behavior in zebrafish - Dong-Dong Ma; Wen-Jun Shi; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Xiao-Bing Long; Xin Liu; Chu-Shu Huang; Guang-Guo Ying (Aquatic Toxicology, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Occurrence, Migration, and Transformation of Black Carbon in Environmental Matrix and Its Influence on the Environmental Fate of Coexisting Pollutants: A Review - Yaqian Gao; Yuhui Ge; Yunfeng Ma; Hailun Zhao; Guixing Xiao; Pau Loke Show; Jianqiu Chen; Ruixin Guo; Yanhua Liu (Reviews of Environmental Contamination and Toxicology, 2023)

Self-assembly of Fe-MOF on vermiculite nanosheets with enhanced catalytic activity - Haibin Yang; Junzhen Guo; Liang Chu; Zhi Huang; Zhaohui Liu; Liyan Wang; Zhaokun Wang; Mu Yang; Ge Wang (Applied Clay Science, 2023)

Geomorphologic evidences and hydrologic reconstruction of Holocene catastrophic flood events in the Yarlung Tsangpo Grand Canyon, Eastern Himalaya - Yongqiang Guo; Yonggang Ge; Peini Mao; Tao Liu; Xudong Fu; Shuaihu Wu (Journal of Hydrology, 2023)

Enhancing persulfate activation by carbon − based Mn − Fe nanoparticles for groundwater ISCO treatment: Efficiency, stability and mechanism - Ruonan Guo; Beidou Xi; Yuhan Hu; Ying Yuan; Huiru Chen; Yi Gong; Xiaoyuan Ge; Ningqing Lv (Chemical Engineering Journal, 2023)

Structural plane recognition from three-dimensional laser scanning points using an improved region-growing algorithm based on the robust randomized Hough transform - Zhi-hua Xu; Ge Guo; Qian-cheng Sun; Quan Wang; Guo-dong Zhang; Run-qing Ye (Journal of Mountain Science, 2023)

VDR promotes testosterone synthesis in mouse Leydig cells via regulation of cholesterol side chain cleavage cytochrome P450 (Cyp11a1) expression - Yuanyuan Hu; Ling Wang; Ge Yang; Shanshan Wang; Miaomiao Guo; Hongzhao Lu; Tao Zhang (Genes & Genomics, 2023)

Transcriptomic profiling of nuclei from paraformaldehyde-fixed and formalin-fixed paraffin-embedded brain tissues - Yunxia Guo; Junjie Ma; Zhengyue Li; Kaitong Dang; Qinyu Ge; Yan Huang; Guang-zhong Wang; Xiangwei Zhao (Analytica Chimica Acta, 2023)

Aged polycyclic aromatic hydrocarbons as stratigraphic marker in the Anthropocene: Evidence from Tibetan Lake sediments - Jun Li; Ruwen Chang; Xiyu Ban; Guo-Li Yuan; Xinyu Du; Ge Yin; Tian Lin (Water Research, 2023)

Phenylalanine maintains the postharvest quality of ‘Jinfeng’ pear fruit by modulating the tricarboxylic acid cycle and chlorophyll catabolism - Miao Wang; Canying Li; Jiaqi Liu; Shuran Zhang; Yan Guo; Yueruxin Jin; Yonghong Ge (Postharvest Biology and Technology, 2023)

Ent- kaurane diterpenoids from Isodon japonica var. glaucocalyx with PCSK9 inhibitory activities - Ge Wang; Tong Chen; Peng-Ju Guo; Shou Peng; Wen-Qiong Wang; Li-Jiang Xuan (Phytochemistry Letters, 2023)

Dynamic obstacle avoidance of unmanned ship based on event-triggered adaptive nonlinear model predictive control - Shilong Li; Yakun Zhu; Jianguo Bai; Ge Guo (Ocean Engineering, 2023)

Cross-species analysis of transcriptome emphasizes a critical role of TNF-α in mediating MAP2K7/AKT2 signaling in zearalenone-induced apoptosis - Fa-Li Zhang; Ke-Xin Zhu; Jing-Ya Wang; Min Zhang; Jia-Mao Yan; Qing-Chun Liu; Xiao-Yuan Zhang; Jia-Chen Guo; Xuan Liu; Qi-Cheng Sun; Wei Ge; Lan Li; et al. (Journal of Hazardous Materials, 2023)

Experimental study on Diels-Alder addition of conjugated dienes directly from cracking C5 fraction by continuous micro-channel reactors - Zehao Jing; Tingting Ge; Hui Guo; Yuchao Li; Zhou Li; Cuncun Zuo; Ming Wang; Haofei Huang; Lin Guo; Guangjun Cui (Fuel, 2023)

Impacts of an extreme Changjiang flood on variations in carbon cycle components in the Changjiang Estuary and adjacent East China sea - Shuzhen Song; Richard Bellerby; Jing Liu; Wenyun Guo; PeiSong Yu; Jianzhong Ge; Daoji Li (Continental Shelf Research, 2023)

Preparation of porous hollow spherical MoOX/C catalyst for efficient extraction and oxidative desulfurization - Junzhen Guo; Baozhen Li; Danfeng Zhao; Liang Chu; Haibin Yang; Zhi Huang; Zhaohui Liu; Mu Yang; Ge Wang (Chemical Engineering Journal, 2023)

Highly dispersed FeN-CNTs heterogeneous electro-Fenton catalyst for carbamazepine removal with low Fe leaching at wide pH - Jieru Guo; Ge Song; Minghua Zhou (Chemical Engineering Journal, 2023)

Construction of charge-switchable and pH-sensitive carboxymethyl chitosan/Zn2+/heterocycle nanocomposite for the treatment of phytopathogens in agriculture - Xuexue Liang; Ge Bai; Chunhua Niu; Yulong Feng; Zhong Wei; Zhigang Lei; Kai Chen; Xuhong Guo (Chemical Engineering Journal, 2023)

Climbazole causes cell apoptosis and lipidosis in the liver of grass carp - Zhi-Jie Lu; Wen-Jun Shi; Fang-Zhou Gao; Dong-Dong Ma; Jin-Ge Zhang; Si-Ying Li; Xiao-Bing Long; Qian-Qian Zhang; Guang-Guo Ying (Aquatic Toxicology, 2023)

Genetic Algorithm Optimized Light Gradient Boosting Machine for 3D Mineral Prospectivity Modeling of Cu Polymetallic Skarn-Type Mineralization, Xuancheng Area, Anhui Province, Eastern China - He Li; Xiaohui Li; Feng Yuan; Mingming Zhang; Xiangling Li; Can Ge; Zhiqiang Wang; Dong Guo; Xueyi Lan; Minhui Tang; Sanming Lu (Natural Resources Research, 2023)

Identification of watermelon H3K4 and H3K27 genes and their expression profiles during watermelon fruit development - Yang Qiao; Yan-Ge Li; Tong-Lu Wei; Hai-Nan Liu; Mao-Song Pei; Xue-Jie Zhu; Zhong-Hou Zhu; Da-Long Guo (Molecular Biology Reports, 2023)

The carbon-doped Fe3O4 montmorillonite particle electrode for the degradation of antiviral drugs in electro-Fenton system - Ting Zhang; Ge Bai; Nan Cai; Yongqian Lei; Pengran Guo; Jingwei Xu (Applied Clay Science, 2023)

Hyperspectral image classification Based on weakened Laplacian pyramid and guided filtering - Wuli Wang; Ge Wang; Yumeng Jiang; Wenhui Guo; Guangbo Ren; Jianbu Wang; Yanjiang Wang (International Journal of Remote Sensing, 2023)

PRRSV inhibited the proliferation of CSFV by inducing IL-1β maturation via NLRP3 inflammasome activation - Dengjin Chen; Tianbei Tuo; Yongning Zhang; Lei Zhou; Xinna Ge; Jun Han; Xin Guo; Hanchun Yang (Veterinary Microbiology, 2023)

The behavior of microplastics and nanoplastics release from UV-aged masks in the water - Hao Liang; Ruiyang Guo; Di Liu; Ningning Song; Fangli Wang; Yan Li; Wei Ge; Chao Chai (Science of The Total Environment, 2023)

Structural and species diversity explain aboveground carbon storage in forests across the United States: Evidence from GEDI and forest inventory data - Erin T.H. Crockett; Jeff W. Atkins; Qinfeng Guo; Ge Sun; Kevin M. Potter; Scott Ollinger; Carlos A. Silva; Hao Tang; Christopher W. Woodall; Justin Holgerson; Jingfeng Xiao (Remote Sensing of Environment, 2023)

Selection strategies and finite-time target tracking of multiple unmanned surface vehicles with mode uncertainty and disturbances - Yakun Zhu; Jianguo Bai; Shilong Li; Ge Guo (Ocean Engineering, 2023)

Numerical study of reaction enhancement in hydrogen oxidation reactor with supercritical water medium by twisted oval structure - Fei Shang; Jiawei Zhang; Hui Jin; Zhiwei Ge; Yunan Chen; Bin Chen; Liejin Guo (Fuel, 2023)

EMT-NH2 zeolite interlayer induces the formation of high-performance polyamide membrane - Shengchao Wei; Yaoli Guo; Ge Yang; Hailing Guo; Zifeng Yan; Svetlana Mintova; Q. Jason Niu (Chemical Engineering Journal, 2023)

Fine-tuning channel structure and surface chemistry of stable bismuth-organic frameworks for efficient C2H4 purification through reversely trapping CO2 and C2H2 - Chunlian Hao; Zhencui Ge; Rajamani Krishna; Hao Ren; Houyu Zhu; Yuhua Chi; Wen Zhao; Xiuping Liu; Wenyue Guo (Chemical Engineering Journal, 2023)

Continuous productions of highly fluorescent carbon dots and enriched polymer nanofibers via microfluidic techniques - Yifeng Chen; Anze Shen; Jiazhuang Guo; Liangliang Zhu; Ge Li; Ying Qin; Xiaowei Qu; Cai-Feng Wang; Su Chen (Chemical Engineering Journal, 2023)

Effects of Fertilization of Different Crops on Non-Point Source Pollution in the Upper Reaches of Erhai Lake Basin - Hao Zhao; Jing Li; Honggang Zheng; Jianhua Li; Jianxiong Wang; Lijun Liao; Xingyan Ge; Yunchun Chen; Xiaofei Guo; Weijun Zeng (Water, Air, & Soil Pollution, 2023)

Long-term seismic network in South China Sea by floating MERMAIDs - Yong Yu; Yongshun John Chen; Zhen Guo; Zengxi Ge (Science China Earth Sciences, 2023)

A simple creep model for soft clay incorporating its deviatoric features - Chen Ge; Zhu Jungao; He Kun; Ran Congyong; Guo Wanli (Bulletin of Engineering Geology and the Environment, 2023)

Multiple genotypes infection and molecular characterization of Torque teno neovison virus: A novel Anelloviridae of mink in China - Weizhi Xin; Zhiyuan Guo; Lin Wang; Yifan Li; Haikun Shangguan; Kun Xue; Hongyan Chen; Hongliang Yang; Lili Zhao; Junwei Ge (Research in Veterinary Science, 2023)

Ferulic acid enhanced resistance against blue mold of Malus domestica by regulating reactive oxygen species and phenylpropanoid metabolism - Mi Guo; Canying Li; Rui Huang; Linhong Qu; Jiaxin Liu; Chenyang Zhang; Yonghong Ge (Postharvest Biology and Technology, 2023)

Experimental study on supercritical water gasification of oily sludge using a continuous two-step method - Gaoyun Wang; Jiasunle Li; Xujun Li; Jiajing Kou; Zhiwei Ge; Linhu Li; Pai Peng; Liejin Guo (Journal of Hazardous Materials, 2023)

Quantitative analysis of abandonment and grain production loss under armed conflict in Ukraine - Tingting He; Maoxin Zhang; Wu Xiao; Ge Zhai; Yan Wang; Andong Guo; Cifang Wu (Journal of Cleaner Production, 2023)

Conversion by thermostable β-glucosidase Tpebgl3 improves the anti-tumor activity of Panax notoginseng saponins against breast cancer - Xianying Fang; Yuan Dai; Jingqiu Wang; Guoqin Guo; Xiangyang Ge; Linguo Zhao (Food Bioscience, 2023)

Fabrication of submicron linewidth silver grid/ionogel hybrid films for highly stable flexible transparent electrodes via asymmetric wettability template-assisted self-assembly - Zhixin Wang; Xiaohan Sun; Zilong Guo; Rubing Xi; Lingyun Xu; Zhihao Zhao; Yinghao Ge; Ziquan Cao; Xiangyu Jiang; Wensheng Yang; Lei Jiang (Chemical Engineering Journal, 2023)

A novel index combining temperature and vegetation conditions for monitoring surface mining disturbance using Landsat time series - Tingting He; Maoxin Zhang; Andong Guo; Ge Zhai; Cifang Wu; Wu Xiao (CATENA, 2023)

Norethindrone suppress the germ cell development via androgen receptor resulting in male bias - Xiao-Bing Long; Wen-Jun Shi; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying (Aquatic Toxicology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Spatial organization and connectivity of wood rays in Pinus massoniana xylem based on high-resolution μCT-assisted network analysis - Lingyu Ma; Qiulu Meng; Xiaomei Jiang; Zhedong Ge; Zixiong Cao; Yupei Wei; Lichao Jiao; Yafang Yin; Juan Guo (Planta, 2023)

A time-series analysis of short-term ambient ozone exposure and hospitalizations from acute myocardial infarction in Henan, China - Yulong Wei; Lin Fei; Yongbin Wang; Min Zhang; Zhigang Chen; Huige Guo; Shiqi Ge; Sen Zhu; Pingshuan Dong; Kan Yang; Na Xie; Guoan Zhao (Environmental Science and Pollution Research, 2023)
Epidemiological studies in recent years have identified an association between exposure to air pollutants and acute myocardial infarction (AMI); however, the association between short-term ozone (O 3 ) exposure and AMI hospitalization remains unclear, particularly in developing countries. Therefore, this study collected information on 24,489 AMI patients, including daily air pollutant and meteorological data in Henan, China, between 2016 and 2021. A distributed lagged nonlinear model combined with a Poisson regression model was used to estimate the nonlinear lagged effect of O 3 on AMI hospitalizations. We also quantified the effects of O 3 on the number of AMI hospitalizations, hospitalization days, and hospitalization costs. The results showed that single- and dual-pollution models of O 3 at lag0, lag1, and lag (01–07) were risk factors for AMI hospitalizations, with the most significant effect at lag03 (RR = 1.132, 95% CI:1.083–1.182). Further studies showed that males, younger people (15–64 years), warm seasons, and long sunshine duration were more susceptible to O 3 . Hospitalizations attributable to O 3 during the study period accounted for 11.66% of the total hospitalizations, corresponding to 2856 patients, 33,492 hospital days, and 90 million RMB. Maintaining O 3 at 10–130 µg/m 3 can prevent hundreds of AMI hospitalizations and save millions of RMB per year in Henan, China. In conclusion, we found that short-term exposure to O 3 was significantly associated with an increased risk of hospitalization for AMI in Henan, China, and that further reductions in ambient O 3 levels may have substantial health and economic benefits for patients and local healthcare facilities. Graphical Abstract

Ecosystem sustainability of rice and aquatic animal co-culture systems and a synthesis of its underlying mechanisms - Lei Ge; Yu Sun; Yujie Li; Luyao Wang; Guanqing Guo; Lili Song; Cui Wang; Guogan Wu; Xiaoyun Zang; Xiaomei Cai; Shuangxi Li; Peng Li (Science of The Total Environment, 2023)

Nonagricultural emissions enhance dimethylamine and modulate urban atmospheric nucleation - Yunhua Chang; Qingyang Ling; Xinlei Ge; Xiangyang Yuan; Shengqian Zhou; Kai Cheng; Jianjiong Mao; Dandan Huang; Qingyao Hu; Jun Lu; Shijie Cui; Yaqing Gao; et al. (Science Bulletin, 2023)

The influence of dietary Coenzyme Q10 on growth performance, antioxidant capacity and resistance against Aeromonas hydrophila of juvenile European eel (Anguilla anguilla) - Ying Huang; Ruxiang Ge; Gege Lou; Nengzuo Jiang; Xiaoming Zhu; Yazhe Guo; Haokun Liu; Xuanyu Liu; Xinhua Chen (Fish & Shellfish Immunology, 2023)

Insight into the interconversion mechanisms during the supercritical water gasification of bark - Hui Ge; Lei Yi; Yong Huang; Pai Peng; Wen Cao; Yu-nan Chen; Liejin Guo (Chemical Engineering Journal, 2023)

Tracing magnesium flows in China: A dynamic material flow analysis - Tianjiao Guo; Yong Geng; Xiaoqian Song; Xue Rui; Zewen Ge (Resources Policy, 2023)

Magnetic MnFe2O4 nanoparticles anchored on sludge-derived biochar in activating peroxydisulfate for levofloxacin degradation: Mechanism, degradation pathways and cost analysis - Xiaoyan Meng; Tingting Song; Chao Zhang; Huayu Wang; Ming Ge; Changsheng Guo (Journal of Environmental Chemical Engineering, 2023)

Evaluation of a novel carbon-based micro-nano zero-valent iron composite for immobilization of heavy metals in soil - Song Guo; Huifen Yang; Qiwei Sun; Ge Zhang; Tong Zhao; Yichen Zhou; Xuan Li; Pu Gao (Journal of Environmental Chemical Engineering, 2023)

Chemical conversions of free phytosterols during the bleaching of corn oil - Ge Bai; Chuan-Guo Ma; Yu-Yuan Hu; Shu-Jing Guo; Tong Wang (Food Chemistry, 2023)

Emerging co-synthesis of dimethyl oxalate and dimethyl carbonate using Pd/silicalite-1 catalyst with synergistic interactions of Pd and silanols - Chunzheng Wang; Ningkun Xu; Ke Huang; Bin Liu; Peihua Zhang; Ge Yang; Hailing Guo; Peng Bai; Svetlana Mintova (Chemical Engineering Journal, 2023)

Association between nitrogen dioxide concentration and hypertension hospitalization: A multicenter time-series analysis in Xinxiang, China - Shi-qi Ge; Yong-bin Wang; Fei Lin; Run-ran Miao; Kai Zhang; Li Li; Hui-ge Guo; Qian Wang; Li Zhang; Zhi-gang Chen; Guo-an Zhao (Atmospheric Pollution Research, 2023)

Reconstruction of mid-Holocene extreme flood events in the upper Minjiang River valley, eastern Tibetan Plateau, China - Yongqiang Guo; Yonggang Ge; Peini Mao; Tao Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Readily regenerated porous fiber-supported metal tin sulfide for rapid and selective removal of cesium from wastewater - Can Liu; Haojie Ge; Linxue Yan; Xiaoping Yu; Yafei Guo; Nelson Belzile; Tianlong Deng (Journal of Cleaner Production, 2023)

Polystyrene microplastics facilitate the biotoxicity and biomagnification of ZnO nanoparticles in the food chain from algae to daphnia - Jingyi Guo; Na Liu; Qiting Xie; Lizhong Zhu; Fei Ge (Environmental Pollution, 2023)

Experimental investigation of the seismic performance of precast post-tensioned segmental bridge piers with stainless energy-dissipating bars - Jian-Yu Fu; Xiao Ge; Jian-Tao Li; Zhi-Guo Sun; Hui Qian; Dong-Sheng Wang (Engineering Structures, 2023)

Substitutes or complements? Exploring the impact of environmental regulations and informal institutions on the clean energy utilization behaviors of farmers - Jinhua Xie; Gangqiao Yang; Ge Wang; Yaying Zhu; Zhaoxia Guo (Environment, Development and Sustainability, 2023)

Associations of selenium exposure with blood lipids: Exploring mediating DNA methylation sites in general Chinese urban non-smokers - Xiuquan Nie; Ge Mu; Yanjun Guo; Shijie Yang; Xing Wang; Zi Ye; Qiyou Tan; Mengyi Wang; Min Zhou; Jixuan Ma; Weihong Chen (Science of The Total Environment, 2023)

Cooperative target substitution tracking control of multiple unmanned surface vehicles with substitute USVs - Yakun Zhu; Jianguo Bai; Ge Guo (Ocean Engineering, 2023)

Sulfur transformation mechanism during supercritical water gasification of black liquor - Libo Lu; Wenwen Wei; Fan Liu; Zhiwei Ge; Hui Jin; Yunan Chen; Liejin Guo (Fuel, 2023)

Highly efficient metal-acid synergetic catalytic fractionation of lignocellulose under mild conditions over lignin-coordinated N-anchoring Co single-atom catalyst - Jing Ge; Guanhua Wang; Wenjie Sui; Chuanling Si; Haoran Guo; Yonghao Ni; Jinguang Hu (Chemical Engineering Journal, 2023)

OsCYBDOMG1, a cytochrome b561 domain-containing protein, regulates salt tolerance and grain yield in rice - Ping Deng; Chengjuan Cao; Xingyu Shi; Qun Jiang; Jinjin Ge; Like Shen; Chunxia Guo; Ling Jiang; Wen Jing; Wenhua Zhang (Theoretical and Applied Genetics, 2023)

Application of a novel Ca-Fe-Si-S composite for the synchronous stabilization of As, Zn, Cu, and Cd in acidic arsenic slag - Ge Zhang; Huifen Yang; Xuan Li; Yichen Zhou; Song Guo; Tong Zhao (Environmental Science and Pollution Research, 2023)

Efficient coupling of sulfadiazine removal with microalgae lipid production in a membrane photobioreactor - Feng Gao; Jin-Long Zhou; Yu-Ru Zhang; Ashiwin Vadiveloo; Qing-Guo Chen; Jun-Zhi Liu; Qiao Yang; Ya-Ming Ge (Chemosphere, 2023)

Dispersal limitation and host selection drive geo-specific and plant-specific differentiation of soil bacterial communities in the Tibetan alpine ecosystem - Sai Qu; Congcong Shen; Lin Zhang; Jichen Wang; Li-Mei Zhang; Baodong Chen; Guo-Xin Sun; Yuan Ge (Science of The Total Environment, 2023)

A comprehensive analysis of Holocene extraordinary flood events in the Langxian gorge of the Yarlung Tsangpo River valley - Yongqiang Guo; Yonggang Ge; Peini Mao; Tao Liu (Science of The Total Environment, 2023)

Tri-decadal evolution of land subsidence in the Beijing Plain revealed by multi-epoch satellite InSAR observations - Jie Dong; Shaokun Guo; Nan Wang; Lu Zhang; Daqing Ge; Mingsheng Liao; Jianya Gong (Remote Sensing of Environment, 2023)

Prevalence and genetic diversity of canine coronavirus in northeastern China during 2019–2021 - Nuowa Li; Yue Bai; Runhang Liu; Zhiyuan Guo; Xin Yan; Kongrui Xiang; Feng Liu; Lili Zhao; Junwei Ge (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Assessment of future flood risk induced by sea level rise and tropical cyclones under global warming in the Xiamen Bay, Fujian, China - Wenyun Guo; Ding Yao; Zhi Chen; Pingxing Ding; Jianzhong Ge (Frontiers in Marine Science, 2023)
Tropical cyclone (TC)-induced coastal flooding can lead to severe hazards in low-lying lands and is expected to be exacerbated by sea level rise and TC climatology changes related to the warming climate. Since the dense population in Xiamen Bay, Fujian, China, it is highly valuable in understanding coastal flooding of it, but little studies involved this topic. In this study, we establish a high-resolution numerical model covering all coastal low-lying land in Xiamen Bay based on FVCOM. This model is then used to assess the flood risk in Xiamen Bay under TCs with 10-, 100-, and 1000-year pressures by applying a multi-tracks blend method. The results show that 126 km 2 of low-lying area can be flooded periodically by astronomical tides; and 388, 504, and 598 km 2 of low-lying area can be flooded under TCs with 10-, 100-, and 1000-year pressures, accompanied by increased average flood depths of 2.3, 2.8, and 3.4 m, respectively. By 2100 under SSP5-8.5, the well-protected Xiamen Island becomes impacted by TCs with 10-year pressure, and flood areas under TCs with 100-year pressure are estimated to be nearly equivalent to that under TCs with 1000-year pressure at the current climate. The most increased exposure area by climate change are artificial surfaces and agricultural areas, showing the potential higher flood disasters in future.

Similarity Study of Electromagnetic and Underwater Acoustic Scattering by Three-Dimensional Targets in Unbounded Space - Jie Wang; Hai Lin; Huaihai Guo; Qi Zhang; Junxiang Ge (Journal of Marine Science and Engineering, 2023)
The characterization of targets by electromagnetic (EM) scattering and underwater acoustic scattering is an important object of research in these two related fields. However, there are some difficulties in the simulation and measurement of the scattering by large targets. Consequently, a similarity study between acoustic and EM scattering may help to share results between one domain and the other and even provide a general reference method for the simulation of scattering characteristics in both fields. Based on the method of physical optics, the similarity between the EM scattering of conductors and the acoustic scattering of soft/hard targets and the similarity between the EM scattering of dielectrics and the acoustic scattering of elastics are studied. In particular, we derive how to transfer quantities from one domain into another so that similar scattering patterns arise. Then, according to these transfer rules, the EM scattering and acoustic scattering of three typical targets with different types of boundaries were simulated and measured, and the simulated EM scattering and acoustic scattering curves were found to be in perfect agreement, with correlation coefficients above 0.93. The correlation coefficients between the electromagnetic and acoustic scattering patterns were above 0.98, 0.91, and 0.65 for three typical targets. The simulated and measured scattering results verify the proposed similarity theory of EM and acoustic scattering, including the transfer from one domain into the other and the conditions of EM and acoustic scattering, and illustrate that the acoustic scattering characteristic of the target can be simulated using the EM scattering based on the derived conditions and vice versa.

Identification and localization of morphological feature-specific metabolites in Reynoutria multiflora roots - Meng-Ting Cai; Yu Zhou; Wen-Luan Ding; Yu-Hong Huang; Ying-Shan Ren; Zhi-You Yang; Lei Zhang; Fei Sun; Hai-Biao Guo; Liang-Yun Zhou; Zhi-Hong Gong; Xiu-Hong Piao; et al. (Phytochemistry, 2023)

Salt rhythmite formation and organic matter enrichment in the Qianjiang formation, Jianghan Basin, China: Constraints from alternating dry and wet climates - Taoyuan Ge; Zaixing Jiang; Xiangxin Kong; Hanyong Bao; Fengling Chen; Shiqiang Wu; Libin Guo; Yepeng Yang; Tong Liu; Jiazhi Zhang (Marine and Petroleum Geology, 2023)

Highly selective and easily regenerated novel porous polyacrylonitrile-ammonium phosphomolybdate beads for cesium removal from geothermal water - Qi Liu; Haojie Ge; Can Liu; Ningluo Zhang; Yafei Guo; Tianlong Deng (Journal of Water Process Engineering, 2023)

Oil diffusion mathematical model in oily sludge particle under supercritical water environment - Gaoyun Wang; Le Wang; Linhu Li; Yunan Chen; Wen Cao; Hui Jin; Zhiwei Ge; Liejin Guo (Journal of Hazardous Materials, 2023)

Recent advances in persulfate activation by magnetic ferrite-carbon composites for organic contaminants degradation: Role of carbon materials and environmental application - Tingting Song; Xiaoxuan Kang; Changsheng Guo; Zhangxing He; Ming Ge (Journal of Environmental Chemical Engineering, 2023)

Antimicrobial activity and mechanism of preservatives against Alicyclobacillus acidoterrestris and its application in apple juice - Zhouli Wang; Yu Tian; Qi Wang; Tianmin Guo; Yahong Yuan; Tianli Yue; Hang Jia; Qian Ge; Zidan Zhao; Rui Cai (International Journal of Food Microbiology, 2023)

Climatic factors and human population changes in Eurasia between the Last Glacial Maximum and the early Holocene - Yanyan Yu; Feng He; Stephen J. Vavrus; Amber Johnson; Haibin Wu; Wenchao Zhang; Qiuzhen Yin; Junyi Ge; Chenglong Deng; Michael D. Petraglia; Zhengtang Guo (Global and Planetary Change, 2023)

One-step synthesis of low-cost perylenediimide-based cathode interfacial materials for efficient inverted perovskite solar cells - Tao Wu; Peng Xu; Daizhe Wang; Xingjian Jiang; Fengyun Guo; Shiyong Gao; Ziyi Ge; Yong Zhang (Chemical Engineering Journal, 2023)

Genome-wide signatures of the geographic expansion and breeding of soybean - Ying-Hui Li; Chao Qin; Li Wang; Chengzhi Jiao; Huilong Hong; Yu Tian; Yanfei Li; Guangnan Xing; Jun Wang; Yongzhe Gu; Xingpeng Gao; Delin Li; et al. (Science China Life Sciences, 2023)

Influence of soil infiltration and geomorphic change on main parameters of dam-break floods - Yadong Zhang; Zongkun Li; Jianyou Wang; Wei Ge; Xinyan Guo; Te Wang (Natural Hazards, 2023)

Mussel-inspired magnetic adsorbent MnO2/PDA@Fe3O4 for removing heavy metal ions contaminants in single and mixed systems - Jiangyue Ge; Ning Tang; Jiayin Guo; Mengdie Yu; Yafei Zhang; Xiaodong Li; Jie Liang (Environmental Science and Pollution Research, 2023)

Degradation of carbamazepine over MOFs derived FeMn@C bimetallic heterogeneous electro-Fenton catalyst - Yang Zheng; Xuedong Du; Ge Song; Jinyu Gu; Jieru Guo; Minghua Zhou (Chemosphere, 2023)

Microcystin-LR-induced nuclear translocation of cGAS promotes mutagenesis in human hepatocytes by impeding homologous recombination repair - Xiaofei Wang; Yuchen Zhu; Wenzun Lu; Xiaoying Guo; Liuzeng Chen; Ning Zhang; Shaopeng Chen; Chunmei Ge; Shengmin Xu (Toxicology Letters, 2023)

Trace elements in red swamp crayfish (Procambarus clarkii) in China: Spatiotemporal variation and human health implications - Hui Li; Huaiyan Li; Haiting Zhang; Jing Cao; Tao Ge; Jiale Gao; Yan Fang; Wenling Ye; Ting Fang; Yanhong Shi; Rong Zhang; Xinju Dong; et al. (Science of The Total Environment, 2023)

Comprehensive profiles of per- and polyfluoroalkyl substances in Chinese and African municipal wastewater treatment plants: New implications for removal efficiency - Lulin Jiang; Jingzhi Yao; Ge Ren; Nan Sheng; Yong Guo; Jiayin Dai; Yitao Pan (Science of The Total Environment, 2023)

Reveal the severe spatial and temporal patterns of abandoned cropland in China over the past 30 years - Maoxin Zhang; Guangyu Li; Tingting He; Ge Zhai; Andong Guo; Hang Chen; Cifang Wu (Science of The Total Environment, 2023)

Excellent catalytic performance over acid-treated MOF-808(Ce) for oxidative desulfurization of dibenzothiophene - Liang Chu; Junzhen Guo; Zhi Huang; Haibin Yang; Mu Yang; Ge Wang (Fuel, 2023)

PM2.5-related DNA methylation and the association with lung function in non-smokers - Ge Mu; Xiuquan Nie; Shijie Yang; Zi Ye; Man Cheng; Lieyang Fan; Weihong Qiu; Qiyou Tan; Min Zhou; Yanjun Guo; Weihong Chen (Environmental Pollution, 2023)

Association of long-term air pollution exposure with the risk of prediabetes and diabetes: Systematic perspective from inflammatory mechanisms, glucose homeostasis pathway to preventive strategies - Yayuan Mei; Ang Li; Jiaxin Zhao; Quan Zhou; Meiduo Zhao; Jing Xu; Runkui Li; Yanbing Li; Kai Li; Xiaoyu Ge; Chen Guo; Yongjie Wei; et al. (Environmental Research, 2023)

Stimuli-responsive pesticide carriers based on porous nanomaterials: A review - Jie Zhou; Guangyang Liu; Zhaojiang Guo; Miao Wang; Chenyu Qi; Ge Chen; Xiaodong Huang; Shuo Yan; Donghui Xu (Chemical Engineering Journal, 2023)

The direct modification of metal Cu interface for high-performing solid-state anode via KCu7S4/Cu7S4 interconversion mechanism - Tianyi Gao; Tianyu xiao; Yunshuang Ge; Shuai Zhang; Zimeng Wang; Zhongyu Wang; Zhipeng Ma; Wenfeng Guo; Yuqian Fan (Chemical Engineering Journal, 2023)

Porous polydroxyalkanoates (PHA) scaffolds with antibacterial property for oral soft tissue regeneration - Fanfan Chen; Xinyi Liu; Xiyuan Ge; Yong Wang; Zifan Zhao; Xu Zhang; Guo-Qiang Chen; Yuchun Sun (Chemical Engineering Journal, 2023)

Amphiphilic halloysite nanotube enclosing molybdenum oxide as nanoreactor for efficient desulfurization of model fuels - Junzhen Guo; Liang Chu; Haibin Yang; Zhi Huang; Mu Yang; Ge Wang (Chemical Engineering Journal, 2023)

Supercritical water partial oxidation of indole: Reaction variables, migration pathways, and nitrogen distribution - Shi Liu; Zhiwei Ge; Mingming Du; Liejin Guo (Chemical Engineering Journal, 2023)

Positional cloning identified HvTUBULIN8 as the candidate gene for round lateral spikelet (RLS) in barley (Hordeum vulgare L.) - Dandan Qin; Gang Liu; Rui Liu; Chunchao Wang; Fuchao Xu; Qing Xu; Yu Ling; Guoqing Dong; Yanchun Peng; Shuangtao Ge; Ganggang Guo; Jing Dong; et al. (Theoretical and Applied Genetics, 2023)
Key message Map-based cloning, subcellular localization, virus-induced-gene-silencing and transcriptomic analysis reveal HvTUB8 as a candidate gene with pleiotropic effects on barley spike and leaf development via ethylene and chlorophyll metabolism. Abstract Barley lateral spikelet morphology and grain shape play key roles in grain physical quality and yield. Several genes and QTLs for these traits have been cloned or fine mapped previously. Here, we report the phenotypic and genotypic analysis of a barley mutant with round lateral spikelet (rls) from cv. Edamai 934. rls had round lateral spikelet, short but round grain, shortened awn, thick glume and dark green leaves. Histocytologic and ultrastructural analysis revealed that the difference of grain shape of rls was caused by change of cell arrangement in glume, and the dark leaf color resulted from enlarged chloroplast. HvTUBULIN8 ( HvTUB8 ) was identified as the candidate gene for rls by combination of RNA-Seq, map-based-cloning, virus-induced-gene-silencing (VIGS) and protein subcellular location. A single G-A substitution at the third exon of HvTUB8 resulted in change of Cysteine 354 to tyrosine. Furthermore, the mutant isoform Hvtub8 could be detected in both nucleus and cytoplasm, whereas the wild-type protein was only in cytoplasm and granular organelles of wheat protoplasts. Being consistent with the rare phenotype, the “A” allele of HvTUB8 was only detected in rls , but not in a worldwide barley germplasm panel with 400 accessions. VIGS confirmed that HvTUB8 was essential to maintain spike integrity. RNA-Seq results suggested that HvTUB8 may control spike morphogenesis via ethylene homeostasis and signaling, and control leaf color through chlorophyll metabolism. Collectively, our results support HvTUB8 as a candidate gene for barley spike and leaf morphology and provide insight of a novel mechanism of it in barley development.

Roles of microRNAs and exosomes in Helicobacter pylori associated gastric cancer - Xiao-Han Xu; Shu-Li Shao; Dong Guo; Li-Na Ge; Zan Wang; Peng Liu; Yuan-Yong Tao (Molecular Biology Reports, 2023)

Aberrant Topological Properties of Brain Functional Network in Children with Obstructive Sleep Apnea Derived from Resting-State fMRI - Tingting Ji; Xuemin Ren; Ting Long; Xiaodan Li; Lin Mei; Wentong Ge; Jie Zhang; Shengcai Wang; Yongli Guo; Zhifei Xu; Yun Peng; Jiangang Liu; et al. (Brain Topography, 2023)

Evaluating the effects of contact time and leaching solution on measured solubilities of aerosol trace metals - Rui Li; Shuwei Dong; Chengpeng Huang; Feng Yu; Fu Wang; Xiaofei Li; Huanhuan Zhang; Yan Ren; Mingxian Guo; Qingcai Chen; Baozhu Ge; Mingjin Tang (Applied Geochemistry, 2023)

Inhibition of Spinal 5-HT3 Receptor and Spinal Dorsal Horn Neuronal Excitability Alleviates Hyperalgesia in a Rat Model of Parkinson’s Disease - Cheng-Jie Li; Li-Ge Zhang; Lu-Bing Liu; Meng-Qi An; Li-guo Dong; Han-Ying Gu; Yong-Ping Dai; Fen Wang; Cheng-Jie Mao; Chun-Feng Liu (Molecular Neurobiology, 2022)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Development of a pressure-retaining separation and transfer system for sediment and overlying seawater - Jin Guo; Qixiao Zhou; Yongqiang Ge; Haonan Li; Qiaoling Gao; Ying Wang; Yuan Lin; Jiawang Chen (Frontiers in Marine Science, 2022)
Methane leakage at the interface between sediment and overlying seawater is an important basis for gas hydrate exploration. Therefore, a transfer device with working pressure of 30MPa and corresponding scheme are proposed to separate and transfer the sediment and overlying water inside the sampler under the condition of pressure-retaining. Based on the pressure relief valve with adjustable threshold pressure, the device transfers the overlying water by compressing the internal volume and transfers the sediment by secondary sampling. The performance of transfer device is studied by simulation and experiment. Based on the coupled Eulerian-Lagrangian approach in the Abaqus, the secondary sampling was investigated, and the penetration resistance and coring rate of the secondary sampling tube are 141N and 86.2%, respectively. By using the hydraulic simulation software AMESim, the pressure fluctuation caused by the movement of the mechanism during the transfer process was studied, and the pressure fluctuation amplitude is within 0.89 MPa. Furthermore, the laboratory transfer tests were carried out under high pressure conditions, and meantime, the simulation results are verified. Under the working condition of 30MPa, the device can maintain a pressure loss of no more than 8.0% (2.4MPa) within two hours, maintain pressure fluctuations during the transfer process within 4.8% (1.44MPa), and ensure that the pressure in the culture kettle decreases by 4.7% relative to the pressure in the sampler after the transfer, which shows the feasibility of the device application.

Distribution and ecological risk assessment of heavy metals in sediments of Dajiuhu Lake Wetland in Shennongjia, China - Jiumei Wang; Jiwen Ge; Xiaojing Yang; Dandan Cheng; Chenhao Yuan; Ziwei Liu; Shiyu Yang; Yan Guo; Yansheng Gu (Environmental Science and Pollution Research, 2022)

Combination of bicarbonate and low temperature stress induces the biosynthesis of both arachidonic and docosahexaenoic acids in alkaliphilic microalgae Dunaliella salina HTBS - Zhile Guo; Yuyong Hou; Zhiyong Liu; Yanbo Ma; Tong Han; Nahui Hao; Yuanjiang Yao; Chunxuan Lan; Tongling Ge; Maliheh Safavi; Weijie Wang; Lei Zhao; et al. (Frontiers in Marine Science, 2022)
High bicarbonate levels and low temperature may have an impact on microalgae cultivation. However, changes in cellular composition in response to the combination of the above stresses are still poorly understood. In this study, the combined effects of bicarbonate and low temperature on biochemical changes in alkaliphilic microalgae Dunaliella salina HTBS were investigated. Comparing to the control condition of 25°C without bicarbonate, the cell density was increased from 0.69 to 1.18 in the treatment condition of 0.15 M bicarbonate and low temperature (16 °C) while the lipid\protein\carbohydrate contents were increased from 34.71% to 43.94%, 22.44% to 26.03%, 22.62% to 29.18%, respectively. Meanwhile, the PUFAs, arachidonic acid (AA) and docosahexaenoic acid (DHA) contents reached to 3.52% and 4.73% with the combination of low temperature and bicarbonate, respectively, whereas they were not detected when the cells were treated with single condition. Moreover, both the chlorophyll and carotenoid contents were also detected with increased profiles in the combined treatments. As a result, the maximum photochemical efficiency but not reduced non-photochemical quenching was strengthened, which enhanced the photosynthetic performance. Additionally, our results indicated that D. salina HTBS could acclimate to the combined stress by up-regulating the activity of SOD\CAT and reducing MDA content. These findings demonstrated that the addition of a certain bicarbonate under low temperature could effectively enhance the biomass production and accumulation of AA and DHA, which would benefit the development of the microalgae industry in value-added products.

Transposon insertions within alleles of BnaFT.A2 are associated with seasonal crop type in rapeseed - Qingdong Jin; Gengdong Gao; Chaocheng Guo; Taihua Yang; Ge Li; Jurong Song; Na Zheng; Shuai Yin; Licong Yi; Zhen Li; Xianhong Ge; Graham J. King; et al. (Theoretical and Applied Genetics, 2022)

Involvement of Mitophagy in Primary Cultured Rat Neurons Treated with Nanoalumina - Lan Zhang; Jinjin Zhao; Xinyue Guo; Cuicui Ge; Lijun Chang; Xiaocheng Gao; Tao Huang; Yanhong Wang; Nan Shang; Qiao Niu; Qinli Zhang (Neurotoxicity Research, 2022)

Evaluation of the water pollution risk of dam and dike-break floods in the inundated area - Yadong Zhang; Zongkun Li; Wei Ge; Jianyou Wang; Xinyan Guo; Te Wang; Hua Zhang (Environmental Science and Pollution Research, 2022)

Soil microbe inoculation alters the bacterial communities and promotes root growth of Atractylodes lancea under heat stress - Hongyang Wang; Yuefeng Wang; Daiquan Jiang; Zengxu Xiang; Sheng Wang; Chuanzhi Kang; Wenjin Zhang; Yang Ge; Tielin Wang; Luqi Huang; Dahui Liu; Lanping Guo (Plant and Soil, 2022)

Pathological Networks Involving Dysmorphic Neurons in Type II Focal Cortical Dysplasia - Yijie Shao; Qianqian Ge; Jiachao Yang; Mi Wang; Yu Zhou; Jin-Xin Guo; Mengyue Zhu; Jiachen Shi; Yiqi Hu; Li Shen; Zhong Chen; Xiao-Ming Li; et al. (Neuroscience Bulletin, 2022)

WRKY74 regulates cadmium tolerance through glutathione-dependent pathway in wheat - Ge-Zi Li; Yong-Xing Zheng; Hai-Tao Liu; Jin Liu; Guo-Zhang Kang (Environmental Science and Pollution Research, 2022)

Failure process of a lateral slope deposit and its effect on debris flood formation - Xiaojun Guo; Yonggang Ge; Meiqiang Zhan; Hua Yan (Bulletin of Engineering Geology and the Environment, 2022)

Exploration of walnut components and their association with health effects - Zhi-Jing Ni; Yi-Ge Zhang; Sheng-Xiong Chen; Kiran Thakur; Shaoyun Wang; Jian-Guo Zhang; Ya-Fang Shang; Zhao-Jun Wei (Critical Reviews in Food Science and Nutrition, 2022)

Long-term mercury variations in tree rings of the permafrost forest, northeastern China - Huhu Kang; Xiaohong Liu; Junming Guo; Qiuliang Zhang; Yabo Wang; Jie Huang; Guobao Xu; Guoju Wu; Wensen Ge; Shichang Kang (Science China Earth Sciences, 2022)

OsAPL controls the nutrient transport systems in the leaf of rice (Oryza sativa L.) - Zhen Yan; Man-Yu Yang; Biligen-Gaowa Zhao; Guo Li; Qing Chao; Feng Tian; Ge Gao; Bai-Chen Wang (Planta, 2022)

Production and Evaluation of a Novel Multi-Epitope Bivalent Vaccine Against Echinococcus multilocaularis Metacestode - Runle Li; Mingyuan Xin; Kunmei Liu; Bingwen Hu; Jingwei Ma; Pei Zhou; Lin Feng; Mingquan Pang; Ri-li Ge; Haining Fan; Le Guo; Feng Tang (International Journal of Peptide Research and Therapeutics, 2022)

Extracellular vesicles-associated tRNA-derived fragments (tRFs): biogenesis, biological functions, and their role as potential biomarkers in human diseases - Qiuyan Weng; Yao Wang; Yaoyao Xie; Xiuchong Yu; Shuangshuang Zhang; Jiaxin Ge; Zhe Li; Guoliang Ye; Junming Guo (Journal of Molecular Medicine, 2022)
Traditionally, transfer RNAs (tRNAs) specifically decoded messenger RNA (mRNA) and participated in protein translation. tRNA-derived fragments (tRFs), also known as tRNA-derived small RNAs (tsRNAs), are generated by the specific cleavage of pre- and mature tRNAs and are a class of newly defined functional small non-coding RNAs (sncRNAs). Following the different cleavage positions of precursor or mature tRNA, tRFs are classified into seven types, 5′-tRNA half, 3′-tRNA half, tRF-1, 5′U-tRF, 3′-tRF, 5′-tRF, and i-tRF. It has been demonstrated that tRFs have a diverse range of biological functions in cellular processes, which include inhibiting protein translation, modulating stress response, regulating gene expression, and involvement in cell cycles and epigenetic inheritance. Emerging evidences have indicated that tRFs in extracellular vesicles (EVs) seem to act as regulatory molecules in various cellular processes and play essential roles in cell-to-cell communication. Furthermore, the dysregulation of EV-associated tRFs has been associated with the occurrence and progression of a variety of cancers and they can serve as novel potential biomarkers for cancer diagnosis. In this review, the biogenesis and classification of tRFs are summarized, and the biological functions of EV-associated tRFs and their roles as potential biomarkers in human diseases are discussed.

Analysis of the heavy metals (As, Pb, Cu, Zn) by leaching and sequential extraction procedure from a municipal solid waste incinerator fly ash co-processing cement kiln plant - Nan Yang; Zhimeng Ge; Aihong Li; Baiyong Wei; Yinming Li; Ye Zhang; Qianjin Shen; Tuqiang Wang; Xueqian Wu; Xiangdong Cao; Jianping Guo; Zhaojia Wang (Environmental Monitoring and Assessment, 2022)

Geochronology and geochemistry of the W-Mo-ore-related granitic rocks from eastern Ningzhen, lower Yangtze river belt, eastern China - Fangyue Wang; Yongjie Guo; Haiyang Yan; Haiou Gu; He Sun; Can Ge (Acta Geochimica, 2022)

Association between air pollution and emergency room visits for eye diseases and effect modification by temperature in Beijing, China - Wanzhou Wang; Wenlou Zhang; Hongxia Ge; Baiqi Chen; Jingjing Zhao; Jun Wu; Zefeng Kang; Xinbiao Guo; Furong Deng; Qingbian Ma (Environmental Science and Pollution Research, 2022)

Contamination, risk and quantitative identification of nutrients and potentially toxic elements in the surface sediments of Baiyangdian Lake, North China - Jingzhong Wang; Hao Wei; Zhao Liang; Shuie Zhan; Hongjuan Jia; Shuai Guo; Peixun Ge (Ecotoxicology, 2022)

A Preliminary Study on Silver Isotopic Composition in Polymetallic Ore Deposits in Eastern China - Ge Dong; Hai-Zhen Wei; Yuanfeng Zhu; Xi Liu; Qi Guo; Wei Pu; Yibo Lin; Junlin Wang (Journal of Earth Science, 2022)

Energy-based plastic potential and yield functions for rockfills - Wanli Guo; Ge Chen; Junjie Wang; Fuxian Jian (Bulletin of Engineering Geology and the Environment, 2022)

Tibetan Plateau v ortex‐associated precipitation and its link with the Tibetan Plateau heating anomaly - Zhiqiang Lin; Weidong Guo; Xiuping Yao; Jun Du; Wenkai Li; Jun Ge (International Journal of Climatology, 2021)
The Tibetan Plateau (TP) is known as the Asian water tower that supplies fresh water for millions of people in Asia. The Tibetan Plateau vortices (TPVs) are one of the major precipitation‐producing weather systems over the TP. The characteristics of TPV‐associated precipitation from 1979 to 2017 are quantitatively analysed based on three daily precipitation datasets. The influence of TPVs on precipitation is more significant in the warm season (May–September) because the precipitation and TPV activities both peak in the warm season. The TPV‐associated precipitation (VAP) dominates the total precipitation over most of the TP in the warm season. The VAP contributes more than 50% of the total precipitation in the warm season over 30% of the area over the TP, particularly in the central TP, while the VAP accounts for more than 25% of the total precipitation in the cold season over about 20% of the area over the TP. Therefore, TPVs are the major systems to produce precipitation on the TP in the warm season, and they are also important in the cold season in certain regions. The interannual variation of VAP is mainly determined by the number, rather than the precipitation intensity, of TPVs. Furthermore, the heating anomaly caused by the TP thermodynamic effect is an influential factor of VAP. Stronger (weaker) TP heating and resulting ascending motion strengthen (attenuate) the convergence near the TP surface and the divergence in the upper troposphere. The thermal adaption‐associated circulation generates more (less) TPVs and VAP.

Functional homoeologous alleles of CONSTANS contribute to seasonal crop type in rapeseed - Qingdong Jin; Shuai Yin; Ge Li; Tao Guo; Ming Wan; Haitao Li; Juanjuan Li; Xianhong Ge; Graham J. King; Zaiyun Li; Jing Wang; Guangsheng Zhou (Theoretical and Applied Genetics, 2021)

Simulation of summer climate over Central Asia shows high sensitivity to different land surface schemes in WRF - Sha Lu; Weidong Guo; Yongkang Xue; Fang Huang; Jun Ge (Climate Dynamics, 2021)
Land surface processes are vital to the performance of regional climate models in dynamic downscaling application. In this study, we investigate the sensitivity of the simulation by using the weather research and forecasting (WRF) model at 10-km resolution to the land surface schemes over Central Asia. The WRF model was run for 19 summers from 2000 to 2018 configured with four different land surface schemes including CLM4, Noah-MP, Pleim-Xiu and SSiB, hereafter referred as Exp-CLM4, Exp-Noah-MP, Exp-PX and Exp-SSiB respectively. The initial and boundary conditions for the WRF model simulations were provided by the National Centers for Environmental Prediction Final (NCEP-FNL) Operational Global Analysis data. The ERA-Interim reanalysis (ERAI), the GHCN-CAMS and the CRU gridded data were used to comprehensively evaluate the WRF simulations. Compared with the reanalysis and observational data, the WRF model can reasonably reproduce the spatial patterns of summer mean 2-m temperature, precipitation, and large- scale atmospheric circulation. The simulations, however, are sensitive to the option of land surface scheme. The performance of Exp-CLM4 and Exp-SSiB are better than that of Exp-Noah-MP and Exp-PX assessed by Multivariable Integrated Evaluation (MVIE) method. To comprehensively understand the dynamic and physical mechanisms for the WRF model’s sensitivity to land surface schemes, the differences in the surface energy balance between Ave-CLM4-SSiB (the ensemble average of Exp-CLM4 and Exp-SSiB) and Ave-NoanMP-PX (the ensemble average of Exp-Noah-MP and Exp-PX) are analyzed in detail. The results demonstrate that the sensible and latent heat fluxes are respectively lower by 30.42 W·m −2 and higher by 14.86 W·m −2 in Ave-CLM4-SSiB than that in Ave-NoahMP-PX. As a result, large differences in geopotential height occur over the simulation domain. The simulated wind fields are subsequently influenced by the geostrophic adjustment process, thus the simulations of 2-m temperature, surface skin temperature and precipitation are respectively lower by about 2.08 ℃, 2.23 ℃ and 18.56 mm·month −1 in Ave-CLM4-SSiB than that in Ave-NoahMP-PX over Central Asia continent.

Acrolein Induces Systemic Coagulopathy via Autophagy-dependent Secretion of von Willebrand Factor in Mice after Traumatic Brain Injury - Wenxing Cui; Xun Wu; Dayun Feng; Jianing Luo; Yingwu Shi; Wei Guo; Haixiao Liu; Qiang Wang; Liang Wang; Shunnan Ge; Yan Qu (Neuroscience Bulletin, 2021)
Traumatic brain injury (TBI)-induced coagulopathy has increasingly been recognized as a significant risk factor for poor outcomes, but the pathogenesis remains poorly understood. In this study, we aimed to investigate the causal role of acrolein, a typical lipid peroxidation product, in TBI-induced coagulopathy, and further explore the underlying molecular mechanisms. We found that the level of plasma acrolein in TBI patients suffering from coagulopathy was higher than that in those without coagulopathy. Using a controlled cortical impact mouse model, we demonstrated that the acrolein scavenger phenelzine prevented TBI-induced coagulopathy and recombinant ADAMTS-13 prevented acrolein-induced coagulopathy by cleaving von Willebrand factor (VWF). Our results showed that acrolein may contribute to an early hypercoagulable state after TBI by regulating VWF secretion. mRNA sequencing (mRNA-seq) and transcriptome analysis indicated that acrolein over-activated autophagy, and subsequent experiments revealed that acrolein activated autophagy partly by regulating the Akt/mTOR pathway. In addition, we demonstrated that acrolein was produced in the perilesional cortex, affected endothelial cell integrity, and disrupted the blood-brain barrier. In conclusion, in this study we uncovered a novel pro-coagulant effect of acrolein that may contribute to TBI-induced coagulopathy and vascular leakage, providing an alternative therapeutic target.

Exogenous Glutathione Alleviates Cadmium Toxicity in Wheat by Influencing the Absorption and Translocation of Cadmium - Ge-Zi Li; Shi-Juan Chen; Na-Ying Li; Ying-Ying Wang; Guo-Zhang Kang (Bulletin of Environmental Contamination and Toxicology, 2021)
Cadmium (Cd), a toxic heavy metal, is harmful to plants and human health. Glutathione (GSH) could alleviate Cd toxicity of plant species, whereas its mechanism responsible for wheat remains poorly understood. Here, we found that exogenous GSH application significantly increased the fresh and dry weight, root elongation, chlorophyll contents, while decreased the contents of malondialdehyde (MDA) and GSH, and translocation factor of Cd compared with Cd treatment. Moreover, GSH application significantly increased activities of antioxidant enzymes and expression of related genes, which involved in GSH synthesis, especially in roots. In addition, we found that GSH application suppressed Cd-induced expression of metal transporter genes TaNramp1 , TaNramp5 , TaHMA2 , TaHMA3 , TaLCT1 and TaIRT2 in roots. Taken together, our results suggested that GSH could alleviate Cd toxicity in wheat by increasing GSH synthesis gene expression or suppressing Cd transporter genes expression, and further affecting Cd uptake and translocation in wheat plants.

Genetic changes and evolutionary analysis of canine circovirus - Lin Wang; Yifan li; Zhiyuan Guo; Ying Yi; Han Zhang; Haikun Shangguan; Chengshi Huang; Junwei Ge (Archives of Virology, 2021)

Construction and verification of a rainstorm death risk index based on grid data fusion: a case study of the Beijing rainstorm on July 21, 2012 - Xianhua Wu; Jiqiang Zhao; Yun Kuai; Ji Guo; Ge Gao (Natural Hazards, 2021)

Thermal diffusivity and thermal conductivity of alkali feldspar at 0.8–3 GPa and 300–873 K - Zili Xiong; Baohua Zhang; Jianhua Ge; Shuangmeng Zhai; Xinzhuan Guo (Contributions to Mineralogy and Petrology, 2021)

Activated microglia–induced neuroinflammatory cytokines lead to photoreceptor apoptosis in Aβ-injected mice - Jing Wu; Ge Gao; Fanjun Shi; Hai Xie; Qian Yang; Dandan Liu; Sichang Qu; Haifeng Qin; Chaoyang Zhang; Guo-Tong Xu; Fang Liu; Jingfa Zhang (Journal of Molecular Medicine, 2021)

B3GNT3 acts as a carcinogenic factor in endometrial cancer via facilitating cell growth, invasion and migration through regulating RhoA/RAC1 pathway-associated markers - Ji-Shui Wang; Fang Ruan; Li-Zhu Guo; Feng-Ge Wang; Fu-Ling Wang; Hong-Min An (Genes & Genomics, 2021)

Phylogeny and taxonomy of two new Alternaria (Ascomycota: Pleosporaceae) species in section Gypsophilae from China - Lin He; Hong Cheng; Aye Aye Htun; Hui Ge; Zhen Zhou Xia; Jian Wei Guo; Jian Xin Deng; Tao Du (Mycological Progress, 2021)

Clinical significance of serum miR-487b in HBV-related hepatocellular carcinoma and its potential mechanism - Xiuping Li; Yuzhen Guo; Xiyan Wang; Anning Ge; Hui Wang; Kaiyun Fan; Changtong Guo (Infectious Diseases, 2021)

Determining the Mineral Admixture and Fiber on Mechanics and Fracture Properties of Concrete under Sulfate Attack - Jin-jun Guo; Kun Wang; Cui-ge Qi (Journal of Marine Science and Engineering, 2021)
The concrete structure in the coastal area suffers from the combined erosion of sulfate and dry–wet cycles. In this study, in order to modify ordinary concrete, fly ash, slag powder, silica fume and polyester fiber are added separately. The crack resistance of concrete was studied through mechanical performance test and three-point bending fracture test of notched beam under sulfate dry–wet cycles. The load-crack opening displacement (P-CMOD) curve characteristics, fracture toughness and fracture energy of modified concrete after corrosion are calculated and analyzed. Results reveal that the P-CMOD curve of modified concrete after corrosion has gone through four stages of damage: initial bending section, proportional elastic section, stable expansion section and softening section. With the increase of dry–wet cycles, the overall corrosion resistance and toughening coefficient of modified concrete increases first and then decreases. Adding 25% fly ash can significantly enhance the fracture toughness of concrete in the initial stage. The addition of polyester fiber and slag is beneficial to the improvement of the instability toughness and fracture energy of the concrete in the later stage.

Quantitative Determination of Glymphatic Flow Using Spectrophotofluorometry - Yu Zhang; Jian Song; Xu-Zhong He; Jian Xiong; Rong Xue; Jia-Hao Ge; Shi-Yu Lu; Die Hu; Guo-Xing Zhang; Guang-Yin Xu; Lin-Hui Wang (Neuroscience Bulletin, 2020)

Cortical 3-hinges could serve as hubs in cortico-cortical connective network - Tuo Zhang; Xiao Li; Xi Jiang; Fangfei Ge; Shu Zhang; Lin Zhao; Huan Liu; Ying Huang; Xianqiao Wang; Jian Yang; Lei Guo; Xiaoping Hu; et al. (Brain Imaging and Behavior, 2020)
Mapping the relation between cortical convolution and structural/functional brain architectures could provide deep insights into the mechanisms of brain development, evolution and diseases. In our previous studies, we found a unique gyral folding pattern, termed a 3-hinge, which was defined as the conjunction of three gyral crests. The uniqueness of the 3-hinge was evidenced by its thicker cortex and stronger fiber connections than other gyral regions. However, the role that 3-hinges play in cortico-cortical connective architecture remains unclear. To this end, we conducted MRI studies by constructing structural cortico-cortical connective networks based on a fine-granular cortical parcellation, the parcels of which were automatically labeled as 3-hinge, 2-hinge (ordinary gyrus) or sulcus. On human brains, 3-hinges possess significantly higher degrees, strengths and betweennesses than 2-hinges, suggesting that 3-hinges could serve more like hubs in the cortico-cortical connective network. This hypothesis gains supports from human functional network analyses, in which 3-hinges are involved in more global functional networks than ordinary gyri. In addition, 3-hinges could serve as ‘connector’ hubs rather than ‘provincial’ hubs and they account for a dominant proportion of nodes in the high-level ‘backbone’ of the network. These structural results are reproduced on chimpanzee and macaque brains, while the roles of 3-hinges as hubs become more pronounced in higher order primates. Our new findings could provide a new window to the relation between cortical convolution, anatomical connection and brain function.

Recent Progress in Impacts of Mixing State on Optical Properties of Black Carbon Aerosol - Xiaodong Wei; Yanhong Zhu; Jianlin Hu; Chao Liu; Xinlei Ge; Song Guo; Dantong Liu; Hong Liao; Huijun Wang (Current Pollution Reports, 2020)

Complete Genome of Vibrio neocaledonicus CGJ02-2, An active Compounds Producing Bacterium Isolated from South China Sea - Lin Tan; Isabel Gómez-Betancur; Suxia Guo; Yu Ge; Jianping Zhao; Chang Chen; Nan Wang (Current Microbiology, 2020)

Examining two sets of introgression lines across multiple environments reveals background-independent and stably expressed quantitative trait loci of fiber quality in cotton - Yuzhen Shi; Aiying Liu; Junwen Li; Jinfa Zhang; Shaoqi Li; Jinfeng Zhang; Liujun Ma; Rui He; Weiwu Song; Lixue Guo; Quanwei Lu; Xianghui Xiang; et al. (Theoretical and Applied Genetics, 2020)
Key message Background-independent (BI) and stably expressed (SE) quantitative trait loci (QTLs) were identified using two sets of introgression lines across multiple environments. Genetic background more greatly affected fiber quality traits than environmental factors. Sixty-one SE-QTLs, including two BI-QTLs, were novel and 48 SE-QTLs, including seven BI-QTLs, were previously reported. Abstract Cotton fiber quality traits are controlled by QTLs and are susceptible to environmental influence. Fiber quality improvement is an essential goal in cotton breeding but is hindered by limited knowledge of the genetic basis of fiber quality traits. In this study, two sets of introgression lines of Gossypium hirsutum × G. barbadense were used to dissect the QTL stability of three fiber quality traits (fiber length, strength and micronaire) across environments using 551 simple sequence repeat markers selected from our high-density genetic map. A total of 76 and 120 QTLs were detected in the CCRI36 and CCRI45 backgrounds, respectively. Nine BI-QTLs were found, and 78 (41.71%) of the detected QTLs were reported previously. Thirty-nine and 79 QTLs were SE-QTLs in at least two environments in the CCRI36 and CCRI45 backgrounds, respectively. Forty-eight SE-QTLs, including seven BI-QTLs, were confirmed in previous reports, and 61 SE-QTLs, including two BI-QTLs, were considered novel. These results indicate that genetic background more strongly impacts on fiber quality traits than environmental factors. Twenty-three clusters with BI- and/or SE-QTLs were identified, 19 of which harbored favorable alleles from G. barbadense for two or three fiber quality traits. This study is the first report using two sets of introgression lines to identify fiber quality QTLs across environments in cotton, providing insights into the effect of genetic backgrounds and environments on the QTL expression of fiber quality and important information for the genetic basis underlying fiber quality traits toward QTL cloning and molecular breeding.

Interspecific difference in N:P stoichiometric homeostasis drives nutrient release and soil microbial community composition during decomposition - Hanxiong Song; Jingjing Huang; Leming Ge; Changhui Peng; Pengxiang Zhao; Xinyi Guo; Tong Li; Xiaojuan Shen; Qiuan Zhu; Weiguo Liu; Hua Wei; Meng Wang (Plant and Soil, 2020)

MiR-206 suppresses proliferation and epithelial-mesenchymal transition of renal cell carcinoma by inhibiting CDK6 expression - Zhen Guo; Haiyan Jia; Junke Ge (Human Cell, 2020)

The characteristics of oestrone mobility in water and soil by the addition of Ca-biochar and Fe–Mn-biochar derived from Litchi chinensis Sonn. - Huan-yu Tao; Hui Ge; Jianghong Shi; Xiaowei Liu; Wei Guo; Mengtao Zhang; Yaobin Meng; Xiao-yan Li (Environmental Geochemistry and Health, 2020)

Evaluation of the Benefits of Urban Water Resource Utilization Based on the Catastrophe and Emergy Methods - Meimei Wu; Wei Ge; Zening Wu; Xi Guo; Danyang Di; Shuoqiao Huang (Water Resources Management, 2020)

Evolution of genes and genomes in the genomics era - Song Ge; Ya-Long Guo (Science China Life Sciences, 2020)

Differentiation of human umbilical cord mesenchymal stem cells into Leydig-like cells with defined molecular compounds - Weiping Ji; Yong Chen; Long Wang; Zhangye Xu; Jahanzeb Ahmed; Renshan Ge; Maoping Chu; Xiaoling Guo (Human Cell, 2020)

Disruption of the lactate dehydrogenase and acetate kinase genes in Klebsiella pneumoniae HD79 to enhance 2,3-butanediol production, and related transcriptomics analysis - Jingping Ge; Jiawang Wang; Guangbin Ye; Shanshan Sun; Rui Guo; Gang Song; Wenxiang Ping (Biotechnology Letters, 2020)

Genomic and biological characterization of a pandemic norovirus variant GII.4 Sydney 2012 - Lili Ge; Xuhui Chen; Jinjin Liu; Lijun Zheng; Chongfen Chen; Shuying Luo; Pengbo Guo; Jinghui Kong; Yinsen Song; Yuqi Huo (Virus Genes, 2020)

Counting Kmers for Biological Sequences at Large Scale - Jianqiu Ge; Jintao Meng; Ning Guo; Yanjie Wei; Pavan Balaji; Shengzhong Feng (Interdisciplinary Sciences: Computational Life Sciences, 2020)

Effects of different 2A peptides on transgene expression mediated by tricistronic vectors in transfected CHO cells - Yan-mei Li; Meng Wang; Tian-yun Wang; Yong-ge Wei; Xiao Guo; Chun-liu Mi; Chun-peng Zhao; Xiang-xiang Cao; Yuan-yuan Dou (Molecular Biology Reports, 2020)

Chemical constituents of Curcuma kwangsiensis and their antimigratory activities in RKO cells - Ju-Tao Wang; Ding Ge; Hai-Fang Qu; Guo-Kai Wang; Gang Wang (Natural Product Research, 2019)

Bifidobacterium bifidum TMC3115 Can Characteristically Influence Glucose and Lipid Profile and Intestinal Microbiota in the Middle-Aged and Elderly - Ke Wang; Xiaohong Yu; Yi Li; Yun Guo; Lin Ge; Fangfang Pu; Xinying Ma; Wenjing Cui; Francesco Marrota; Fang He; Ming Li (Probiotics and Antimicrobial Proteins, 2019)

A specific assay for JmjC domain-containing lysine demethylase and its application to inhibitor screening - He Wen; Guo Li; Yongcan Chen; Meiting Li; Yafei Lv; Zhiming Li; Yinglu Li; Tianyun Hou; Hui Wang; Chaohua Liu; Xiaopeng Lu; Qian Zhu; et al. (Science China Life Sciences, 2019)

Multipath extraction and mitigation for high-rate multi-GNSS precise point positioning - Kai Zheng; Xiaohong Zhang; Pan Li; Xingxing Li; Maorong Ge; Fei Guo; Jizhang Sang; Harald Schuh (Journal of Geodesy, 2019)

Naringenin inhibits migration of breast cancer cells via inflammatory and apoptosis cell signaling pathways - Zhenjiang Zhao; Guoguo Jin; Yinghui Ge; Zhiping Guo (Inflammopharmacology, 2019)

Cloud Radiative Feedbacks during the ENSO Cycle Simulated by CAMS-CSM - Lin Chen; Lijuan Hua; Xinyao Rong; Jian Li; Lu Wang; Guo Zhang; Ming Sun; Zi’an Ge (Journal of Meteorological Research, 2019)

LncRNA NRON alleviates atrial fibrosis via promoting NFATc3 phosphorylation - Yapeng Wang; Peng Xu; Chengxin Zhang; Junbo Feng; Wenhui Gong; Shenglin Ge; Zhixiang Guo (Molecular and Cellular Biochemistry, 2019)

Multi-GNSS satellite clock estimation constrained with oscillator noise model in the existence of data discontinuity - Chuang Shi; Shiwei Guo; Shengfeng Gu; Xinhao Yang; Xiaopeng Gong; Zhiguo Deng; Maorong Ge; Harald Schuh (Journal of Geodesy, 2019)

Modelling and analysis of net primary productivity and its response mechanism to climate factors in temperate grassland, northern China - Fen Zhao; Bin Xu; Xiuchun Yang; Lang Xia; Yunxiang Jin; Jinya Li; Wenbo Zhang; Jian Guo; Ge Shen (International Journal of Remote Sensing, 2019)

Comparative study of remote sensing estimation methods for grassland fractional vegetation coverage – a grassland case study performed in Ili prefecture, Xinjiang, China - Wenbo Zhang; Xiuchun Yang; Asiya Manlike; Yunxiang Jin; Fengling Zheng; Jian Guo; Ge Shen; Yujing Zhang; Bin Xu (International Journal of Remote Sensing, 2019)

Remote sensing monitoring of green-up dates in the Xilingol grasslands of northern China and their correlations with meteorological factors - Jian Guo; Xiuchun Yang; Jianming Niu; Yunxiang Jin; Bin Xu; Ge Shen; Wenbo Zhang; Fen Zhao; Yujing Zhang (International Journal of Remote Sensing, 2019)

Evaluation of a traditional method for peak flow discharge estimation for floods in the Wenchuan Earthquake area, Sichuan Province, China - Xiao-jun Guo; Peng Cui; Yong Li; Jin-feng Liu; Yong-gang Ge; Ci-de Wang (Journal of Mountain Science, 2019)

Enrichment of cancer stem cells by agarose multi-well dishes and 3D spheroid culture - Xiaoling Guo; Yong Chen; Weiping Ji; Xianwu Chen; Chao Li; Renshan Ge (Cell and Tissue Research, 2019)

Oxymatrine attenuates brain hypoxic-ischemic injury from apoptosis and oxidative stress: role of p-Akt/GSK3β/HO-1/Nrf-2 signaling pathway - Xu-Hua Ge; Li Shao; Guo-Ji Zhu (Metabolic Brain Disease, 2018)

MiR-429 improved the hypoxia tolerance of human amniotic cells by targeting HIF-1α - Lihao Ge; Yuyan Wang; Yang Cao; Gang Li; Rui Sun; Peng Teng; Yansong Wang; Yunlong Bi; Zhanpeng Guo; Yajiang Yuan; Deshui Yu (Biotechnology Letters, 2018)

Flavobacterium zaozhuangense sp. nov., a new member of the family Flavobacteriaceae, isolated from metolachlor-contaminated soil - Qing Chen; Hong-Mei Wang; Wen Zhuang; Zhong-Guan Sun; Jing Chen; Yan Ge; Ji-guo Qiu; Jian He (Antonie van Leeuwenhoek, 2018)

Late Cretaceous basalts and rhyolites from Shimaoshan Group in eastern Fujian Province, SE China: age, petrogenesis, and tectonic implications - Xi-Yao Li; San-Zhong Li; Yan-Hui Suo; Li-Ming Dai; Ling-Li Guo; Feng-Jian Ge; Pei-Jun Lin (International Geology Review, 2018)

Multi-GNSS precise point positioning for precision agriculture - Jing Guo; Xingxing Li; Zhenhong Li; Leyin Hu; Guijun Yang; Chunjiang Zhao; David Fairbairn; David Watson; Maorong Ge (Precision Agriculture, 2018)

Silencing of miR156 confers enhanced resistance to brown planthopper in rice - Yafei Ge; Junyou Han; Guoxin Zhou; Yunmin Xu; Yue Ding; Min Shi; Changkui Guo; Gang Wu (Planta, 2018)

Dynamic monitoring the infrastructure of major ports in Sri Lanka by using multi-temporal high spatial resolution remote sensing images - Yong Ge; Yuehong Chen; Yuanxin Jia; Xian Guo; Shan Hu (Journal of Geographical Sciences, 2018)

Study on the Clinical Features and Prognosis of Penicilliosis marneffei Without Human Immunodeficiency Virus Infection - Ying-ge Wang; Jin-mei Cheng; Hai-bo Ding; Xi Lin; Guo-hao Chen; Mei Zhou; Sheng-nan Ye (Mycopathologia, 2018)

Genetic analysis of the fiber quality and yield traits in G. hirsutum background using chromosome segments substitution lines (CSSLs) from Gossypium barbadense - Lixue Guo; Yuzhen Shi; Juwu Gong; Aiying Liu; Yunna Tan; Wankui Gong; Junwen Li; Tingting Chen; Haihong Shang; Qun Ge; Quanwei Lu; Jie Sun; et al. (Euphytica, 2018)

Cloning and characterization of a specific UDP-glycosyltransferase gene induced by DON and Fusarium graminearum - Lanfei Zhao; Xin Ma; Peisen Su; Wenyang Ge; Hongyan Wu; Xiuxiu Guo; Anfei Li; Hongwei Wang; Lingrang Kong (Plant Cell Reports, 2018)

Inputs optimization to reduce the undesirable outputs by environmental hazards: a DEA model with data of PM2.5 in China - Xianhua Wu; Yufeng Chen; Ji Guo; Ge Gao (Natural Hazards, 2018)

Picroside II Exerts a Neuroprotective Effect by Inhibiting mPTP Permeability and EndoG Release after Cerebral Ischemia/Reperfusion Injury in Rats - Shan Li; Tingting Wang; Li Zhai; Keli Ge; Jun Zhao; Weihong Cong; Yunliang Guo (Journal of Molecular Neuroscience, 2018)

A WTLS-based rational function model for orthorectification of remote-sensing imagery - Yong Ge; Yongzhao Wei; Yongze Song; Tianjun Wu; Alfred Stein; Xian Guo; Chenghu Zhou; Jianghong Ma (International Journal of Remote Sensing, 2017)

The accumulation and fractionation of Rare Earth Elements in hydroponically grown Phytolacca americana L. - Ming Yuan; Mei-Na Guo; Wen-Shen Liu; Chang Liu; Antony van der Ent; Jean Louis Morel; Hermine Huot; Wan-Ying Zhao; Xian-Ge Wei; Rong-Liang Qiu; Ye-Tao Tang (Plant and Soil, 2017)

A rapid and efficient Agrobacterium-mediated transient gene expression system for strawberry leaves and the study of disease resistance proteins - Meng-Yuan Cui; Wei Wei; Kuan Gao; Yin-Ge Xie; Ye Guo; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Identification and genetic characterization of a novel circular single-stranded DNA virus in a human upper respiratory tract sample - Lunbiao Cui; Binyao Wu; Xiaojuan Zhu; Xiling Guo; Yiyue Ge; Kangchen Zhao; Xian Qi; Zhiyang Shi; Fengcai Zhu; Lixin Sun; Minghao Zhou (Archives of Virology, 2017)

Adiponectin Suppresses T Helper 17 Cell Differentiation and Limits Autoimmune CNS Inflammation via the SIRT1/PPARγ/RORγt Pathway - Kai Zhang; Yawei Guo; Zhenzhen Ge; Zhihui Zhang; Yurong Da; Wen Li; Zimu Zhang; Zhenyi Xue; Yan Li; Yinghui Ren; Long Jia; Koon-Ho Chan; et al. (Molecular Neurobiology, 2017)

Species abundance distribution and ecological niches of chigger mites on small mammals in Yunnan province, southwest China - Pei-Ying Peng; Xian-Guo Guo; Dao-Chao Jin; Wen-Ge Dong; Ti-Jun Qian; Feng Qin; Zhi-Hua Yang (Biologia, 2017)

Effect of elevated CO2 and O3 on phytohormone-mediated plant resistance to vector insects and insect-borne plant viruses - Honggang Guo; Shifan Wan; Feng Ge (Science China Life Sciences, 2017)

Autophagy promotes apoptosis induction through repressed nitric oxide generation in the treatment of human breast cancer MCF-7 cells with L-A03, a dihydroartemisinin derivative - Guodong Yao; Hao Chen; Ling Chen; Mengyao Ge; Jing Yang; Weiwei Liu; Mingyu Xia; Toshihiko Hayashi; Chun Guo; Takashi Ikejima (Medicinal Chemistry Research, 2017)

The emergence of the hyperinvasive vine, Mikania micrantha (Asteraceae), via admixture and founder events inferred from population transcriptomics - Ming Yang; Ziwen He; Yelin Huang; Lu Lu; Yubin Yan; Lan Hong; Hao Shen; Ying Liu; Qiang Guo; Lu Jiang; Yanwu Zhang; Anthony J. Greenberg; et al. (Molecular Ecology, 2017)
Biological invasions that involve well‐documented rapid adaptations to new environments provide unequalled opportunities for testing evolutionary hypotheses. Mikania micrantha Kunth (Asteraceae), a perennial herbaceous vine native to tropical Central and South America, successfully invaded tropical Asia in the early 20th century. It is regarded as one of the most aggressive weeds in the world. To elucidate the molecular and evolutionary processes underlying this invasion, we extensively sampled this weed throughout its invaded range in South‐East and South Asia and surveyed its genetic structure using variants detected from population transcriptomics. Clustering results suggest that more than one source population contributed to this invasion. Computer simulations using genomewide genetic variation support a scenario of admixture and founder events during invasion. The genes differentially expressed between native and invasive populations were found to be involved in oxidative and high light intensity stress responses, pointing to a possible ecological mechanism of adaptation. Our results provide a foundation for further detailed mechanistic and population studies of this ecologically and economically important invasion. This line of research promises to provide new mitigation strategies for invasive species as well as insights into mechanisms of adaptation.

A reliability analysis method for rock slope controlled by weak structural surface - Jia-wen Zhou; Ming-yuan Jiao; Hui-ge Xing; Xing-guo Yang; Yu-chuan Yang (Geosciences Journal, 2017)

Identification and characterization of a phospholipase A1 activity type three secreted protein, PP _ExoU from Pseudomonas plecoglossicida NB 2011, the causative agent of visceral granulomas disease in large yellow croaker ( Larimichthys crocea ) - J Zhang; Y Wang; H Guo; Z Mao; C Ge (Journal of Fish Diseases, 2017)
Pseudomonas plecoglossicida NB 2011 , the causative agent of visceral granulomas disease in farmed Larimichthys crocea in China, encodes a predicted type three effector PP _ExoU, a homolog of the cytotoxin ExoU of Pseudomonas aeruginosa . In this study, secretion of PP _ExoU was tested in various broth, the protein was expressed with the pET 30a prokaryotic system, the phospholipase A ( PLA ) activity of the recombinant protein was determined with fluorogenic phospholipid substrates, fusion expression with green fluorescent protein in transfected HeLa cells was investigated, and the lactate dehydrogenase ( LDH ) level was measured. The results showed the protein was type three secreted in several media; the recombinant protein displayed significant PLA 1 activity with ubiquitin. Fluorescence was observed on the cell membrane and scattered in the cytoplasm of HeLa cells expressing catalytic wild‐type PP _ExoU, blebbing and stretching developed in the cell membranes indicating of membrane damage. Fluorescence scattered in the cytoplasm of cells expressing the catalytic inactive protein. A significant LDH level was detected in HeLa cells expressing wild‐type PP _exoU, but not in the Ser/Asp‐mutated protein, suggestion mutation of predicted catalytic residues abolished the PLA activity. This is the first report on the function of a secreted type three protein from P. plecoglossicida .

Baseline antibody level may help predict the risk of active human cytomegalovirus infection in a HCMV seropositive population - T.-d. Li; J.-j. Li; X. Huang; H. Wang; X.-y. Guo; S.-x. Ge; J. Zhang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Functional effector memory T cells contribute to protection from superinfection with heterologous simian immunodeficiency virus or simian-human immunodeficiency virus isolates in Chinese rhesus macaques - Ming Sun; Huiwen Zheng; Yingpeng Xie; Bingxiang Li; Haiting Long; Ge Guo; Lei Guo; Jingjing Wang; Ruotong Ning; Yue Li; Longding Liu (Archives of Virology, 2017)

Neutrophil-To-Lymphocyte Ratio Predicts 3-Month Outcome of Acute Ischemic Stroke - Sen Qun; Yan Tang; Jing Sun; Zhaoxia Liu; Juncang Wu; Ji Zhang; Jidong Guo; Zhiqiang Xu; Dan Zhang; Zhengxu Chen; Fuyong Hu; Xingshun Xu; et al. (Neurotoxicity Research, 2017)

Neuregulin1β Effects on Brain Tissue via ERK5-Dependent MAPK Pathway in a Rat Model of Cerebral Ischemia–Reperfusion Injury - Ning Gu; Keli Ge; Cui Hao; Yaqing Ji; Hongyun Li; Yunliang Guo (Journal of Molecular Neuroscience, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Root nematode infection enhances leaf defense against whitefly in tomato - Honggang Guo; Feng Ge (Arthropod-Plant Interactions, 2017)

Establishment of the South Asian high over the Indo-China Peninsula during late spring to summer - Lijuan Wang; Aiguo Dai; Shuaihong Guo; Jing Ge (Advances in Atmospheric Sciences, 2017)

Rapid identification of QTLs underlying resistance to Cucumber mosaic virus in pepper (Capsicum frutescens) - Guangjun Guo; Shubin Wang; Jinbing Liu; Baogui Pan; Weiping Diao; Wei Ge; Changzhou Gao; John C. Snyder (Theoretical and Applied Genetics, 2017)

Signal sampling for efficient sparse representation of resting state FMRI data - Bao Ge; Milad Makkie; Jin Wang; Shijie Zhao; Xi Jiang; Xiang Li; Jinglei Lv; Shu Zhang; Wei Zhang; Junwei Han; Lei Guo; Tianming Liu (Brain Imaging and Behavior, 2016)

Trace projection transformation: a new method for measurement of debris flow surface velocity fields - Yan Yan; Peng Cui; Xiaojun Guo; Yonggang Ge (Frontiers of Earth Science, 2016)

Illicit drugs and their metabolites in 36 rivers that drain into the Bohai Sea and north Yellow Sea, north China - De-Gao Wang; Qiu-Da Zheng; Xiao-Ping Wang; Juan Du; Chong-Guo Tian; Zhuang Wang; Lin-Ke Ge (Environmental Science and Pollution Research, 2016)

Urban flood depth-economic loss curves and their amendment based on resilience: evidence from Lizhong Town in Lixia River and Houbai Town in Jurong River of China - Xianhua Wu; Lei Zhou; Ge Gao; Ji Guo; Zhonghui Ji (Natural Hazards, 2016)

Anti-inflammatory and blood stasis activities of essential oil extracted from Artemisia argyi leaf in animals - Yue-bin Ge; Zhi-gang Wang; Ying Xiong; Xian-ju Huang; Zhi-nan Mei; Zong-guo Hong (Journal of Natural Medicines, 2016)

Improved tilt-depth method for fast estimation of top and bottom depths of magnetic bodies - Yan-Guo Wang; Jin Zhang; Kun-Peng Ge; Xiao Chen; Feng-Jun Nie (Applied Geophysics, 2016)

Petrogenesis of Early Cretaceous volcanic rocks of the Manketouebo Formation in the Wuchagou region, central Great Xing’an Range, NE China, and tectonic implications: geochronological, geochemical, and Hf isotopic evidence - Zheng Ji; Wen-Chun Ge; Qing-Hai Wang; Hao Yang; Guo-Chun Zhao; Jun-Hui Bi; Yu Dong (International Geology Review, 2016)

Molecular cloning, expression, and stress response of the estrogen-related receptor gene (AccERR) from Apis cerana cerana - Weixing Zhang; Ming Zhu; Ge Zhang; Feng Liu; Hongfang Wang; Xingqi Guo; Baohua Xu (The Science of Nature, 2016)

Effect of La(NO3)3 and Ce(NO3)3 on shoot induction and seedling growth of in vitro cultured anoectochilus roxburghii - Yingya Xu; Guifang Zhang; Yan Wang; Ge Guo (Journal of Plant Biology, 2016)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Premature breakdown of tapetum associated with reverse thermo-sensitive genic male-sterile line Huiyou50S in rapeseed (Brassica napus) - Chengyu Yu; Xianfeng Xu; Juan Ge; Yingfen Guo; Jungang Dong; Zhensheng Dong (Acta Physiologiae Plantarum, 2016)

MicroRNA-9 regulates osteoblast differentiation and angiogenesis via the AMPK signaling pathway - Jining Qu; Daigang Lu; Hua Guo; Wusheng Miao; Ge Wu; Meifen Zhou (Molecular and Cellular Biochemistry, 2016)

Isolation and characterization of twenty-two polymorphic microsatellite markers from Gardenia jasminoides (Rubiaceae) - YAN-QIN XU; GUO-YAN WEI; YIN ZHOU; FEI GE; GUANG-MING LUO (Journal of Genetics, 2015)

Passive-source multitaper-spectral method based low-frequency data reconstruction for active seismic sources - Pan Zhang; Li-Guo Han; Yan Zhou; Zhuo Xu; Qi-Xin Ge (Applied Geophysics, 2015)

Characterization of a new temperature-sensitive male sterile line SP2S in rapeseed (Brassica napus L.) - Chengyu Yu; Yingfen Guo; Juan Ge; Yumei Hu; Jungang Dong; Zhensheng Dong (Euphytica, 2015)

Prestack forward modeling of tight reservoirs based on the Xu–White model - Chao Zhu; Qing-Xin Guo; Qing-Shun Gong; Zhan-Guo Liu; Sen-Ming Li; Ge-Ping Huang (Applied Geophysics, 2015)

Cerebral lipiodol embolism following abdomen trauma in a patient with hepatocellular carcinoma treated with transcatheter arterial chemoembolization - Quanmin Nie; Hao Wu; Pin Guo; Jianwei Ge; Yongming Qiu (Acta Neurologica Belgica, 2015)

Molecular phylogeny and the underestimated species diversity of the endemic white‐bellied rat (Rodentia: Muridae: Niviventer ) in Southeast Asia and China - Liang Lu; Deyan Ge; Douglas Chesters; Simon Y. W. Ho; Ying Ma; Guichang Li; Zhixin Wen; Yongjie Wu; Jun Wang; Lin Xia; Jingli Liu; Tianyu Guo; et al. (Zoologica Scripta, 2015)
The white‐bellied rat, Niviventer , is a genus endemic to Southeast Asia and China. However, the interspecific phylogenetic relationships and species diversity of this genus remain poorly understood. In the present study, single and multi‐locus analyses were performed. Phylogenetic reconstruction on Cytochrome b (512 individuals, including data from Genbank) revealed five major clades with approximately 35 operational taxonomic units ( OTU s), a number twice the existing taxonomy. The first clade ( N . langbianis species group) was the earliest diverged. The second clade ( N. fulvescens species group) diverged in Southeast Asia, the south and lower altitude regions of the Hengduan Mountains, and Southeast China. The third clade (the N. eha species group) is endemic to high altitudes in Northwest Yunnan and the central region of Himalaya. The fourth clade (the N. andersoni species group), is mainly confined to alpine regions of the Hengduan Mountains. The fifth clade ( N . confucianus species group) is mainly distributed in the north and higher altitude regions of eastern Himalaya, the Hengduan Mountains and Taiwan, with the complex also invading central and northern China. Results from the combined dataset of four genes (Cytochrome b, Cytochrome oxidase subunit I, the D‐loop sequence of the mitochondrial genome and the first exon of the nuclear interphotoreceptor retinoid binding protein) for 82 representative individuals from China generally coincide with the result of the single gene, with 12 OTU s identified. These results provide a preliminary framework for the existing classification of this highly diversified genus. The divergence time of Niviventer based on the four gene topology was dated to the late Miocene ~6.41 Ma. Significant differences were detected in the general body form changes among these units based on voucher specimens. Moreover, geometric morphometric analysis of the cranium shape of voucher specimens indicated significant differences among five major species groups. Shape divergence of the cranium among several OTU s within the N. confucinaus complex is also significant. Our results provide further evidence for rapid and highly underestimated diversification of Niviventer both in genetics and morphology.

Plant stomatal closure improves aphid feeding under elevated CO 2 - Yucheng Sun; Huijuan Guo; Liang Yuan; Jianing Wei; Wenhao Zhang; Feng Ge (Global Change Biology, 2015)
Stomata help plants regulate CO 2 absorption and water vapor release in response to various environmental changes, and plants decrease their stomatal apertures and enhance their water status under elevated CO 2 . Although the bottom‐up effect of elevated CO 2 on insect performance has been extensively studied, few reports have considered how insect fitness is altered by elevated CO 2 ‐induced changes in host plant water status. We tested the hypothesis that aphids induce stomatal closure and increase host water potential, which facilitates their passive feeding, and that this induction can be enhanced by elevated CO 2 . Our results showed that aphid infestation triggered the abscisic acid ( ABA ) signaling pathway to decrease the stomatal apertures of Medicago truncatula , which consequently decreased leaf transpiration and helped maintain leaf water potential. These effects increased xylem‐feeding time and decreased hemolymph osmolarity, which thereby enhanced phloem‐feeding time and increased aphid abundance. Furthermore, elevated CO 2 up‐regulated an ABA ‐independent enzyme, carbonic anhydrase, which led to further decrease in stomatal aperture for aphid‐infested plants. Thus, the effects of elevated CO 2 and aphid infestation on stomatal closure synergistically improved the water status of the host plant. The results indicate that aphid infestation enhances aphid feeding under ambient CO 2 and that this enhancement is increased under elevated CO 2 .

Stromal cell-derived factor 1 (SDF-1) accelerated skin wound healing by promoting the migration and proliferation of epidermal stem cells - Rui Guo; Linlin Chai; Liang Chen; Wenguang Chen; Liangpeng Ge; Xiaoge Li; Hongli Li; Shirong Li; Chuan Cao (In Vitro Cellular & Developmental Biology - Animal, 2015)

Characterisation of novel linear antigen epitopes on North American-type porcine reproductive and respiratory syndrome virus M protein - Qian Wang; Jiazeng Chen; Jinmei Peng; Tongqing An; Chaoliang Leng; Yan Sun; Xin Guo; Xinna Ge; Zhijun Tian; Hanchun Yang (Archives of Virology, 2014)

Improved zinc tolerance of tobacco by transgenic expression of an allene oxide synthase gene from hexaploid wheat - Huai-Hua Liu; Yuan-Ge Wang; Shu-Ping Wang; Hong-Jie Li; Qing-Guo Xin (Acta Physiologiae Plantarum, 2014)

Assessment of the Excavation-Damaged Zone in a Tall Rock Slope Using Acoustic Testing Method - Jia-wen Zhou; Xing-guo Yang; Hui-ge Xing; Yu-feng Xue; Gang He (Geotechnical and Geological Engineering, 2014)

Genistein Alleviates Radiation-Induced Pneumonitis by Depressing Ape1/Ref-1 Expression to Down-regulate Inflammatory Cytokines - Guo-Dong Liu; Lei Xia; Jian-Wu Zhu; Shan Ou; Meng-Xia Li; Yong He; Wei Luo; Juan Li; Qian Zhou; Xue-Qin Yang; Jin-Lu Shan; Ge Wang; et al. (Cell Biochemistry and Biophysics, 2014)

Serum differential protein identification of Xinjiang Kazakh esophageal cancer patients based on the two-dimensional liquid-phase chromatography and LTQ MS - Cui Li; Guo Xia; Zhang Jianqing; Yang Mei; Bai Ge; Zhang Li (Molecular Biology Reports, 2014)

Elevation‐induced climate change as a dominant factor causing the late Miocene C 4 plant expansion in the Himalayan foreland - Haibin Wu; Zhengtang Guo; Joël Guiot; Christine Hatté; Changhui Peng; Yanyan Yu; Junyi Ge; Qin Li; Aizhi Sun; Deai Zhao (Global Change Biology, 2014)
During the late Miocene, a dramatic global expansion of C 4 plant distribution occurred with broad spatial and temporal variations. Although the event is well documented, whether subsequent expansions were caused by a decreased atmospheric CO 2 concentration or climate change is a contentious issue. In this study, we used an improved inverse vegetation modeling approach that accounts for the physiological responses of C 3 and C 4 plants to quantitatively reconstruct the paleoclimate in the Siwalik of Nepal based on pollen and carbon isotope data. We also studied the sensitivity of the C 3 and C 4 plants to changes in the climate and the atmospheric CO 2 concentration. We suggest that the expansion of the C 4 plant distribution during the late Miocene may have been primarily triggered by regional aridification and temperature increases. The expansion was unlikely caused by reduced CO 2 levels alone. Our findings suggest that this abrupt ecological shift mainly resulted from climate changes related to the decreased elevation of the Himalayan foreland.

The comparison of sensitivity of motion sickness between retinal degeneration fast mice and normal mice - Xiao-Cheng Wang; Zhao-Hui Shi; Ka Bian; Lei Zhang; Jun-Hui Xue; Guo-Qing Yang; Xue-Song Ge; Zuo-Ming Zhang (Journal of Comparative Physiology A, 2014)

Exposure to diethylhexyl phthalate (DEHP) results in a heritable modification of imprint genes DNA methylation in mouse oocytes - Lan Li; Teng Zhang; Xun-Si Qin; Wei Ge; Hua-Gang Ma; Li-Lan Sun; Zhu-Mei Hou; Hong Chen; Ping Chen; Guo-Qing Qin; Wei Shen; Xi-Feng Zhang (Molecular Biology Reports, 2014)

Molecular and biochemical characterization of Sclerotinia sclerotiorum laboratory mutants resistant to dicarboximide and phenylpyrrole fungicides - Ya-Bing Duan; Chang-Yan Ge; Ming-Guo Zhou (Journal of Pest Science, 2014)

Clinical and laboratory characteristics of patients having amyloidogenic transthyretin deposition in osteoarthritic knee joints - Ya-Jun Gu; Peng Ge; Yun Mu; Jin-Hai Lu; Fang Zheng; Xu-Guo Sun (Journal of Zhejiang University-SCIENCE B, 2014)

Differential expression of VGLUT1 or VGLUT2 in the trigeminothalamic or trigeminocerebellar projection neurons in the rat - Shun-Nan Ge; Zhi-Hong Li; Jun Tang; Yunfei Ma; Hiroyuki Hioki; Ting Zhang; Ya-Cheng Lu; Fu-Xing Zhang; Noboru Mizuno; Takeshi Kaneko; Ying-Ying Liu; Mandy Siu Yu Lung; et al. (Brain Structure and Function, 2014)

Xenon-enhanced CT assessment of cerebral blood flow in stroke-in-progress patients with unilateral internal carotid artery or middle cerebral artery stenosis - Zhen-Ni Guo; Ge Yang; Hong-Wei Zhou; Jing Wang; Jiang Wu; Yi Yang (Neuroscience Bulletin, 2013)

Isolation and characterization of fifteen polymorphic tetranucleotide microsatellite loci in Schizopygopsis younghusbandi Regan - Huan Zheng; Gui-Rong Zhang; Shan-Shan Guo; Kai-Jian Wei; Cong-Xin Xie; Tai-Ming Ge (Conservation Genetics Resources, 2013)

Acrylamide biodegradation ability and plant growth-promoting properties of Variovorax boronicumulans CGMCC 4969 - Zhong-Hua Liu; Yu-Min Cao; Qian-Wen Zhou; Kun Guo; Feng Ge; Jun-Yi Hou; Si-Yi Hu; Sheng Yuan; Yi-Jun Dai (Biodegradation, 2013)

Molecular basis for insecticide‐enhanced thermotolerance in the brown planthopper N ilaparvata lugens S tål ( H emiptera: D elphacidae) - Lin‐Quan Ge; Liu‐Juan Huang; Guo‐Qin Yang; Qi‐Sheng Song; David Stanley; G. M. Gurr; Jin‐Cai Wu (Molecular Ecology, 2013)
Climate change is likely to have marked ecological effects on terrestrial ecosystems, including the activities of insect pests. Most attention has focused on the increasing geographical ranges of pests; however, if extrinsic factors enhance their thermotolerance, populations may express increased voltinism and longer daily and annual activity periods. These changes in pest populations have the potential for severe consequences, including increased crop losses and decreased food security at the global level. The brown planthopper ( BPH ) Nilaparvata lugens Stål (Hemiptera: Delphacidae) is a serious pest of rice crops in temperate and tropical regions of Asia. It is often present in rice microclimates at temperatures close to its maximum thermotolerance. Recent BPH outbreaks in tropical Asia are considered to be associated with excess use of pesticides and increasing temperature. This study tested whether exposure to sublethal concentrations of triazophos (tzp), an insecticide widely used in Asian rice production, enhances thermotolerance of BPH . Tzp exposure (40 ppm at 40 °C) significantly decreased mortality (from 94% in controls to 50% at 48 h post‐treatment) and increased lethal mean time ( LT 50 ) of adults by 17.2 h. To investigate the underlying molecular mechanism of this tzp‐enhanced thermotolerance, we selected Hsp70 and Arginine kinase (Argk) for detailed study. Transcripts encoding both proteins in third‐instar nymphs and brachypterous adult females were up‐regulated, compared with controls, after exposure to tzp. RNA i silencing of both genes demonstrated that Hsp70 and Argk are essential for survival and tzp‐increased thermotolerance. We propose that tzp induces thermotolerance in BPH s by increasing the expression of genes that act in cell protection mechanisms. The significance of our proposal relates to the importance of understanding the influence of sublethal concentrations of insecticides on pest biology. In addition to its influence on thermotolerance, tzp also enhances BPH reproduction. We infer that exposure to a pesticide stressor can produce cross‐tolerance, that is, increased tolerance to one stressor also increases tolerance to other stressors, including temperature. Aside from needing a better understanding of these effects in nature and in other pest/cropping systems, we suggest that pest management programmes can be improved with better understanding of the influences of stressors, including increased environmental temperatures and sublethal concentrations of insecticides, on pest biology.

Pea aphid promotes amino acid metabolism both in M edicago truncatula and bacteriocytes to favor aphid population growth under elevated CO 2 - Huijuan Guo; Yucheng Sun; Yuefei Li; Bin Tong; Marvin Harris; Keyan Zhu‐Salzman; Feng Ge (Global Change Biology, 2013)
Rising atmospheric CO 2 levels can dilute the nitrogen ( N ) resource in plant tissue, which is disadvantageous to many herbivorous insects. Aphids appear to be an exception that warrants further study. The effects of elevated CO 2 (750 ppm vs. 390 ppm) were evaluated on N assimilation and transamination by two M edicago truncatula genotypes, a N‐fixing‐deficient mutant ( dnf1 ) and its wild‐type control (Jemalong), with and without pea aphid ( Acyrthosiphon pisum ) infestation. Elevated CO 2 increased population abundance and feeding efficiency of aphids fed on Jemalong, but reduced those on dnf1 . Without aphid infestation, elevated CO 2 increased photosynthetic rate, chlorophyll content, nodule number, biomass, and pod number for Jemalong, but only increased pod number and chlorophyll content for dnf1 . Furthermore, aphid infested Jemalong plants had enhanced activities of N assimilation‐related enzymes (glutamine synthetase, Glutamate synthase) and transamination‐related enzymes (glutamate oxalate transaminase, glutamine phenylpyruvate transaminase), which presumably increased amino acid concentration in leaves and phloem sap under elevated CO 2 . In contrast, aphid infested dnf1 plants had decreased activities of N assimilation‐related enzymes and transmination‐related enzymes and amino acid concentrations under elevated CO 2 . Furthermore, elevated CO 2 up‐regulated expression of genes relevant to amino acid metabolism in bacteriocytes of aphids associated with Jemalong, but down‐regulated those associated with dnf1 . Our results suggest that pea aphids actively elicit host responses that promote amino acid metabolism in both the host plant and in its bacteriocytes to favor the population growth of the aphid under elevated CO 2 .

Efficient Fluorescent Recognition of Carboxylates in Aqueous Media Using Facilely Electrosynthesized Poly(9-Aminofluorene) - Ge Zhang; Yangping Wen; Yuzhen Li; Jingkun Xu; Chaoqun Guo; Baoyang Lu; Danhua Zhu (Journal of Fluorescence, 2013)

Overexpression of a Malus xiaojinensis Nas1 Gene Influences Flower Development and Tolerance to Iron Stress in Transgenic Tobacco - De-Guo Han; Guo-Hui Yang; Ke-Dong Xu; Qin Shao; Ze-Yuan Yu; Bing Wang; Qiu-Lai Ge; Yang Yu (Plant Molecular Biology Reporter, 2013)

Investigation on pretreatment of centrifugal mother liquid produced in the production of polyvinyl chloride by air-Fenton technique - Yingying Sun; Xiuyi Hua; Rui Ge; Aitong Guo; Zhiyong Guo; Deming Dong; Wentian Sun (Environmental Science and Pollution Research, 2013)

Different mechanisms lead to convergence of reproductive strategies in two lacertid lizards (Takydromus wolteri and Eremias argus) - Bao-Jun Sun; Shu-Ran Li; Xue-Feng Xu; Wen-Ge Zhao; Lai-Gao Luo; Xiang Ji; Wei-Guo Du (Oecologia, 2013)

The rice OsDIL gene plays a role in drought tolerance at vegetative and reproductive stages - Changkui Guo; Xiaochun Ge; Hong Ma (Plant Molecular Biology, 2013)

Selection and validation of suitable reference genes for mRNA qRT-PCR analysis using somatic embryogenic cultures, floral and vegetative tissues in citrus - Zheng Liu; Xiao-Xia Ge; Xiao-Meng Wu; Shu-Jun Kou; Li-Jun Chai; Wen-Wu Guo (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

HIF-1α up-regulates NDRG1 expression through binding to NDRG1 promoter, leading to proliferation of lung cancer A549 cells - Qiang Wang; Li-Hong Li; Guo-Dong Gao; Gang Wang; Liang Qu; Jin-Ge Li; Chun-Mei Wang (Molecular Biology Reports, 2013)

Characteristics, causes and mitigation of catastrophic debris flow hazard on 21 July 2011 at the Longda Watershed of Songpan County, China - Yong-gang Ge; Peng Cui; Xiao-jun Guo; Guo-hu Song; Wei-ming Liu (Journal of Mountain Science, 2013)

Phylogenetic analysis of porcine epidemic diarrhea virus field strains prevailing recently in China - Yueyi Gao; Qiuwen Kou; Xinna Ge; Lei Zhou; Xin Guo; Hanchun Yang (Archives of Virology, 2013)

Pathways and Organisms Involved in Ammonia Oxidation and Nitrous Oxide Emission - Jianhua Guo; Yongzhen Peng; Shuying Wang; Bin Ma; Shijian Ge; Zhongwei Wang; Huijun Huang; Jingrong Zhang; Liang Zhang (Critical Reviews in Environmental Science and Technology, 2013)

Resting State fMRI-guided Fiber Clustering: Methods and Applications - Bao Ge; Lei Guo; Tuo Zhang; Xintao Hu; Junwei Han; Tianming Liu (Neuroinformatics, 2013)

De-novo characterization of the soft-shelled turtle Pelodiscus sinensis transcriptome using Illumina RNA-Seq technology - Wei Wang; Cai-yan Li; Chu-tian Ge; Lei Lei; You-ling Gao; Guo-ying Qian (Journal of Zhejiang University-SCIENCE B, 2013)

Compromised cerebrovascular modulation in chronic anxiety: evidence from cerebral blood flow velocity measured by transcranial Doppler sonography - Hong-Liang Zhang; Zhen-Ni Guo; Ge Yang; Le Yang; Ke Han; Jiang Wu; Yingqi Xing; Yi Yang (Neuroscience Bulletin, 2012)

Expressed sequence tag analysis and cloning of trehalose-6-phosphate synthase gene from marine alga Laminaria japonica (Phaeophyta) - Jinsong Xuan; Yanbin Feng; Manli Weng; Ge Zhao; Jinfeng Shi; Jianting Yao; Xiuliang Wang; Baotai Guo; Lixian Qiao; Delin Duan; Bin Wang (Acta Oceanologica Sinica, 2012)

Transcriptional profiling of genes involved in embryogenic, non-embryogenic calluses and somatic embryogenesis of Valencia sweet orange by SSH-based microarray - Xiao-Xia Ge; Li-Jun Chai; Zheng Liu; Xiao-Meng Wu; Xiu-Xin Deng; Wen-Wu Guo (Planta, 2012)

Consistent isomiR expression patterns and 3′ addition events in miRNA gene clusters and families implicate functional and evolutionary relationships - Li Guo; Hailing Li; Tingming Liang; Jiafeng Lu; Qi Yang; Qinyu Ge; Zuhong Lu (Molecular Biology Reports, 2012)

PDGF-AA Mediates B104CM-Induced Oligodendrocyte Precursor Cell Differentiation of Embryonic Neural Stem Cells Through Erk, PI3K, and p38 Signaling - Jian-Guo Hu; Yan-Xia Wang; Hong-Ju Wang; Ming-Sheng Bao; Zhen-Huan Wang; Xin Ge; Feng-Chao Wang; Jian-Sheng Zhou; He-Zuo Lü (Journal of Molecular Neuroscience, 2012)

Seroprevalence of porcine cytomegalovirus and sapovirus infection in pigs in Hunan province, China - Guo-Hua Liu; Run-Cheng Li; Jing Li; Ze-Bin Huang; Chao-Ting Xiao; Wei Luo; Meng Ge; Da-Liang Jiang; Xing-Long Yu (Archives of Virology, 2012)

Biomechanism of adhesion in gecko setae - Ce Guo; JiuRong Sun; YingBin Ge; WenBo Wang; DaPeng Wang; ZhenDong Dai (Science China Life Sciences, 2012)

Tracking miRNA precursor metabolic products and processing sites through completely analyzing high-throughput sequencing data - Li Guo; Hailing Li; Jiafeng Lu; Qi Yang; Qinyu Ge; Wanjun Gu; Yunfei Bai; Zuhong Lu (Molecular Biology Reports, 2012)

Late Mesozoic rift evolution and crustal extension in the central Songliao Basin, northeastern China: constraints from cross-section restoration and implications for lithospheric thinning - Rongfeng Ge; Qinglong Zhang; Liangshu Wang; Juan Chen; Guo'ai Xie; Xiyong Wang (International Geology Review, 2012)

First Isolation of Candida dubliniensis from Oral Cavities of Dermatological Patients in Nanjing, China - Yi P. Ge; Guo X. He; Tong Lin; Gui X. Lu; Yong N. Shen; Wei D. Liu (Mycopathologia, 2011)

Impact of long-range transport and under-cloud scavenging on precipitation chemistry in East China - Yuhua Li; Yan Wang; Aijun Ding; Xiaohuan Liu; Jia Guo; Penghui Li; Minghu Sun; Fuling Ge; Wenxing Wang (Environmental Science and Pollution Research, 2011)

Antiviral activity and possible mechanisms of action of pentagalloylglucose (PGG) against influenza A virus - Ge Liu; Sheng Xiong; Yang-Fei Xiang; Chao-Wan Guo; Feng Ge; Chong-Ren Yang; Ying-Jun Zhang; Yi-Fei Wang; Kaio Kitazato (Archives of Virology, 2011)

Alteration of encephalomyocarditis virus pathogenicity due to a mutation at position 100 of VP1 - Shu Zhu; XinNa Ge; XiaoWen Gong; Xin Guo; YanHong Chen; HanChun Yang (Science China Life Sciences, 2011)

Effects of baicalein on Sendai virus in vivo are linked to serum baicalin and its inhibition of hemagglutinin-neuraminidase - Jie Dou; Lili Chen; Ge Xu; Lei Zhang; Huimin Zhou; Hui Wang; Zhenzhen Su; Mengyun Ke; Qinglong Guo; Changlin Zhou (Archives of Virology, 2011)

Two new compounds from Semen celosiae and their protective effects against CCl 4 -induced hepatotoxicity - Qian Xue; Zhen-Liang Sun; Mei-Li Guo; Ying Wang; Ge Zhang; Xiao-Kang Wang (Natural Product Research, 2011)

Analysis on the interaction between IL-1F7 gene and environmental factors on patients with ankylosing spondylitis: a case-only study - Rui Ge; Faming Pan; Fangfang Liao; Guo Xia; Yang Mei; Beibei Shen; Tianchen Zhang; Jing Gao; Li Zhang; Zhenhua Duan; Shengqian Xu; Jianhua Xu (Molecular Biology Reports, 2011)

Stage and tissue-specific modulation of ten conserved miRNAs and their targets during somatic embryogenesis of Valencia sweet orange - Xiao-Meng Wu; Mei-Ya Liu; Xiao-Xia Ge; Qiang Xu; Wen-Wu Guo (Planta, 2011)

Characterization of a late gene, ORF75 from Bombyx mori nucleopolyhedrovirus - Jun-Qing Ge; Guo-Hui Gao; Yi-Peng Xu; Chuan-Xi Zhang (Molecular Biology Reports, 2011)

Expression and identification of a thermostable malate dehydrogenase from multicellular prokaryote Streptomyces avermitilis MA-4680 - Zong-Da Wang; Bao-Juan Wang; Ya-Dong Ge; Wei Pan; Jie Wang; Lei Xu; Ai-Min Liu; Guo-Ping Zhu (Molecular Biology Reports, 2011)

A FVCOM-based unstructured grid wave, current, sediment transport model, I. Model description and validation - Lunyu Wu; Changsheng Chen; Peifang Guo; Maochong Shi; Jianhua Qi; Jianzhong Ge (Journal of Ocean University of China, 2011)

Weight-reducing effect of Acer truncatum Bunge may be related to the inhibition of fatty acid synthase - Wen-Hua Zhao; Li-Fang Gao; Wen Gao; Yong-Sheng Yuan; Chun-Chun Gao; Li-Ge Cao; Zi-Zheng Hu; Jian-Qiang Guo; Ying-Xia Zhang (Natural Product Research, 2011)

Thick Miocene eolian deposits on the Huajialing Mountains: The geomorphic evolution of the western Loess Plateau - Tao Zhan; ZhengTang Guo; HaiBin Wu; JunYi Ge; Xin Zhou; ChunLin Wu; FangMing Zeng (Science China Earth Sciences, 2011)

Cloning, molecular characterization and expression analysis of a SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASE gene (CitSERK1-like) in Valencia sweet orange - Xiao-Xia Ge; Gai-En Fan; Li-Jun Chai; Wen-Wu Guo (Acta Physiologiae Plantarum, 2010)

Probability assessment of river blocking by debris flow associated with the Wenchuan Earthquake - Jian-Qi Zhuang; Peng Cui; Yong-Gang Ge; Yi-Ping He; Ying-Hui Liu; Xiao-Jun Guo (International Journal of Remote Sensing, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

In vitro synergistic activity between 8-methoxypsoralen and ethambutol, isoniazid, and rifampin when used in combination against Mycobacterium tuberculosis - Fa Ge; Fanli Zeng; Na Guo; Junwen Fan; Yu Song; Siguo Liu; Xiuping Wu; Xuelin Wang; Xuming Deng; Qi Jin; Lu Yu (World Journal of Microbiology and Biotechnology, 2010)

Detecting relationships between amylose content and amino acid contents of indica rice with conditional approach - Chun Hai Shi; Qiong Qiong Zhu; Ke Ming Wang; Guo Ke Ge; Jian Guo Wu; Zhen Ghao Xu (Journal of Genetics, 2010)

Sanchi ginseng (Panax notoginseng (Burkill) F. H. Chen) in China: distribution, cultivation and variations - Hong Bo Guo; Xiu Ming Cui; Na An; Ge Ping Cai (Genetic Resources and Crop Evolution, 2010)

No significant association between Fc receptor-like 3 gene polymorphisms and human leukocyte antigen-B27 positive ankylosing spondylitis in Han Chinese population - Guo Xia; Faming Pan; Fangfang Liao; Xiaowu Tang; Rui Ge; Yang Mei; Heping Pan; Shengqian Xu; Jianhua Xu (Molecular Biology Reports, 2010)

Effects of Neuregulin on Expression of MMP-9 and NSE in Brain of Ischemia/Reperfusion Rat - Qin Li; Rui Zhang; Yin-lin Ge; Yuan-wu Mei; Yun-liang Guo (Journal of Molecular Neuroscience, 2009)

Nine novel microsatellite markers for the hog deer (Axis porcinus) - Hong Lian; Jian-Qiu Yu; Yun-Fa Ge; Sheng-Guo Fang (Conservation Genetics, 2009)

Comparative analysis of distinct non-coding characteristics potentially contributing to the divergence of human tissue-specific genes - Qianli Huang; Jiaming Guo; Qq Ge; Jesse Li-Ling; Xueping Chen; Fei Ma (Genetica, 2009)

Evidence for Tibetan plateau uplift in Qaidam basin before Eocene-Oligocene boundary and its climatic implications - Junling Pei; Zhiming Sun; Xisheng Wang; Yue Zhao; Xiaohong Ge; Xinzhuan Guo; Haibing Li; Jialiang Si (Journal of Earth Science, 2009)

Analysis of synonymous codon usage in the UL24 gene of duck enteritis virus - Renyong Jia; Anchun Cheng; Mingshu Wang; Hongyi Xin; Yufei Guo; Dekang Zhu; Xuefeng Qi; Lichan Zhao; Han Ge; Xiaoyue Chen (Virus Genes, 2009)

Eight novel microsatellite markers from the Père David’s deer (Elaphurus davidianus) - Yang Jiao; Yun-Fa Ge; Sheng-Guo Fang (Conservation Genetics, 2008)

Recovery of viable porcine reproductive and respiratory syndrome virus from an infectious clone containing a partial deletion within the Nsp2-encoding region - Z. G. Ran; X. Y. Chen; X. Guo; X. N. Ge; K. J. Yoon; H. C. Yang (Archives of Virology, 2008)

Characterization of seven genomic and one dbEST-derived microsatellite loci in the river mangrove Aegiceras corniculatum (Myrsinaceae) - Guo-Qing Chen; Lin-Feng Li; Gang Hao; Su-Hua Shi; Xue-Jun Ge (Conservation Genetics, 2008)

Development of thirteen microsatellite loci for Impatiens lateristachys (Balsaminaceae) - Lin-Feng Li; Guo-Qing Chen; Yong-Ming Yuan; Xue-Jun Ge (Conservation Genetics, 2008)

Enhancement of fructanohydrolase synthesis from Aspergillus niger by simultaneous in vitro induction and in vivo acid stress using sucrose ester - Xiang-Yang Ge; He Qian; Wei-Guo Zhang (World Journal of Microbiology and Biotechnology, 2008)

Development of ten microsatellite loci for Gentiana crassicaulis (Gentianaceae) - Yong Li; Lin-Feng Li; Guo-Qing Chen; Xue-Jun Ge (Conservation Genetics, 2007)

Development and characterization of microsatellite markers for an endangered shrub, Ammopiptanthus mongolicus (Leguminosae) and cross-species amplification in Ammopiptanthus nanus - Guo-Qing Chen; Hong-Wen Huang; Ming Kang; Xue-Jun Ge (Conservation Genetics, 2007)

Isolation and characterization of a novel cDNA encoding ERF/AP2-type transcription factor OsAP25 from Oryza Sativa L. - Xiao-Yan Fu; Zhen Zhang; Ri-He Peng; Ai-Sheng Xiong; Jin-Ge Liu; Li-Juan Wu; Feng Gao; Hong Zhu; Zhao-Kui Guo; Quan-Hong Yao (Biotechnology Letters, 2007)

Genomic analysis of two porcine encephalomyocarditis virus strains isolated in China - G. Q. Zhang; X. N. Ge; X. Guo; H. C. Yang (Archives of Virology, 2007)

Improvement of ethanol yield from raw corn flour by Rhizopus sp. - Li-Sen Wang; Xiang-Yang Ge; Wei-Guo Zhang (World Journal of Microbiology and Biotechnology, 2007)

Association of MTHFR C677T and SHMT1 C1420T with susceptibility to ESCC and GCA in a high incident region of Northern China - Yimin Wang; Wei Guo; Yutong He; Zhifeng Chen; Denggui Wen; Xiufeng Zhang; Na Wang; Yan Li; Hui Ge; Jianhui Zhang (Cancer Causes & Control, 2007)

Biological Comparison of Two Genotypes of Helicoverpa armigera Single-Nucleocapsid Nucleopolyhedrovirus - Zhong-Jian Guo; Jun-Qing Ge; Dun Wang; Ya-Ming Shao; Qi-Yi Tang; Chuan-Xi Zhang (BioControl, 2006)

Improved production of an enzyme that hydrolyses raw yam starch by Penicillium sp. S-22 using fed-batch fermentation - Hai-Yan Sun; Xiang-Yang Ge; Wei-Guo Zhang (Biotechnology Letters, 2006)

Reliable genetic analyses based on formalin-fixed materials: a new noninvasive sampling perspective for the giant panda - Qiu-Hong Wan; Jian-Qiu Yu; Yan-Ge Yong; Sheng-Guo Fang (Conservation Genetics, 2006)

A lower specificity PhaC2 synthase from Pseudomonas stutzeri catalyses the production of copolyesters consisting of short-chain-length and medium-chain-length 3-hydroxyalkanoates - Jing-Yu Chen; Ge Song; Guo-Qiang Chen (Antonie van Leeuwenhoek, 2006)

A clinical and molecular-genetic analysis of Chinese patients with lattice corneal dystrophy and novel Thr538Pro mutation in theTGFBI (BIGH3) gene - Ping Yu; Yangshun Gu; Yuehong Yang; Xiaoyi Yan; Liu Chen; Zhen Ge; Ming Qi; Jianmin Si; Lei Guo (Journal of Genetics, 2006)

Effects of Octadecanoylsucrose Derivatives on the Production of Inulinase by Apergillus niger SL-09 - Xiang-Yang Ge; Wei-Guo Zhang (World Journal of Microbiology and Biotechnology, 2005)

Review of digital elevation model (DEM) based research on China Loess Plateau - Guo’an Tang; Shanshan Ge; Fayuan Li; Jieyu Zhou (Journal of Mountain Science, 2005)

Genetic Diversity and Population Differentiation of Liaoning Weedy Rice Detected by RAPD and SSR Markers - Guo-qin Yu; Ying Bao; Chun-hai Shi; Chang-qin Dong; Song Ge (Biochemical Genetics, 2005)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)

The use of dual—Doppler radar data in the study of 1998 meiyu frontal precipitation in huaihe river basin - Xu Hui; Zhang Weiping; Lang Xuxing; Guo Xia; Ge Wenzhong; Dang Renqing; Takao Takeda (Advances in Atmospheric Sciences, 2000)